Les titres sociaux dans le régime de la communauté légale - Geneste, Axelle (Université de Montpellier, 2019)
Cette étude a pour objet de mettre en relation les titres sociaux et le régime de la communauté légale. De manière plus précise, il s’agit d’appréhender les effets et les conséquences pratiques résultant de l’articulation entre le droit des régimes matrimoniaux et le droit des sociétés. Les objectifs assignés à cette étude sont la détermination des points essentiels qui devront impérativement retenir l’attention des rédacteurs d’actes mais aussi tenter, autant que faire se peut, de proposer des solutions théoriques et pratiques aux difficultés rencontrées. L’application des règles de régimes matrimoniaux aux biens particuliers que sont les droits sociaux a nécessairement des conséquences, tant au niveau de l’acquisition que de la perte de la qualité d’associé.
Keywords: Communauté légale; Corporate law; Droit des sociétés; Droits sociaux; Legal communité; Matrimonial regimes; Régimes matrimoniaux; Shares

Le lancement d'alertes en droits français et américain - Schwartz-Miralles, Johanna (Aix-Marseille Université, 2019)
Cette thèse est une étude comparée du droit français et américain en matière de lancement d’alertes. Le droit en matière d’alertes est protéiforme : il englobe plusieurs règles, dont des dispositions en droit du travail, en droit civil, en droit pénal, ou en droit disciplinaire interdisant des actes de rétorsion à l’encontre des lanceurs d’alerte ; des dispositifs qui protègent la confidentialité ou l’anonymat des lanceurs d’alerte ; des devoirs d’alerter ; des restrictions au droit de révéler des informations sensibles ; des procédures obligatoires d’alerte ; ou encore des lois qui autorisent le paiement de récompenses financières aux lanceurs d’alerte. En analysant les textes juridiques français et américains en la matière, cette thèse distingue deux grands modèles dans le domaine du droit d’alerte. Le premier, qui prédomine en France, vise principalement la protection du droit fondamental du lanceur d’alerte à la liberté d’expression ; ce modèle est également dominant au niveau du droit européen. Le deuxième modèle, américain, est axé moins sur la protection du droit du lanceur d’alerte à la liberté d’expression, que sur le rôle de l’alerte dans la détection et la prévention des infractions. Cette thèse montre comment ces deux modèles influencent les choix législatifs et jurisprudentiels français et américains, se concrétisant ainsi en règles de droit parfois similaires, parfois différentes
Keywords: Alerte professionnelle; Compliance programs; Criminalité – Prévention – États-Unis; Disclosure rights; Dispositifs d’alerte; Dodd-Frank; Droit d’alerte; False Claims Act; Freedom of expression; Lanceurs d’alerte; Liberté d'expression – France; Liberté d’expression; Lois Qui tam; Qui tam laws; Sapin II; Sarbanes-Oxley; Whistle blowing; Whistleblower hotlines; Whistleblowers; Études comparatives

Contribution à l'étude du régime juridique de l'apport en industrie en droit OHADA - Touré, Mahamoudou (Université Cheikh Anta Diop, 2019)
Keywords: Apport en industrie; Droit OHADA; Droit des sociétés commerciales

Atividade empresarial e bens comuns: a aplicação do regime de bens comuns para determinados bens da companhia - Ramunno, Pedro Alves Lavacchini (Universidade de São Paulo, 2019)
Este trabalho tem como objetivo analisar a possibilidade de caracterizar determinados bens da companhia como tendo natureza de bem comum, à luz das premissas metodológicas propostas pelo novo estruturalismo jurídico e partindo do conceito de bem comum desenvolvido por Elinor Ostrom. Diante do entendimento pela possibilidade dessa identificação em casos restritos, apresenta-se uma proposta de regulação para tais bens, que são referidos como commons empresariais, o que demanda o enfrentamento das estruturas propriedade e empresa - enquanto atividade empresarial - de acordo com a premissa metodológica apresentada. A partir de uma lente inspirada nas reflexões de Direito e Economia, defende-se que a propriedade deve ser entendida como uma forma de internalização de externalidades e composta por feixes de direitos de propriedade (bundle of rights), ao passo que a atividade empresarial deve ser entendida como um instrumento para maximização de eficiência distributiva, em um posicionamento que se entende alinhado com os preceitos do institucionalismo organizativo, sendo que o preenchimento desse objetivo é identificado com o conceito de melhor interesse da companhia. Diante dessas considerações discutese a forma de internalização de titulares de interesses afetados pela destinação desses commons empresariais, o que deve ser feito sempre visando, justamente, ao melhor interesse da companhia. Nesse contexto defende-se que soluções autorregulatórias (voluntárias e compulsórias) seriam os instrumentos adequados para a promoção desse objetivo, sendo o contrato associativo plurilateral, visto como um método de organização de interesses, a forma jurídica adequada para tanto.
Keywords: Activité commerciale; Bem comum; Bien commun; Biens sociaux; Common empresarial; Common-pool resource; Company's interest; Contrato associativo plurilateral; Corporate common; Distributive efficiency; Eficiência distributiva; Estruturalismo jurídico; Interesse da companhia; Legal structuralism; Patrimoine commun; Plurilateral associative contract

L'autonomisation de la SAS : Réflexion sur la fonction du modèle en droit des sociétés - Alhoussari, Houda (Université de Rennes 1, 2019)
La notion de « modèle » n’a jamais été définie en droit français des sociétés. Le législateur n’utilise pas cette notion, la jurisprudence non plus. Les travaux doctrinaux permettent toutefois de considérer que le terme de « modèle » suppose la réunion de deux critères cumulatifs : l’existence d’une référence et l’imitation de cette référence. De ce point de vue, les traits du « modèle » sont bien présents en droit des sociétés. L’objet de cette étude consiste à s’interroger sur l’applicabilité de la notion de modèle à la société par action simplifiée (SAS). À première vue, le régime juridique de la SAS conduit à en douter. En effet, lors de l’élaboration du régime juridique de la SAS, le législateur a utilisé la technique de la législation par référence qui consiste à se référer explicitement au régime juridique de la SA. Ce dernier a ainsi constitué un modèle pour la SAS. Le rattachement de ces deux régimes pose actuellement un certain nombre de difficultés pour la vie de la SAS qui était initialement conçue comme une société distincte des autres formes sociétaires du fait de sa souplesse. En d’autres termes, alors que la SAS renferme des atouts incontestables liés à sa flexibilité et pourrait, de ce fait, être une référence pour l’élaboration d’autres formes sociétaires, le rattachement de son régime juridique à celui de la SA constitue à l’heure actuelle un obstacle à l’affirmation de la SAS comme modèle. Afin de résoudre cette difficulté, une approche plus créative du régime de la SAS permet de proposer une solution : détacher législativement le régime de la SAS de celui de la SA. L’autonomisation du régime juridique de la SAS constitue alors la condition essentielle qui permettra à la SAS de s’affirmer comme modèle, au sein du système juridique français comme au-delà des frontières nationales.
Keywords: Compatibility; Comptabilité; Corporate law; Droit des sociétés; Détachement de la SA; Flexibility; Imitation; Model; Modèle; Rattachement à la SAS; SA; SA affiliation; SAS; Secondment of the SA; Sociétés anonymes; Sociétés par actions simplifiées; Souplesse; Statut juridique

Les entreprises de conviction d'un point de vue organisationnel et institutionnel : quelles rationalités ? quelles logiques d'action ? - Indanda Beyo, Matthieu (Le CNAM, 2019)
« Les entreprises de conviction », ce vocable apparemment baroque désigne pourtant un élément classique de l’univers des organisations : une entreprise. Et ce, depuis sa définition jurisprudentielle tant par la Cour européenne des droits de l’homme que par la Cour d’appel de Paris et la Cour de cassation, dans une cause médiatiquement surexposée : l’affaire Baby Loup.Ces entreprises de conviction sont encore peu étudiées en sciences de gestion, non faute de matière à réflexion. En effet, au vu des termes de ladite définition « entités au sein desquelles sont expressément prônées une idéologie, une morale, une philosophie ou une politique, autrement dit, l’objet essentiel de l’activité de ces entreprises est la défense et la promotion d’une doctrine ou d’une éthique », la notion même d'entreprise est réinterrogée.C'est pourquoi, à partir d’une question centrale simple « Qu’est-ce une entreprise de conviction et quel est son apport dans l’ordre des connaissances ?», une réflexion historico-théorique a été proposée, aboutissant à restituer son apparition et son existence comme phénomène de création humaine, avec un ancrage éthico-religieux. Et ce, sous des traits et des caractéristiques que l’on a pu confronter aux réalités observées sur des terrains divers. « Enterprises of conviction», this term somewhat baroque designates however all that is classic in the universe of organizations: a company. And this, since its definition according to the jurisprudence of both the European Court of Human Rights and the Court of Appeal of Paris and the Court of Cassation, in a media overexposed legal case: the case Baby Loup.They are still little studied in Management Science, but neverthless they should give plenty to think about, given the very terms of the definition « entities within which are expressly advocated an ideology, a morality, a philosophy or a policy, in other words, 'essential object of the activity of these enterprises is the defense and the promotion of a doctrine or an ethics » which reexamines the very notion of the company.Thus,from a simple central question ''What is an enterprise of conviction and what is its contribution in the order of knowledge?'', we attempt to undertake a historical-theoretical reflection resulting in restoring its appearance and its existence as a phenomenon of human creation, with a certain ethico-religious anchorage. And this, under features and characteristics that we could confront by the facts observed on different field work.
Keywords: Alternative; Bienfaisance; Charity; Convictions; Enterprise; Entreprise; Entreprises de tendance (gestion); Entreprises de tendance (histoire); Ethic; Humain; Human; Jesuit and franciscans; Jésuites et franciscains; Marchand; Merchant; Sociologie des organisations; Éthique

La place des associés minoritaires dans la gouvernance des entreprises en droit OHADA - Muberankiko, Gervais G. (Université Cheikh Anta Diop, 2019)
Keywords: Associé minoritaire; Droit OHADA; Droit des sociétés commerciales; Gouvernance d'entreprise

Approche renouvelée du régime juridique de la cession de droits sociaux dans les sociétés commerciales en droit français et en droit OHADA - Sawadogo, Félicité (Université de Bordeaux, 2019)
En France et dans l’espace OHADA, la cession de droits sociaux est une opération économique considérablement pratiquée dans des milliers de sociétés commerciales. Pourtant, la loi ne prévoit pas un cadre formellement dédié à son régime juridique. Face à ce vide juridique, la jurisprudence, la doctrine et les praticiens tentent de lui appliquer des régimes juridiques préexistants, mais forcément inadaptés. C’est ainsi que l’on assiste tout naturellement à une appropriation civiliste de l’opération qui est considérée aujourd’hui comme un acte civil. Or, elle a tout le caractère d’un acte fondamentalement commercial. C’est pourquoi la présente étude propose une approche qui priorise sa commercialité.
Keywords: Cession; Commercial Companies; Comparative law; Corporate law; Droit OHADA; Droit comparé; Droit des sociétés commerciales; Droit français; Droits sociaux; Law French; Law OHADA; Legal regime; Régime juridique; Social Rights; Transfer

Etude comparée en droit OHADA et français de la protection du créancier chirographaire d'une société en difficulté - Mafeuguemdjo, Blandine (Université de Nantes, 2019)
L’exercice d’une activité économique est un parcours semé d’obstacles. En témoigne le nombre de liquidations judiciaires clôturées pour insuffisance d’actif. On dénombre pour l’année 2018 en France, 37 214 liquidations judiciaires contre 16 359 redressements judiciaires. Pareillement, dans l’espace OHADA, malgré l’inexistence d’étude permettant de quantifier le nombre de défaillances de sociétés, on sait que les liquidations judiciaires restent importantes et problématiques. Beaucoup de sociétés meurent sans même qu’ait été ouverte une procédure collective, surtout celles évoluant dans le secteur informel. Cette situation n’est pas sans conséquence sur la situation des créanciers chirographaires qui ne disposent d’aucune garantie réelle ou personnelle. Or, le statut de créancier chirographaire ne résulte pas, le plus souvent, d’un choix du créancier concerné. C’est une situation qui s’impose à lui, notamment pour des raisons liées au coût de la prise d’une garantie. Cette situation est d’autant plus inquiétante que le créancier chirographaire impayé risque de devenir, à son tour, un débiteur en difficulté. Il est donc important de chercher un moyen de le protéger. Le premier moyen pour ce faire est d’éviter qu’il soit confronté à une situation d’impayé ce qui passe par des actions préventives visant à prévenir, pour les éviter, les difficultés de ses débiteurs. Les mécanismes de prévention des difficultés doivent à cet égard être aménagés pour une meilleure implication des créanciers chirographaires dans le traitement précoce des difficultés de la société. Par ailleurs, parce que la prévention n’empêche pas la survenance des difficultés, il est important de chercher comment préserver les créanciers chirographaires lorsqu’une procédure collective est malgré tout ouverte. La souscription d’une assurance peut alors être envisagée. The exercise of an economic activity is a path fraught with obstacles. This is evidenced by the number of liquidations closed for lack of assets. For the year 2018 in France, there are 37,214 judicial liquidations against 16,359 judicial restatements. Similarly, in the OHADA space, despite the absence of a study to quantify the number of corporate failures, we know that the judicial liquidations remain significant and problematic. Many societies are dying without even going through a collective process, especially those operating in the informal sector. This situation is not without consequences for unsecured creditors who have no real or personal guarantee. The status of unsecured creditor does not, in most cases, result from a choice of the creditor concerned. This is a situation that is imposed on him, especially for reasons related to the cost of taking a guarantee. This situation is all the more worrying as the unsecured creditor may become, in turn, a debtor in difficulty. It is therefore important to look for a way to protect it. The first way to do this is to prevent it from being confronted with an unpaid situation, which involves preventive actions aimed at preventing, in order to avoid them, the difficulties of its debtors. In this respect, the mechanisms for preventing difficulties must be geared to better involving unsecured creditors in the early treatment of society's difficulties. On the other hand, because prevention does not prevent the occurrence of difficulties, it is important to look for ways to preserve unsecured creditors when a collective proceeding is still open. The subscription of an insurance can then be considered.
Keywords: Droit OHADA; Droit comparé; Droit français; Débiteur et créancier; Entreprise en difficulté; OHADA

La salida voluntaria del socio profesional: especial referencia a las sociedades profesionales de capital - Lorenzo Camacho, María Salomé (Universidad de Sevilla, 2019)
Keywords: Associé; Retrait d'associé

La contractualisation du droit des sociétés : l'ordre public à l'épreuve de la liberté contractuelle dans les sociétés commerciales de l'OHADA - Houenou, Emmanuel Sèmassa (Université d'Abomey-Calavi ; Université Paris 1, 2019)
Dès l’adoption en 1997 de l’AUSC, le caractère d’ordre public des règles qui y sont éditées a été au cœur de maintes interrogations de la part des praticiens et de la doctrine. L'ensemble des dispositions de cet acte uniforme resté étaient déclarées d'ordre public par le législateur qui faisait ainsi un choix difficile à comprendre en ce qu’il s’inscrit totalement aux antipodes de la dynamique contemporaine. En effet, l’une des évolutions notables du droit des sociétés à la fin du 20e siècle est la tendance vers un droit souple dans laquelle la volonté des associés occupe une place de choix. On s'attend alors légitimement à une réforme de I'AUSC qui promeuve le recours dans la réglementation de leurs sociétés. Pourtant, depuis l'adoption de ladite réforme en Janvier 2014, la doctrine n'est pas unanime sur la portée du choix du législateur Ohada d'orienter le droit des sociétés dans le sens de la contractualisation. Ainsi, pendant que certains voient dans la réforme, un triomphe de la liberté contractuelle, d'autres n'y voient qu’une apparente consécration de l'autonomie de la volonté qui ne cacherait qu’un même droit rigide exclusivement constitué de règles d'ordre public. En tant que tel, il était opportun d’évaluer la portée du phénomène contractuel dans le droit des sociétés de l’Ohada et d’apprécier l’efficacité des mécanismes qui y concourent. Ainsi, en partant d’une analyse substantielle du droit positif, la présente étude a révélé un réel recul de l'ordre public sociétaire et un profond assouplissement du régime juridique des formes sociales jusque-là connues pour leur caractère institutionnel avéré. Since the Uniform Act on General Commercial Law came into force in 1997, the public policy nature of the rules enacted has been questioned by practitioners and doctrine. All the provisions of this uniform act were declared mandatory by the legislator who made the difficult choice of diverting the contemporary trend. Indeed, one of the most significant developments in company law since the end of the 20th century is the move towards a flexible law in which the will of the shareholder is prominent. A reform of the Uniform Act on General Commercial Law then became necessary in order to allow the use of contractual mechanisms and adapt OHADA company law to the needs of shareholders.Yet since the law reform in January 2014, scholars are not unanimous on the extent which the OHADA legislator has stretched contract in company law. Thus, while some see the reform as a triumph of contractual freedom, others see it as a mere boost in party autonomy uphelding the same rigid law exclusively made of non deregatory rules. As such, it was appropriate to assess the scope of contractualism in OHADA company law as well as the effectiveness of the related contractual mechanisms. Focusing on a substantial analysis of existing laws, this contribution shows a real decline of public policy in company law and a deep flexibility in the legal regime of companies hitherto for their rigid institutional character.
Keywords: ADR; Alternative dispute resolution; Company law; Contractual freedom; Contractualisation; Contrats; Conventions extrastatuaires; Corporate law; Droit des sociétés; Extra-statutory conventions; Liberté contractuelle; Limited company; Modes alternatifs de règlement des conflits; OHADA; Ordre public; Organisation pour l'harmonisation en Afrique du droit des affaires – Pays de l'OHADA – 1990-2020; Public policy; Règlement de conflits; Société Anonyme

La protection de l'intérêt social dans la réforme du droit OHADA des sociétés commerciales au regard de la "corporate governance" - Sani Mani, Larwanou (Université Cheikh Anta Diop, 2019)
Keywords: Corporate governance; Droit OHADA; Droit des sociétés commerciales; Intérêt social (protection)

La faute de gestion en droit OHADA des sociétés commerciales - Faye, Gilbert Coumakh (Université Cheikh Anta Diop, 2019)
Keywords: Droit OHADA; Droit des sociétés commerciales; Faute de gestion

Abuse of legal personality to avoid tax : piercing the corporate veil as remedy in case of the abuse of legal personality for tax purposes - Marais, Albertus Johannes (Stellenbosch University, 2019)
Companies are legal persons and as much part of commercial traffic as the natural persons owning and controlling them. Compared to one another, companies and natural persons nevertheless have very different legal abilities and characteristics. It is therefore not unexpected that they are treated differently for purposes of the law of taxation. As a result it may often be more beneficial to have the profits generated by a business enterprise taxed in a company rather than in the hands of a natural person, especially in instances where a shareholder would be commercially indifferent to whether those profits are generated in a company or not. By using the separate legal personality of a company shareholders may often perpetrate an abuse of that separate legal personality. Such abuse of legal personality can also take place when legal personality is employed primarily for tax reasons. While a limited form of abuse of the corporate veil is tolerated, whether the use of separate legal personality for tax reasons amounts to an abuse thereof beyond what is permitted in South Africa can be determined in terms of three tests. These tests are the traditional “piercing of the corporate veil” judgments forming part of the common law, section 20(9) of the Companies Act 71 of 2008 and the General Anti-Avoidance Rules (“GAARs”) (and other specific provisions) in the Income Tax Act 58 of 1962. This dissertation considers when any of these various tests will dictate that the separate personality of a company be ignored (or “pierced”) for purposes of taxes levied in terms of the Income Tax Act. Through critical analysis of both the South African rules on piercing as applied for tax purposes as well as the circumstances under which selected other jurisdictions provide for piercing for tax reasons the dissertation formulates what best practice and desired policy for piercing for tax reasons are.
URI: http://hdl.handle.net/10019.1/106096
Keywords: Close Corporations Act; 1984; Companies Act; 2008; Corporate veil; Corporations; Income Tax Act; 1962; South Africa; Tax evasion; Taxation; Unconscionable abuse

Regulation of takeovers and mergers with an emphasis on the mandatory offer rule: a comparative and critical analysis of the law and the institutions that have been set up to enforce the law - Phakeng, Madimetja A. L. (Stellenbosch University, 2019)
ENGLISH ABSTRACT :This dissertation assesses the regulation of takeovers and mergers and the institutions created to enforce the law, from a comparative perspective. It uses South Africa as its point of departure and takes the laws of Delaware in the United States, the United Kingdom and Australia into account. The dissertation indicates that numerous takeover provisions in South Africa are poorly formulated, making them difficult to interpret and apply. Accordingly, the dissertation recommends amendment and improvement of certain Takeover Provisions. Special emphasis is placed on the mandatory offer requirement. The dissertation critically and comparatively analyses this requirement and especially its impacts on the market for corporate control, efficient usage of capital, corporate governance and (in South Africa) Broad Based Black Economic Empowerment. It appears from the literature explored that the mandatory offer requirement originated from the Perlman case in the United States as an expression of the equal opportunity rule. According to the equal opportunity rule, the controlling stake of a company is enriched with a premium of control, which must be shared with other shareholders when there is a change of the controlling shareholder. Shareholders must be given an equal opportunity to share in this control premium. Hence, a mandatory offer must be made to the remaining shareholders of the company by the new controlling shareholder at a price at which control was bought. Perlman case was decided in the United States of America during 1955. It is contended in the dissertation, that the mandatory offer requirement in section 123 of the Companies Act 71 of 2008 (“the Act”), can ultimately be traced back to this case. Researchers have criticised the mandatory offer requirement in a number of respects. It has been pointed out that the rationale for the decision in the Perlman case was not clear and applied in limited circumstances. Other scholars point out that the case was not a final decider on the sharing of the control premium due to later judicial pronouncements that differed with that case. Despite these commentaries, it appears that the case became a basis for imposing and enforcing this most debated rule in takeover and merger law. The dissertation concludes that the sharing of a premium of control, as envisaged by the mandatory offer requirement, is not enforced in the state of Delaware. It further concludes that in the UK, the mandatory offer rule forms the cornerstone of enforcement of the equal opportunity rule, but that widely dispersed shareholding ameliorates it negative consequences in that jurisdiction. The dissertation favours the Australian approach. That jurisdiction does not require a mandatory offer similar to that in section 123 of the Act, but, Australian Takeover Provisions, unlike their South African equivalent, have been tailor-made for Australian market conditions. The dissertation accordingly concludes that the mandatory offer requirement in section 123 of the Act in its current form is not appropriate for South Africa.
URI: http://hdl.handle.net/10019.1/105995
Keywords: Consolidation of corporations; Delaware; Great Britain; Merger of corporations; Regulation; South Africa

Finansal tabloların tutulması ve hukuksal sonuçları - Aksu Özkan, Raziye (Akdeniz Üniversitesi, 2019)
"Bu çalışmada finansal tabloların işlevleri, çeşitleri, düzenlenmesi ve tutulmasından kaynaklanan hukuksal sonuçlar incelenmiştir. Finansal tablolar, işletmenin finansal durumunun ve finansal performansının biçimlendirilmiş sunumudur. Bu tablolar aracılığıyla, şirketin finansal durumu hakkında bilgilendirme yapılmaktadır. Finansal tablolar, özellikle yabancı yatırımcının şirketlere güvenip yatırım kararı alması açısından önem arz etmektedir. Bu bağlamda, Türk Ticaret Kanunu'nun (TTK) genel gerekçesi beşinci paragrafında, uluslararası piyasaların bir parçası olmak hedefi ortaya konulmuştur. Hedefe ulaşmak için, finansal tabloların uluslararası standartlara göre düzenlenmesi gerekliliğine yer verilmiştir. Hedefe ulaşmada yeterli düzenleme yapılması konusunda Kamu Gözetimi, Muhasebe ve Denetim Standartları Kurumu görevlendirilmiştir. Kurum tarafından yapılan düzenlemeler, uluslararası muhasebe standartlarının çevirisinden ibaret olup, yeterli değildir. TTK ile muhasebe uygulaması arasında köprü kurulamamıştır. Ticaret ve vergi hukuku alanında yer alan düzenlemeler kapsamında iki ayrı uygulama yürütülmektedir. Finansal tabloların işletmenin finansal durumunu, finansal performansını ve nakit akışlarını gerçeğe uygun olarak sunması gereklidir. Kural olarak standartlara uygunluk, bilgilerin gerçeğe uygun şekilde açıklanması için yeterlidir; ancak bu uygunluk gerçek durumunu yansıtmıyorsa standartlar uygulanmayabilecektir. Finansal tablolar bilanço, döneme ait kar veya zarar ve diğer kapsamlı gelir tablosu, özkaynak değişim tablosu, nakit akış tablosu, önemli muhasebe politikalarını ve diğer açıklayıcı bilgileri içeren dipnotlardan oluşur. Bilanço, işletmenin hazırlandığı tarih itibariyle varlık, yükümlülük ve özkaynaklarını gösteren finansal tablodur. İşletmenin sahip olduğu her türlü malvarlığı unsuru veya katlandığı her sorumluluk bilançoda muhasebeleştirilemez. Bunun için standartlarda sayılan koşulları taşımaları gerekmektedir. Bilanço dışındaki diğer finansal tablolar, ya bilançonun hazırlanması açısından birer araçtır ya da bilançonun tamamlayıcısıdır. Tabloların içeriğinde yer alan bilgilerin birbiriyle ilişkisi, bunların bir bütün olarak değerlendirilmesi gerektiğini ortaya koymaktadır. Finansal tabloların tutulmasının yönetim kurulu, denetim ve genel kurul açısından hukuki sonuçları bulunmaktadır. Yönetim kurulu finansal tabloları hazırlar ve genel kurula sunar. Bununla birlikte, denetim finansal tablolar esas alınarak yapılacaktır. Buna bağlı olarak, denetçi şirket hakkında denetim raporunu oluşturacaktır. Genel kurul, denetimden geçmiş finansal tablolara dayanarak şirkete ve yönetim kuruluna ilişkin kararlar alacaktır. In this study, the legal results arising from the functions, types, regulation and retention of the financial statements are examined. Financial statements are a structured representation of the financial position and financial performance of an entity. These tables provide information on the financial position of the company. Financial statements are especially significant for foreign investors to trust companies and make investment decisions. In this context, the fifth paragraph of the general justification of the Turkish Commercial Code (TCC) aims to be a part of international markets. In order to reach the target, it is necessary to arrange the financial statements according to international standards. The Public Oversight, Accounting and Auditing Standards Authority has been appointed to ensure adequate regulation to reach the target. The regulations made by the institution consist of translation of international accounting standards and are not sufficient. No bridge could be established between the TCC and the accounting practice. Within the scope of the regulations in the field of trade and tax law, two different applications are carried out. Financial statements shall present fairly the financial position, financial performance and cash flows of an entity. As a rule, compliance with standards is sufficient for the information to be truthfully disclosed; however, if this compliance does not reflect the actual situation of the company, the standards may not apply. The financial statements comprises balance sheet, a statement of profit or loss and other comprehensive income for the period, a statement of changes in equity, a statement of cash flow, notes, comprising significant accounting policies and other explanatory information. The balance sheet is the financial statement showing the assets, liabilities and equity of the entity. Any asset that the entity owns or any liability that it endures cannot be recognized in the balance sheet. For this, they must meet the requirements listed in the standards. Other financial statements, other than the balance sheet, are either tools for the preparation of the balance sheet or complementary to the balance sheet. For this reason, the relationship between the information contained in the content of the tables suggests that they should be evaluated as a whole. The holding of the financial statements has legal consequences for the board of directors, auditing and general assembly. The Board of Directors shall prepare the financial statements and present them to the General Assembly. However, the audit will be performed on the basis of financial statements. Accordingly, the auditor will establish an audit report on the company. The General Assembly shall take decisions regarding the company and the board of directors on the basis of audited financial statements."
Keywords: Commercial law; Compliance with laws; Financial statements; Finansal tablolar; Hukuka uygunluk; Hukuksal esaslar; International Accounting Standards; Legal aspects; Standards; Standartlar; Ticaret hukuku; Turkish Accounting Standarts; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Türkiye Muhasebe Standartları; Uluslararası Muhasebe Standartları

Anonim şirketlerde yönetim kurulunda temsil edilme imtiyazı - Baltali, Candemir (İstanbul Bilgi Üniversitesi, 2019)
Bu çalışma İstanbul Bilgi Üniversitesi Hukuk Fakültesi Özel Hukuk Doktora Tezi olarak hazırlanmıştır. Tezin konusunu anonim şirketlerde yönetim kurulunda temsil edilme imtiyazı oluşturmaktadır. 6012 sayılı Türk Ticaret Kanunu ile imtiyazlara ilişkin yeni bir düzen getirilmiş, ayrıca yönetim kurulunda temsil edilme hakkı normatif düzenlemeye kavuşturulmuş ve belirli gruplar ile azlığa temsil edilme hakkı tanınabileceği hükme bağlanmıştır. Tez kapsamında ilk olarak imtiyaz kavramı ve imtiyazlara ilişkin temel ilkeler incelenmiştir. Takip eden bölümde yönetim kurulunda temsil edilme hakkı irdelenmiştir. Tezde en önemli amaç, temsil edilme hakkını etraflıca incelemek ve temsil edilme hakkıyla imtiyazlar arasında kurulan köprüyü tanıtmak olmuştur. Bu itibarla, bir imtiyaz olarak nitelendirilen temsil edilme hakkının, diğer imtiyazlardan ayrılan özellikleri üzerinde durulmuştur. Ayrıca temsil edilme hakkının tanınabileceği zümreler ile tanındığı her bir zümre özelinde hakkın hukuki niteliğine yönelik tespitlerde bulunulmuş ve öğretide pek tartışılmamış olan temsilci üyenin niteliği ele alınmıştır. Devamında temsil edilme hakkına dair yöntemler incelenmiş ve çeşitli esas sözleşme hükümleri yorumlanmıştır. Tezde karşılaşılan hukuki sorunların işlevsel bir menfaat hukukçuluğu çerçevesinde yanıtlanmasını hedefleyen bir yöntem benimsenmiştir. Yorum yapılırken amaçsal yorum metodu kullanılmış, saptanan hukuki sorunlar için de lege lata çözüm önerilerinde bulunmaya gayret edilmiştir. This paper is prepared as Istanbul Bilgi University Faculty of Law Private Law PH.D. Dissertation. Subject of the dissertation is the privilege to be represented in the board of directors of joint stock companies. Turkish Commercial Code numbered 6102 introduced a paradigm shift in relation to the privileges, regulated the right to be represented in the board of directors and set forth that such right may be granted to certain groups and minority. Firstly, privilege concept and principles surrounding the privileges have been examined in the dissertation. Following section focuses on the right to be represented in the board of directors. The substantial purpose of the dissertation is to introduce the right to be represented and the correlation between such right and privileges. Thus, the differences between the right to be represented which is a privilege and other privileges have been set forth. Further, determinations have been made on classes that may be granted with the right to be represented and legal qualifications of the right by taking into consideration each class that may be granted with such right, and characteristics of the representative, a subject so far that has not been examined in detail by doctrine, have been discussed. Methods of right to be represented are examined and miscellaneous articles of association provisions are interpreted in this regard. The method adopted in the dissertation aims to respond to the legal problems within the frame of taking into consideration the interests of the shareholders. The teleological interpretation methodology has been used for interpretations and proposals of de lege lata solutions to the legal problems have been endeavored.
581706
Keywords: Anonim şirketler; Board of directors; Concessions; Consumer right to representation; Joint stock company; Privileged share; Temsil edilme hakkı; Turkish Commercial Code; Turkish Commercial Law; Türk Ticaret Hukuku; Türk Ticaret Kanunu; Yönetim kurulu; İmtiyazlar; İmtiyazlı pay

Anonim şirketlerde yönetim kurulunun yönetim ve temsil yetkisinin devri ve sınırlandırılması - Büyükatak, Aytuğ (İstanbul Kültür Üniversitesi, 2019)
Anonim şirketin yönetim ve temsil yetkileri 6102 sayılı Türk Ticaret Kanunu'nda ayrı başlıklarda düzenlenmiştir. TTK'da, anonim şirketlerde yönetim yetkisinin devri için esas sözleşmede devre izin veren bir hükmün bulunması ve yönetim organizasyonuna ilişkin bir iç yönerge hazırlanması gerekmektedir. Bu hususlara uygun şekilde, yönetim kurulu alacağı bir karar ile yönetim yetkisinin tamamını veya bir kısmını kurul üyelerine ve/veya üçüncü kişilere devredebilecektir. Temsil yetkisinin devri ve sınırlandırılmasına ise TTK, kanuni ve iradi sınırlandırmaların yanısıra 371. maddenin 7. Fıkrasında yapılan ekleme ile sınırlı temsilci tayini hususunda yeni ve eleştirilen bir rejim getirmiştir. Bu bağlamda çalışmamızda, yönetim ve temsil yetkilerinin devir ve sınırlandırılmasının kapsamı, devir ve sınırlandırmalar için uyulması gereken şartlar, yönetim yetkisi ile temsil yetkinin devri arasındaki ilişki ve bu yetkilerin devredilebileceği kişiler inceleme konusu yapılmakta ve bu konulara ilişkin güncel tartışmalar ele alınmaktadır. Anahtar Kelimeler: Anonim Şirket, Yönetim Kurulu, Yönetim Yetkisi, Temsil Yetkisi, Yetki Devri, Örgüt Yönergesi, Sınırlı Yetkili, Sınırlı Temsilci, Sorumluluk. Management rights and representation rights in joint stock companies have been regulated under separate subjects in 6102 numbered Turkish Commercial Code. According to Turkish Commercial Code, joint stock companies that want to delegate the management rights should have a provision on their articles of association that allows such delegation and should prepare internal rules regarding the organization of management. According to such terms, the board of directors may delegate its management Powers fully or partially to one or more board members and/or third parties by issuing a decision on such matter. Regarding the delegation and limitation of representation rights, the addition of seventh paragraph to article 371. of Turkish Commercial Code, has introduced a new and highly criticized regime on such matter besides the legislative and voluntary limitations. In this context, our study will review the limits of delegation and limitation of management and representation right, requirements for such delegation and limitation, the relationship between right of management and right of representation, persons whom the powers may be delegated and the up-to-date discussions on such subjects. Keywords: Joint Stock Company, Board of Directors, Management Right, Representation Right, Delegation of Rights, Internal Rules, Limited Authority, Representative with Limited Power, Responsibility.
554902
Keywords: Anonim şirketler; Board of directors; Company management; Joint stock company; Representation; Representative authority; Subsidiarity; Succession; Temsil; Temsil yetkisi; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yetki devri; Yönetim devri; Yönetim kurulu; Şirket yönetimi

Bağlı şirketin borçlarından dolayı hakim şirketin sorumluluğu - Demi̇rtaş Nevzer, Sebla (Kocaeli Üniversitesi, 2019)
Birbirinden bağımsız birden fazla şirketin bir araya gelmek suretiyle bir organizasyon oluşturmalarına sıklıkla karşılaşılmakta, bu organizasyona ise şirketler topluluğu denilmektedir. Kuruluşların faaliyet alanlarını genişletmek istemeleri, bu yönde maliyetlerini en aza indirerek kârlılıklarını arttırmak için bir araya gelmeleri sonucunda ticari açıdan bir organizasyon oluşturmaları ülkemizde de sıklıkla görülmektedir. Ancak mevcut kanunlarımızda bu şekilde oluşan organizasyonlara yönelik herhangi bir özel düzenlemeye daha önce yer verilmemişti. Bu tür durumlarla farklı hukuk alanlarında da sıklıkla karşılaşılması, zamanla şirketler topluluğu açısından yasal düzenleme yapılması gereğini doğurmuş ve şirketler topluluğuna ilişkin düzenlemeler ilk olarak 6102 sayılı Türk Ticaret Kanunu ile yapılmıştır. Bu düzenlemeler, topluluk yapılanmasının, organizasyon şemasının kurulmasını, işleyişi ve ilgililerin sorumluluğunun belirlenmesini amaçlamaktadır. Ticaret Kanununda düzenlenen şirketler topluluğuna ilişkin hükümlerin önemli bir bölümü Alman Konzern Hukuku esaslıdır. Çalışmamızda kanundaki şirketler topluluğu düzenlemeleri incelenirken, Türk Hukuku esas alınmış ve konu diğer hukuk dalları ile birlikte çok yönlü bir şekilde ele alınarak şirketler topluluğu düzenlemelerinin uygulanabilirliğinin sağlanması hedeflenmiştir. Bağlı şirketin borçlarından dolayı hakim şirketin sorumluluğunu irdeleyen çalışmamızda, şirketler topluluğunun temel kavramları, şirketler topluluğunda sorumluluk halleri ile bağlı şirketin üçüncü kişilere karşı sorumluluğu konusu, özellikle fiili şirketler topluluğu kapsamında ve anonim şirket temelinde incelenmiştir. Ayrıca şirketler topluluğu düzenlemelerinin uygulama yelpazesinin genişletilmesine katkı sağlaması amacı ile diğer hukuk alanlarına da değinilmek suretiyle çok yönlü araştırma yapılmıştır. Anahtar Kelimeler: Şirketler Topluluğu, Sorumluluk, Hakim Şirket, Bağlı Şirket. It is frequently seen that multiple companies independent from each other come together to form an organization and this organization is called a group of companies. In our country, it is frequently observed that entities form a commercial organization by coming together around the desire of extending their field of activity and in order to reduce costs and increase profitability. However, existing laws lacked a specific regulation in connection with organizations that are formed as such. Encountering such cases in different fields of law has, in time, led to the requirement of a legislative regulation about group of companies and regulations have been introduced for the first time in connection with group of companies under Turkish Commercial Code No. 6102. These regulations are aimed at stipulating the structuring of the group of companies, forming the organizational chart, and determining operational aspects and responsibilities of the concerned persons. Substantial part of the provisions regarding group of companies regulated under Commercial Code is based on German Konzern Law. The present study is focused on group of companies regulations under the Law based on Turkish law and the subject matter is addressed in an in-depth approach based on other branches of the law in order to establish enforceability of the group of companies regulations. In the present study analysing liability of the Dominant Enterprise in connection with debts of an Affiliated Company, basic concepts related with group of companies, liabilities in a group of companies and liability of anAffiliated Company towards third persons are explained within the scope of actual group of companies and joint stock companies. In addition, an in-depth study has been conducted based on other fields of the law for the purpose of contributing to extension of the enforcement range of regulations on group of companies. Keywords: Group of companies, Liability, Dominant Enterprise, Affiliated Company.
566846
Keywords: Borçlar; Borçlu; Businesses; Company law; Debtor; Debts; Dette; Dominant position; Filiale; Hakim durum; Hukuki sorumluluk; Kanunlar 6102 sayılı; Laws 6102 numbered; Legal responsibility; Responsabilité; Responsibility; Société mère; Sorumluluk; Turkish Commercial Code; Turkish Commercial Law; Türk Ticaret Hukuku; Türk Ticaret Kanunu; İşletmeler; Şirketler hukuku

Şirket birleşmelerinde ortakların dava yoluyla korunması - Sarikaya, Sinan (Marmara Üniversitesi, 2019)
Şirket birleşmelerinde ortakların korunması, belirlediği ilkeler ve tanıdığı dava hakları nazara alındığında, kanun koyucunun özel önem atfettiği hususlardan biridir. Devrolunan şirketin ortaklarının, mevcut pay ve haklarını karşılayacak değerde, devralan şirket pay ve haklarını iktisap etmesi esastır. Birleşmenin ortakların malvarlığı cephesinde yarattığı olumsuz sonuçlar, ortaklığın devamlılığı ilkesi çerçevesinde, denkleştirme davası ile denetlenmektedir (TTK m. 191). Bu davada ortaklar, pay ve haklarının gereğince korunmamış veya ayrılma akçesinin uygun belirlenmemiş olması gerekçesiyle, uygun bir denkleştirme isteyebilirler. Öte yandan, Kanun'un birleşmeye ilişkin hükümlerinin ihlali, yine ortakların açabileceği, özel iptal davası ile denetlenmektedir (TTK m. 192). Kanun koyucu, ilgili hükümlerin ihlaline iptal sonucunu bağlamakta; ancak eksikliklerin giderilmesi mekanizması ile bu ağır yaptırımla karşılaşılmaması için devralan şirkete olanak tanımaktadır. Son olarak, birleşme işlemlerine katılan bütün kişilerin, ortaklara karşı kusurları ile vermiş oldukları zararlardan sorumlu oldukları düzenlenerek, ortakların zararlarını tazmin edecek bir özel sorumluluk davası öngörülmektedir (TTK m. 193). Böylece birleşme karşısında ortaklar, üç farklı mekanizma ile koruma altına alınmış olmaktadır. Regarding the principles determined and the right to sue recognized, the protection of the shareholders in the mergers is one of the issues that the legislator attaches special importance to. It is essential that the shareholders of company being acquired attain the shares and rights in the acquiring company equivalent to those in the company being acquired. The negative results of merger on the assets of the shareholders are reviewed by an examination case within the framework of the continuity of the partnership principle (TCC Art. 191). In the present case, the shareholders may demand an appropriate compensation on the grounds that their share and rights are not properly protected or the amount of any cash payment is not determined appropriately. On the other hand, the violation of the provisions of the Law relating to the merger is controlled by a special nullification case, which could be filed by the shareholders (TCC Art. 192). The legislator has concluded the nullification of the violation of the relevant provisions; however, the elimination of deficiencies mechanism allows the acquiring company to avoid it. Finally, it is foreseen a liability case to compensate shareholders' damages that allows all persons participating in the merger transactions are liable for the damages they incurred against the them (TCC Art. 193). Thus, the partners are protected by three different mechanisms against the merger.
Keywords: Annulment action; Associés; Birleşmeler; Cases; Commercial law; Davalar; Denkleştirme; Equalization; Fusion d'entreprises; Liability case; Litige; Mergers; Ortaklar; Ortaklık; Partners; Partnership; Sorumluluk davası; Ticaret hukuku; Turkish Commercial Code; Türk Ticaret Kanunu; İptal davası; Şirket birleşmeleri

Anonim şirket yönetim kurulu üyelerinin Rekabet Hukukundan kaynaklanan sorumluluğu - Seyman, Seda (Dokuz Eylül Üniversitesi, 2019)
Bu çalışmada anonim şirket yönetim kurulu üyelerinin Rekabet Hukukundan kaynaklanan sorumluluğu incelenmiştir. Anonim şirket kural olarak yönetim kurulu tarafından alınan kararlar ile faaliyetini sürdürür. Anonim şirkette yönetim kurulu üyesi olarak görev yapan kişiler birtakım haklara sahip oldukları gibi yükümlülük altına da girerler. Yönetim kurulu üyeleri kanunda kendileri için getirilen yükümlülüklerini ihlal ettikleri takdirde halinde yönetim kurulu üyelerinin hukuki ve cezai sorumluluğuna gidilir. Anonim şirket yönetim kurulunun hukuki sorumluluk sebepleri ve sorumluluğun şartları Türk Ticaret Kanunu'nda ayrıntılı olarak düzenlenmiştir. Yönetim kuruluna yaptırım uygulanabilecek düzenlemeler Türk Ticaret Kanunu'nda düzenleniyor olmakla birlikte, yönetim kurulu üyelerine yaptırım uygulanmasına imkan veren düzenlemeler mevcuttur. Bu düzenlemelerden biri de Rekabetin Korunması Hakkında Kanun'da yer almaktadır. Rekabetin Korunması Hakkında Kanun'un 16'ıncı maddesinde hem teşebbüs yahut teşebbüs birliklerine hem de teşebbüs ve teşebbüs birliğinin yönetici yahut çalışanına yaptırım uygulanmasına imkan veren düzenleme yer almaktadır. Söz konusu düzenleme uyarınca, , anonim şirket rekabeti sınırlayıcı anlaşma, uyumlu eylem ve kararlar, hakim durumun kötüye kullanılması yahut birleşme veya devralma sebebi ile idari para cezasına hükmedilmesi mümkündür. Maddede aynı zamanda Rekabet Kanunu'nun 16'ıncı maddesinin üçüncü fıkrası gereğince teşebbüs veya teşebbüs birliklerine üçüncü fıkrada belirtilen idarî para cezaları verilmesi halinde, ihlalde belirleyici etkisi saptanan teşebbüs veya teşebbüs birliği yöneticilerine ya da çalışanlarına teşebbüs veya teşebbüs birliğine verilen cezanın yüzde beşine kadar idarî para cezası verilebileceğine ilişkin düzenleme yer almaktadır. Çalışmanın birinci kısmında genel olarak Rekabet Hukukuna değinilecektir. İkinci kısmında ise Rekabet Kanunu'nun 16'ıncı maddesinin üçüncü fıkrası uyarınca teşebbüs ve teşebbüs birliklerine uygulanacak yaptırımın şartları ve yaptırımın uygulanması usulü incelenecektir. Çalışmanın son kısmında ise anonim şirket yönetici ve çalışanlarına uygulanacak yaptırımın koşulları ile yaptırımın uygulanması usulü ayrıntılı olacak incelenecektir. Anahtar Kelimeler: Anonim Şirket, Yönetim Kurulu, Rekabet Hukuku, Yönetim Kurulu Üyelerinin Sorumluluğu, Ticaret Hukuku, Rekabetin Korunması Hakkında Kanun. Liabilities of the members of board of directors in joint stock company under competition law is analysed in this study. As a rule, the joint stock company operates with the decisions taken by the board of directors. Persons who are members of the board of directors of a joint stock company have certain rights as well as obligations. If the members of the board of directors violate the obligations imposed on them by law, the members of the board of directors shall be subject to civil and criminal liability. The reasons for the legal responsibility of the joint stock company's board of directors and the conditions of the liability are regulated in detail in the Turkish Commercial Code. Although the regulations that may impose sanctions on the board of directors are regulated in the Turkish Commercial Code, there are regulations allowing sanctions to be imposed on the members of the board of directors. One of these regulations is included in The Act On The Protection Of Competition. Article 16 of The Act On The Protection Of Competition includes the regulation that allows sanctions to be applied to both the undertakings or associations of undertakings and the manager or employee of the association of undertakings and undertakings. According to article it is possible to impose an administrative fine on the basis of an agreement, concerted practices and decisions restricting competition, abuse of dominant position or merger or acquisition. According to article 16/3, in case administrative fines mentioned in paragraph three are imposed on undertakings or associations of undertakings, an administrative fine up to five percent of the penalty imposed on the undertaking or association of undertakings shall be imposed on managers or employees of the undertaking or association of undertakings who are found to have a decisive influence in the infringement. In the first part of the study, Competition Law will be discussed in general. In the second part, the conditions of the sanction to be applied to the undertakings and associations of undertakings and the method of enforcement of sanctions in accordance with the third paragraph of Article 16 of the Act On The Protection Of Competition will be examined. In the last part of the study, the conditions of sanction to be applied to the managers and employees of joint stock companies and the procedure of sanction will be examined in detail. Keywords: Joint Stock Company, Board Of Directors, Competition Law, Liabilities Of The Members Of Board Of Directors, Commercial Law, The Act On The Protection Of Competition.
573022
Keywords: Anonim şirketler; Board of directors; Competencia; Competition law; Concorrência; Concurrence; Joint stock company; Members of the board directors; Rekabet hukuku; Responsibility; Sorumluluk; Yönetim kurulu; Yönetim kurulu üyeleri

Anonim şirketlerde önemli miktarda malvarlığı üzerinde işlemler - Songur Hacigüzeller, Damla Gülseren (Ankara Üniversitesi, 2019)
"Anonim şirkette önemli miktarda malvarlığı üzerinde işlemler, anonim şirketin yapısı ve faaliyetlerini ve ayrıca pay sahiplerinin çıkarlarını etkileyen ciddi sonuçlar doğurur. Bu söz konusu işlemler, yabancı hukuk sistemlerinde uzun zamandır pay sahiplerinin korunması amacıyla genel kurulun yetkili olduğu özel usule tabidir. Türk hukukunda 6102 sayılı Türk Ticaret Kanunu öncesinde sadece tasfiye halindeki anonim şirket için düzenlenen genel kurulun bu yetkisi, Yargıtay kararlarında ve öğretide faaliyeti devam eden şirket için de kabul edilmekteydi. Bugün ise Yargıtay içtihatları ve yabancı hukuk sistemlerine uygun olarak önemli miktarda malvarlığı üzerindeki işlemler, faaliyeti devam eden şirketler açısından özel olarak düzenlenerek genel kurulun devredilemez görev ve yetkileri arasında sayılmış ve ayrıca halka açık şirketler için önemli nitelikte işlemlere özgü özel usule tabi kılınmıştır (TTK md. 408/2-f; SPK md. 23/1-b). Ancak Türk Ticaret Kanunu'na Adalet Komisyonu tarafından sonradan eklenen hüküm birçok yönden yoruma ve tartışmaya açıktır. Zira hükmün kapsamı ve uygulama alanı konusunda Türk Ticaret Kanunu bakımından usul ve esaslar yönünden söz konusu olan belirsizlikler, genel kurul ile yönetim kurulu arasında yetki çatışması yaratabileceği gibi, işlemin akıbeti ve dolayısıyla tarafların işlemle bağlılık durumu açısından da sorun doğurabilecek niteliktedir. Öte yandan halka açık şirketler bakımından Sermaye Piyasası mevzuatında önemli nitelikte işlemler için öngörülen usulün de önemli miktarda malvarlığı üzerindeki işlemler özelinde değerlendirilmesi gerekmektedir. Çalışmamızda yoruma ve tartışmaya muhtaç hususlara açıklık getirilmesi amacıyla, önemli miktarda malvarlığı üzerindeki işlemlerin gerçekleştirilmesine ilişkin hukuki bir çerçeve oluşturularak, bu işlemler düzenlenişi, kapsamı, tabi olduğu usul ve nihayet hüküm ve sonuçları yönünden incelenmiştir. From the legal and economic perspective, transactions regarding the substantial amount of assets of a joint stock company have serious consequences on its structure and activities, specifically affecting the interests of shareholders. That's why, in comparative law, within the scope of the protection of shareholders, such transactions are subjected to a special process in which the general assembly plays a crucial role in authorization of the aforementioned transactions. In Turkish law, before the enactment of Turkish Commercial Code nr. 6102, the general assembly had this authorization, but only in the liquidation process of a company. However, in various decisions of the Turkish High Court of Appeal and the legal scholarly work, in accordance with the comparative law, it was pointed out that the general assembly should have this authorization, even if the company is not in a liquidation process. Currently, such transactions of active companies are specifically regulated and are considered among the non-delegable authorizations of the general assembly. In addition, such transactions of publicly-held corporations are subjected to a special process (Art. 408/2-f of TCC; Art. 23/1-b of CML). However, the relevant article added by the Commission of Justice to the Turkish Commercial Code needs to be scrutinized and interpreted. There are many uncertainties regarding rules and procedures within the scope of this provision. This ambiguity might lead to authorization conflicts between the general assembly and the administrative board. Moreover, certain legal problems might arise from these transactions. Last, the special regulation in the Capital Market Law regarding the transactions embodying the substantial amount of assets needs detailed examination. This thesis aims to resolve the ambiguities of the aforementioned provisions and create a special legal basis for the regulations of these types of transactions."
Keywords: Anonim şirketler; Capital companies; Commercial Code; Commercial companies; Commercial law; Joint stock company; Malvarlığı; Multi partnership companies; Property; Sermaye şirketleri; Ticaret Kanunu; Ticaret hukuku; Ticari şirketler; Trade; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Çok ortaklı şirketler

Anonim ortaklıklarda şirket menfaati kavramı - Sulu, Muhammed (Marmara Üniversitesi, 2019)
Anonim ortaklıklarda şirket menfaati kavramı, şirket eksenli çatışan tüm menfaatlerin ortak paydasıdır. Pay sahibi, yönetici, çalışan, tedarikçi, alacaklı ve hatta toplumun menfaatinin sağlanması ile şirketin meşru menfaatinin sağlanması arasında doğru orantı vardır. Bir şemsiye kavram olan şirket menfaatinin sağlandığı durumlarda orta veya uzun vadede diğer grupların da menfaati sağlanmış olur. Bu kavram, şirket hayatının sürdürülebilirliği için en önemli enstrümandır. İlk bakışta soyut bir kavram olarak dikkat çeken şirket menfaati kavramına başta Türk Ticaret Kanunu olmak üzere mevzuatın pek çok yerinde bazen açıkça, bazen de örtülü olarak sıklıkla başvurulduğu gözlemlenmektedir. Çalışmada öncelikle şirket menfaati kavramı tanımlanmış, akabinde ise kavram ile ilgili olduğu düşünülen hukukî düzenlemeler mukayeseli hukuktan da yararlanılarak irdelenmiştir. The concept of company interest in joint-stock companies is the common denominator of all conflicting interests. There is a direct proportion between benefits of the shareholder, the manager, the employee, the supplier, the creditor, and even the community and the legitimate interest of the company. As an umbrella concept, if the company interest is provided, the benefit of other groups is ensured in the medium or long term. This concept is the most important instrument for the sustainability of the company life. The concept of the company interest which draws attention, prima facie, as an abstract concept, is frequently referred in many parts of the legislation especially Turkish Commercial Code both explicitly and implicitly. In the study, firstly the concept of company interest has been defined and then the legal regulations which are thought to be related to the concept have been examined by using comparative law.
536594
Keywords: Anonim şirketler; Commercial partnership; Common interest; Interest; Joint stock company; Menfaat; Ortak menfaat; Ticari ortaklık; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

L'image fidèle dans les sociétés commerciales de la République Démocratique du Congo : Vérifications empiriques au regard du système comptable OHADA - Halimana Hangi, Bernard (Université Protestante au Congo, 2018)
Le mobile de notre recherche est d’analyser les facteurs ou pesanteurs qui ont empêché les dirigeants sociaux et les professionnels du chiffre (directeurs administratifs et financiers, chefs comptables et comptables, auditeurs et contrôleurs de gestion, experts comptables et commissaires aux comptes)à produire, voire à certifier des états financiers de synthèse qui reflètent l’image fidèle des sociétés commerciales de la RD Congo. L’étude s’est effectuée au cours de deux premières années de mise en application du Système comptable de l’OHADA (SYSCOHADA), soit 2014 pour les comptes personnels et 2015 pour les comptes consolidés et les comptes combinés. Nous avons fait un tour rétrospectif sur l’exercice social 2013 ainsi qu’un regard projectif sur l’exercice 2016, dans le cadre de vérifications empiriques à ce sujet. En grosso modo, nos analyses se sont appuyées sur les données comptables et fiscales de 4 exercices sociaux (2013 à 2016). La toile de fond de notre étude était de savoir pourquoi les états financiers n’ont pas donné l’image fidèle du patrimoine, du résultat et de la situation financière. Cette notion d’image fidèle est consacrée par les articles 2 à 11 de l’Acte uniforme portant organisation et harmonisation des comptabilités des entreprises (AUOHCE), tel que révisé par l’Acte uniforme relatif au droit comptable et à l’information financière (AUDCIF) du 26 janvier 2017 ainsi que les articles 137 à 141 de l’Acte uniforme relatif aux Sociétés commerciales et au Groupement d’intérêt économique (AUSCGIÉ) ; à condition que les états financiers soient établis et présentés conformément aux dispositions des articles 25 à 34 de l’AUDCIF susvisé. Notre analyse est partie des vérifications empiriques sur les informations financières et fiscales de 173 sociétés commerciales et des réponses de 357 dirigeants sociaux des sociétés commerciales et des professionnels du chiffre qui ont répondu à notre questionnaire d’enquête. Les résultats de cette enquête, tout comme ceux des vérifications empiriques ont été recoupés et confirmés à partir de l’entretien semi-directif avec 38 informants qui ont vécu la transition du Plan Comptable Général Congolais (PCGC) vers le SYSCOHADA. De nos analyses, il a été démontré que les états financiers et d’autres documents comptables et de gestion courante des sociétés commerciales de la RD Congo n’ont pas reflété l’image fidèle des patrimoines, des résultats et des situations financières. Pour cause, il a été révélé que les dirigeants sociaux ainsi que les professionnels du chiffre ont établi et/ou certifié des informations financières influencées par des facteurs et pesanteurs politico-contractuels, conventionnels et socio-institutionnels. Ainsi, nous avons suggéré, qu’au-delà du formalisme mettant en relation les éléments de principaux états financiers (Bilan, Compte de résultat et Tableau des flux de trésorerie), il faille instaurer des mécanismes de durcissement de la réglementation comptable par un contrôle du niveau d’application du SYSCOHADA. Ce contrôle doit partir de l’examen des postes du Bilan à celui des soldes intermédiaires de gestion du Compte de résultat pour arriver à tirer les conséquences de la vérification de la comptabilité produite par les gestionnaires (dirigeants sociaux) et/ou certifiée par les professionnels du chiffre (consultants, auditeurs et commissaires aux comptes). Tous ces acteurs devront être invités au respect du Code d’éthique et de la Clause de conscience.
Keywords: AUDCIF; AUOHCE; AUSCGIE; Plan Comptable Général; SYSCOHADA

L'efficacité des sûretés réelles conventionnelles dans les financements d'acquisitions à effet de levier - Chenu, Stanislas (Université de Nantes, 2018)
L’efficacité des sûretés réelles dans les financements d’acquisitions à effet de levier est essentielle pour permettre au créancier d’atténuer son risque de crédit tout en permettant à l’emprunteur d’optimiser ses conditions de financement. Les sûretés réelles qui composent le security package doivent être faciles à mettre en place, peu coûteuses et respectueuses des intérêts du constituant tout en garantissant au créancier l’obtention effective de son dû en cas de réalisation. Nous tenterons dans un premier temps de dégager les techniques juridiques qui peuvent être mises en place par les praticiens pour s’assurer de l’efficacité des sûretés réelles données en garantie d’un financement d’acquisition à effet de levier. Et dans un deuxième temps, après avoir démontré que notre droit des sûretés réelles en France et en Europe n’est pas suffisamment adapté aux réalités pratiques et économiques, nous essayerons de faire des propositions de réforme en droit français mais également en droit européen. The efficiency of security rights granted in the context of leverage buy-out acquisition is essential to enable a creditor to mitigate its credit risk while allowing the borrower to optimize its financing conditions. The security interests which compose the security package must not only be easy to implement, inexpensive and not too restrictive for the pledgor but also efficient for the creditor in case of enforcement. We will attempt first to identify the legal techniques that can be implemented by legal advisors in order to ensure the effectiveness of the security rights granted in the context of a leverage buy-out acquisition. Then, after having demonstrated that our law on security interests in France and in Europe is not well adapted to practical and economic realities, we will try to propose legal reforms under both French law and European law.
Keywords: Crédit – Droit; Débiteur et créancier; Finances; Security package; Sûretés

L'intérêt de la personne morale - Bignebat, Paul (Université Paris-Dauphine, 2018)
En droit, de nombreuses notions se réfèrent à un intérêt. L'intérêt est « ce qui importe ». Ainsi entendu, l’intérêt renvoie à une valeur subjective, qui varie donc d’un individu ou d’un groupe d’individus à un autre. L’objet de la thèse est d’identifier les éléments qui permettent de caractériser l’intérêt de la personne morale.Chaque personne morale a un intérêt que l'on peut qualifier de « personnel », qu'elle relève du droit public ou du droit privé. Cet intérêt est individuel, propre à chaque personne morale, et sa substance est liée à la finalité de cette personne. Cette notion générale peut être précisée à partir de l’étude d’un intérêt personnel particulier : l’intérêt de la société. Par analogie, on peut considérer que la notion d’intérêt personnel permet la protection de la personne morale le temps nécessaire à la réalisation de sa finalité.En raison de l’importance du phénomène de l’organisation en groupe, l’analyse de l’intérêt personnel ne peut se limiter à la situation des personnes morales isolées. Il ressort de l’étude des principes généraux applicables aux groupes et de la jurisprudence que l’intérêt personnel résiste et s’adapte à l’organisation groupée des personnes morales. Néanmoins, l’existence d’un groupe a une incidence sur l’intérêt des personnes morales qui le compose. Cette incidence est parfois désignée par référence à l’intérêt du groupe. Or, cette référence ne correspond à aucune réalité en droit positif. L’incidence du groupe sur l’intérêt personnel doit plutôt être cherchée dans les relations entre intérêts au sein du groupe.
Keywords: Company's best interest; Conflict of interests; Conflit d'intérêts; Conflits d'intérêts; Corporate governance; Gouvernement d'entreprise; Group; Groupe; Intérêt social; Legal person; Personne morale; Personnes morales

La démocratie actionnariale : contribution à l'étude d'un mythe juridique - Crocquevieille, Mathieu (Université Paris 10, 2018)
Slogan ou oxymore pour les uns, prix convoité ou formule vertueuse pour les autres, l’expression de démocratie actionnariale est présente dans les discours relatifs aux entreprises depuis les années 2000. l’étude ici présente s’intéresse à cette expression dans le cadre des discours juridiques portant sur les sociétés par actions. pour ce faire, la démocratie actionnariale a été considérée comme un mythe juridique, c’est-à-dire une représentation à la fois littéraire, politique et historique dans un contexte juridique. le mythe de la démocratie actionnariale incarne et véhicule une dynamique : celle de la rencontre entre la dimension démocratique et la dimension actionnariale. l’histoire et les sciences de gestion ont été parfois sollicitées pour le dévoiler dans son ensemble. le mythe de la démocratie actionnariale apparaît à la fois fondateur et structurant. fondateur, il accompagne les sources, les origines de la législation sur les sociétés par actions. dans sa forme traditionnelle, il est apparu au dix-neuvième siècle. il procède alors d’un rapport analogique assimilant sociétés par actions à une miniature politique. la société est une version réduite de la démocratie. dans sa forme moderne, il est né au vingtième siècle et rend compte de l’encastrement progressif des valeurs démocratiques de la communauté civique dans les sociétés par actions par le biais des mouvements rse. structurant, il participe à la pratique de ce type de société. autour de l’actionnaire, il nourrit ses droits politiques mais peine à rendre compte des droits financiers. autour des dirigeants, il s’associe à d’autres représentations pour en encadrer les pouvoirs.
Keywords: Actionnaires; Capitalism; Capitalisme; Companies; Democracy; Directors; Dirigeants; Démocratie; Gouvernance; Governance; Langage juridique; Shareholders; Sociétés

L’évaluation comptable et financière de la capacité à entreprendre du dirigeant de PME : enjeux, modalités et proposition d'un modèle - Lopez, Jean-Claude (Université de Reims Champagne-Ardenne, 2018)
Nous proposons, à l’aide d’une approche pluridisciplinaire, de mieux rendre compte des compétences entrepreneuriales d’un dirigeant de PME, de jeter les bases d’un modèle d’évaluation de la capacité à entreprendre à partir de l’analyse des cycles d’exploitation. Ce modèle sera construit sur les bases d’une enquête exploratoire, puis testé au sein d’une PME de négoce afin d’en vérifier la pertinence et d’en améliorer l’applicabilité.Une estimation pertinente de la capacité à entreprendre pourrait rendre possible une meilleure évaluation de la valeur ajoutée des dirigeants de PME et une esquisse plus précise de la stratégie de soutien aux actions entrepreneuriales. Evaluer la capacité à entreprendre est tout autant un défi pour la communauté financière et comptable que l’est l’évaluation du capital humain. La présente propose une nouvelle approche pour mieux aborder la "vraie" valeur d’une entreprise, avec l’espoir que notre modèle sera utile aux parties prenantes de l’entrepreneuriat. We suggest, by means of a multidisciplinary approach, reporting better entrepreneurial skills of a leader of SME, to lay the foundations for a model of evaluation of the capacity to be undertaken from the analysis of the cycles of exploitation. This model will be built on the bases of an exploratory investigation, then tested within a trade SME to verify the relevance and improve the applicability.A relevant estimation of the capacity to be undertaken could make possible a better evaluation of the added value of the leaders of SME and a more precise sketch of the strategy of support for the entrepreneurial actions To estimate the capacity to be undertaken is just as much a challenge for the financial and accounting community than is it the evaluation of the human resources. The present proposes a new approach to approach better the ''real'' value of a company, with the hope than our model will be useful for the stakeholders of the entrepreneurship.
Keywords: Accounting; Aptitude pour la direction; Capital humain; Capital humain specifique; Chefs d'entreprise (évaluation); Comptabilite; Entrepreunariat; Human resources; Specific human capital

La délégation de pouvoirs dans les sociétés commerciales de droit OHADA - Diène, Oumy (Université de Bordeaux ; Université Cheikh Anta Diop, 2018)
C’est avec une ambition modeste que la délégation de pouvoirs est admise dans les sociétés commerciales de droit OHADA. La société anonyme en est la structure d’accueil. Les u travailorganes sociaux en sont les acteurs. Elle est mise en œuvre pour faire face une urgence due à l’empêchement du président ou pour asseoir la rapidité d’une action relative à une opération financière. Or, étant aujourd’hui reconnue comme technique de bonne gouvernance, la délégation de pouvoirs pour remplir une telle fonction en droit OHADA, est à généraliser. Tout dirigeant social doit avoir la liberté d’y recourir et les salariés, plus proches des réalités du terrain, doivent y être associés. Une telle appréhension de la délégation de pouvoirs appelle la conception d’un régime juridique précis qui garantit son jeu loyal. It is with the modest ambition that the delegation of power is admitted in the trading companies of OHADA law. The limited company is the reception center and social organs are the actors. It is implemented to face an urgency due to the hindrance of the president or to establish the speed of a financial transaction. Yet, being now acknowledged as a good governance practice, the delegation of power should be generalized to satisfy such a function in OHADA law. Every social leader has to have the freedom to use it and employees, closer to realities of the ground, must be associated there. Such an apprehension of the delegation of power calls the conception of a precise legal regime which guarantees its loyal play.
Keywords: Bonne gouvernance; Delegation of power; Droit des sociétés commerciales; Délégation de pouvoirs; Délégation des pouvoirs; Employees; Good governance; Gouvernement d'entreprise; Organes sociaux; Salariés; Socials organs; Trading companies

O poder da informação e o dano informacional nas companhias abertas - Vergueiro, Carlos Eduardo (Universidade de São Paulo, 2018)
Esta Tese aborda os temas do poder da informação, da fraude informacional e do dano informacional dela decorrente. O estudo parte da premissa de que houve opção, no Direito Comparado, pelo regime da divulgação de informações (disclosure) como mecanismo principal da estratégia regulatória do mercado de valores mobiliários. Essa opção, por exemplo, substitui um juízo de mérito que poderia existir sobre viabilidade de ofertas de valores mobiliários que fosse atribuído ao órgão regulador do mercado. Pela escolha feita, o Direito obriga a divulgação de informações para permitir que investidores do mercado de valores mobiliários tenham condições de precificar os valores mobiliários em negociação. Ou que investidores que não possuem as habilidades para tanto sejam beneficiados pela precificação feita por outros mais habilitados. A partir dessa premissa, chega-se, em primeiro lugar, ao que a Tese denominou de poder da informação, para se analisar um aspecto inerente à posição de controladores, pela maioria do capital ou pelo controle gerencial, que faz com algumas pessoas que estão na posse de informações divulgadas e não divulgadas ao mercado sobre a situação da companhia sejam obrigadas a divulga-las. A palavra poder foi escolhida porque significa tanto uma posição de prevalência sobre outros, quanto para indicar os deveres que uma posição de prevalência sobre outros traz aos detentores dessa posição. A simples obrigação de divulgar não poderia ser a única regra para permitir que a divulgação ocorra e seja baseada em caracteres verídicos. Informação omitida e informação divulgada com fraude causam danos ao detentor do valor mobiliário, que toma decisões de compra e venda com base nas informações, e ao próprio mercado de valores mobiliários, cuja integridade, como um todo, é fragilizada a partir de uma situação de dano. O dano não é, portanto, unicamente privado. Fraude informacional é uma expressão escolhida por esta Tese para se referir tanto à situação de omissão de divulgação de informação necessária de ser divulgada, quanto à divulgação de informação errada ou incompleta, todas elas contribuindo para que o mercado esteja municiado de informações que não permitem a correta identificação da situação do emissor. A fraude informacional traz o dano informacional, outra expressão escolhida pela Tese para significar o dano que decorre da situação de fraude informacional. Ao redor do mundo, a repressão à fraude informacional foi regida por leis com sanções fortes e com aspectos de Direito Civil (a reparação civil), penal (a imposição de pena para seus praticantes) e administrativa (pelo órgão regulador do mercado de valores mobiliários). A harmonia e tratamento único do tema são medidas necessárias para o incremento das regras de combate à fraude informacional, que funcionam (ou deveriam funcionar) tanto quanto regras de responsabilização como quanto elementos de dissuasão do potencial praticante de fraude informacional. O avanço da ciência pretendido pela Tese, especialmente focado na inovação da Ciência Jurídica para os temas objeto de estudo pela Tese, está representado por sugestões de melhoria no Direito brasileiro em tema de combate à fraude e dano informacionais, especialmente se valendo de elementos exemplificativos do Direito comparado. This Thesis analyses the topics of the power of information, informational fraud and informational damages arising from it. The research is based on the option for having the disclosure, as made by Comparative Law, as the main regulatory scheme as applicable to securities markets. This option, for example, substitutes a merit based approach over securities public offerings that could exist as function of a securities markets regulator. Based on the choice made, Law mandates the disclosure of information so that securities markets' investors have ways to price securities and non skilled investors benefit from prices set by skilled ones. Having such ideas as start, this Thesis first analyzes what it called as information power which in turns analyzes corporate controllers' position (whether from the holding of a majority of voting stock or as a result of a managerial control) and the holding of information that they have due to their position, with the mandatory disclosure system that mandates disclosure to be made. The word "power" has been chosen to indicate both the prevailing position of corporate controllers and the duties that arise as a consequence of being in such position. The simple mandatory disclosure rule could not be the sole rule to allow that disclosure dully happens and be based on true information. Omitted information and frauded information cause damages to both securities holders, who trade based on the information, and to the market as a whole, whose integrity is affected by such frauded information. Damages are not solely private and related to the person who suffered them directly. Therefore, punitive rules shall exist. Informational fraud is another expression that has been chosen by this Thesis to refer to both the situation when information that should be disclosed is omitted and to the situation where information disclosed is partially or totally wrong, all of them making market not informed with information that could allow it to dully price securities. Informational damages arise as a consequence of informational fraud. Around the world, informational fraud has been fought with strong sanctions and with Criminal Law, Torts (the damaged person reimbursement), and Administrative (through administrative sanctions imposed by securities regulators) rules. Harmony among all fields is required to the advancement of fight against informational fraud as it is required to have rules to promote deterrence against wrong makers in potential. The Law development that is seek as contribution for the innovation of Legal Sciences by this Thesis are the recommendations that it does for changes in the Brazilian Law based on the Comparative Law.
Keywords: Civil liability; Corporate control; Dano informacional; Disclosure; Divulgação de informações (disclosure); Efficient capital markets; Fraude informacional; Hipótese do mercado de capitais eficiente; Informational damages; Informational fraud; Informational power; Mercado de valores mobiliários; Poder da informação; Poder de controle; Public companies; Responsabilidade civil; Securities markets

A critical analysis of the removal of directors by the board of directors and the judiciary under the Companies Act 71 of 2008 - Cassim, Rehana (University of South Africa, 2018)
Section 71(3) of the Companies Act 71 of 2008 has introduced into South African company law a provision which for the first time permits the board of directors to remove another director from office in certain specific instances. A further significant innovation in the Companies Act 71 of 2008 is contained in section 162, which empowers a court to make an order declaring a director delinquent or placing him under probation in specific instances. The effect of section 162 is that a court is empowered to remove a director from the board of directors. The focus of this thesis is the removal of directors from office by the board of directors and by the judiciary. The thesis explores the underpinning philosophy of the statutory provisions relating to the removal of directors from office. It also examines the impact of the power given to the board of directors and to the courts to remove a director from office. The grounds and the procedures for the removal of directors by the board of directors and the judiciary are examined. The fiduciary duties applicable to directors in removing a director from the board of directors are also explored. In addition, this thesis examines the removal of directors holding multiple positions or capacities in relation to a company, such as an employee or a shareholder with loaded voting rights. The remedies which may be relied on by a director who has been removed from office by the board of directors are examined. Recommendations are made to strengthen and improve the provisions in the Companies Act 71 of 2008 relating to the removal of directors from office by the board of directors and the judiciary. Amendments to the Companies Act 71 of 2008 are suggested to remove ambiguities; to guard against the abuse of sections 71(3) and 162; to improve the grounds and procedures for the removal of directors by the board of directors and the judiciary, and to enhance the remedies that may be relied on by a director who has been removed from office by the board of directors.
Keywords: Corporate governance; Directors and shareholders power; Directors of corporations; Fiduciary duties; Investor relations; Removal of directors from office; Stockholders' voting; Voting rights

İmtiyazlı pay sahipleri özel kurulu - Aktaş, Betül (Galatasaray Üniversitesi, 2018)
Doktora tez konumuz olan imtiyazlı pay sahipleri özel kurulunun temel işlevi imtiyazların korunmasıdır. Bu doğrultuda, imtiyazlı pay sahiplerinin haklarını ihlal edebilecek nitelikte olan genel kurulun anasözleşme değişikliklerinde, yönetim kuruluna sermaye artırımı yetkisi verilmesi kararında ve kayıtlı sermaye sisteminde yönetim kurulunun yaptığı sermaye artırımında özel kurul onayı alınması gerekmektedir. Aksi takdirde alınan genel kurul veya yönetim kurulu kararı uygulanamaz. Özel kurul toplantısının yapılabilmesi bakımından aranan temel şartlardan biri, imtiyazlı pay sahiplerinin haklarını ihlal edebilecek nitelikte bir anasözleşme değişikliği veya yönetim kurulunun sermaye artırımı kararının alınmasıdır. Özel kurul kararının alınmadığı aşamada genel kurul kararı hukuken geçerli, fakat hukuki sonuçlarını doğurması özel kurul onayının varlığına bağlıdır. The basic function of the special committee of preference shareholders is to protect the preferences. In this respect, Art. 454 of the Turkish Commercial Code (TCC) regulates the approval of special committee for the amendments to the articles of association of the general assembly, which are in the nature of violating the rights of the preferred shareholders, authorization for capital increase for the board of directors and the capital increase in the registered capital system. Otherwise, the decision of the general assembly or board of directors cannot be applied. One of the basic conditions sought in order to be able to hold the special board meeting is to adopt an amendment in the articles of association or the capital increase decision of the board of directors. At the stage where the decision of the special board is not taken, the decision of the general assembly is legally valid but its legal consequences are subject to the approval of the special committee.
Keywords: Anonim şirketler; Commercial law; Joint stock company; Pay sahipleri; Privileged share; Shareholders; Special meeting; Ticaret hukuku; Turkish Commercial Code; Türk Ticaret Kanunu; Özel kurul; İmtiyazlı pay

Anonim ortaklıklar hukukunda özel denetim - Günay, Gözde Engin (Galatasaray Üniversitesi, 2018)
Anonim şirketlerde pay ve oy çoğunluğunu elinde bulunduranlar bir araya geldikleri zaman, hâkimiyeti elinde bulundurdukları için şirket yönetimini etkileyecek kararları alarak, kendi kararları doğrultusunda şirketi yönlendirebilirler. Çoğunluğu elinde tutanların gücü karşısında azlık ve münferit pay sahiplerinin korunması, onlara bazı bireysel haklar tanınması ile sağlanmaya çalışılmıştır. Çalışmamızın konusu Anonim Ortaklıklar Hukuku'nda Özel Denetim'dir. TTK'nin "pay sahibinin kişisel haklarıˮ ana başlığı ve V. numaralı özel denetim isteme hakkı alt başlığı altında TTK m.438 ve 444' da düzenlenen özel denetim isteme hakkı, anonim ortaklıkta önemli bir bireysel ortaklık ve azlık haklarından birisini oluşturmaktadır. Aydınlatıcı haklar olarak adlandırılan bilgi alma ve inceleme hakkı ile özel denetim isteme hakları; şirketin faaliyetleri, işlemleri, ekonomik durumu hakkında yeterli bilgiye sahip olmayan pay sahiplerinin, bu haklarını kullanarak daha bilinçli olmalarını sağlarlar. Bu iki hak, hem önleyici hem de telafi edici niteliktedir. According to Article 438, CO Art.697a, any shareholder may introduce a motion at the general meeting of shareholders calling for certain facts to be subject to a special examination by a special and independent searcher. The special examination has to be necessary for the exercising of the shareholders' rights. If the shareholders' meeting approves the motion, the judge (called upon by the Company or by shareholder) appoints the special searcher. If the general meeting does not approve the motion calling for the appointment of the appointment of the special searcher, shareholders who represent at least ten percent of the share capital or who represent shares with par value of one million Turkish Lira may request the judge to appoint a special searcher. The shareholders are legally entitled to the appointment of a special searcher if they credibly establish that corporate bodies have violated the law or the articles of incorporation and have thereby damaged company or shareholders. Special examination has a pre-condition for requesting, as per article TTK m.438, in order for a shareholder to request a special examination, that shareholder or any shareholder of the company should have duly consumed its right to information and examination. This is pre- condition for requesting the special examination
635031
Keywords: Anonim ortaklıklar; Anonim şirketler; Control; Denetim; Incorporated companies; Joint stock company; Private auditor; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Özel denetçi

La mobilité des sociétés de l’espace OHADA : étude à la lumière du droit européen et international des sociétés. - Sane, Claude MIchel (Université de Pau et des Pays de l'Adour, 2017)
À coté de l’objectif immédiat d’uniformiser les législations des États membres, l’OHADA s’est fixée un objectif médiat, celui de créer un vaste marché sans frontière. Or au regard des difficultés pour les sociétés commerciales de déplacer leurs sièges sociaux d’un État membre à un autre, nous ne pouvons que constater que l’existence de ce marché intégré n’est pas encore une réalité pour elles. Il apparaît alors que la seule uniformisation du droit des sociétés commerciales par l’OHADA ne suffit pas à leur permettre de réaliser des opérations de restructuration transfrontalière. Cette thèse a ainsi montré que l’OHADA a besoin d’évoluer et de se transformer pour mettre en place un véritable droit à la mobilité pour les sociétés commerciales au sein son espace communautaire. Elle doit pour cela compléter son intégration juridique par une intégration économique consacrant un libre établissement dont les opérations de mobilité seraient des modalités d’exercice, comme l’a fait l’Union européenne. Ce droit à la mobilité ne devra toutefois pas s’exercer de manière abusive. L’OHADA devra donc trouver un équilibre entre une mobilité fluidifiée et une protection efficace des actionnaires, salariés et tiers. De même il conviendra de rechercher un équilibre dans la gestion de la coexistence des normes communautaires qui ne manquera pas de se présenter dans le régime des opérations de mobilité puisqu’il s’agit d’un problème récurrent dans l’espace OHADA. Apart from the direct objective of the Organization for the Harmonization of Business Law in Africa (OHADA) to standardize the law, its indirect objective relates to the creation of a large common market. However, regarding the difficulties for companies to transfer their registered office from one member state to another, we can see that the existence of such market is still not a reality for them. Therefore, it appears that the only standardizing of the corporate law by OHADA is not sufficient to allow them to perform their cross-border mergers. This research shows thus that OHADA needs to change and to transform itself to put in place a real right to mobility in the community area for the companies. Like the European Union, it should complete the legal integration by an economic integration setting up a freedom of establishment, including border restructuring operations. But this right to mobility should not be abused. OHADA will have to find a balance between facilitating the mobility and protecting efficiently minority shareholders, employees and third parties rights. Similarly a balance must be struck to solve the conflict of community norms in the restructuring operations legal regime, since it is a recurrent problem for OHADA space.
Keywords: Border reorganization; Border transfer of registered office; Companies freedom of establishment; Conflict of community norms; Conflit de normes communautaires; Corporate law; Cross-border mergers; Droit commercial (droit international); Droit communautaire africain; Droit communautaire européen; Droit des sociétés; Droit européen; Droit international des sociétés; Droit international privé (droit européen); Economic integration; European and African community law; Fusion transfrontalière; International corporate law; Intégration juridique; Intégration économique; Legal integration; Libre établissement des sociétés; Nationality of companies; Nationalité des sociétés; Organisation pour l’harmonisation en Afrique du droit des affaires; Organization for the Harmonization of Business Law in Africa (OHADA); Restructuration transfrontalière; Sociétés; Transfert transfrontalier de siège social

La protection des associés et des créanciers dans les opérations de fusion et d’apport partiel d'actif des sociétés commerciales en droit français et en droit OHADA - Wagou Leumega, Marie Pamela (Université de Lorraine, 2017)
La fusion et l’apport partiel d’actif soumis au régime des scissions sont des opérations fréquentes tant en France que dans les pays membres de l’OHADA. Elles présentent des risques multiples pour les actionnaires et les créanciers et cette thèse s'attache justement à étudier la protection qui s'offre à ces catégories. Cette étude fait apparaître que leur protection est assurée par trois éléments essentiels dans les deux ordres juridiques : l'information, la consultation et le principe de la transmission universelle du patrimoine. Nos analyses révèlent cependant que ces protections sont insuffisantes car elles ne sont pas mises en œuvre de manière optimale et sont fortement limitées par la jurisprudence. Aussi pour améliorer le système actuel, des solutions législatives et contractuelles sont nécessaires pour garantir au mieux la protection des actionnaires et des créanciers. La voie législative permet de renforcer l’efficacité d’un droit, comme par exemple la reconnaissance du droit de retrait aux actionnaires. Quant à la contractualisation, elle permet de renforcer la protection de base instituée par les textes, ainsi que l’illustre la clause de survie de l’obligation de couverture ou de la garantie autonome. The merger and the partial contribution of assets subjected to the regime of splits are frequent operations both in France and in the member countries of the OHADA. They present multiple risks for shareholders and creditors, and this thesis focuses on the protection afforded to these categories. This study shows that their protection is ensured by three essential elements in the two legal orders: information, consultation and the principle of the universal transmission of the heritage. However, our analyzes reveal that these protections are insufficient because they are not implemented optimally and are strongly limited by case law. To improve the current system, legal and contractual solutions are needed to ensure the best protection of shareholders and creditors. The legislative way makes it possible to reinforce the effectiveness of a right, as for example the recognition of the right of withdrawal to the shareholders. As for the contractualization, it makes it possible to reinforce the basic protection instituted by the texts, as the survival clause of the obligation of cover or of the autonomous guarantee illustrates it.
Keywords: Apport partiel d’actif; Associates; Associés; Creditors; Créanciers; Droit commercial; Fusion; Fusion d'entreprises; Merger; Partial asset contribution

L’action civile de l’associé en droit pénal des sociétés - Martinelle, Mathieu (Université de Lorraine, 2017)
La victime en col blanc est mésestimée, tant par l’opinion publique que par le droit. Si les infractions en matière économique, financière et boursière heurtent, les personnes lésées par ces agissements bénéficient peu de l’empathie traditionnellement accordée aux victimes pénales. Parmi elles, il en est cependant une qui mérite une attention particulière : l’associé. Alors qu’une personne sur trois dispose en France de cette qualité, l’associé est susceptible d’être une victime du fait de son engagement. Acteur social majeur, il peut subir les effets d’une infraction au droit pénal des sociétés. Lorsqu’il est la victime d’une telle infraction, l’associé a vocation à exercer une action civile. Action en réparation appartenant à tous ceux ayant subi un dommage directement causé par l’infraction, celle-ci est toutefois réservée aux seuls associés titulaires du bien juridique protégé par l’incrimination chef des poursuites. Alors que le droit d’agir en action civile de l’associé est ainsi limité, le bien-fondé de la demande en réparation de son préjudice est également soumis à des conditions interprétées à l’aune de théories singulières. Le brouillard dans lequel se situe aujourd’hui l’associé victime d’une infraction au droit pénal des sociétés est dense. Il nous revient de l’en sortir en proposant des évolutions conformes au droit et répondant à la situation réelle de cette victime pénale jusque-là oubliée.
Keywords: Action civile; Associé; Bearer of the protected legal interest; Bien-fondé; Business criminal law; Civil proceedings; Compensation; Corporate law; Dommages-intérêts; Droit de la réparation; Droit des sociétés; Droit d’agir; Droit pénal des sociétés; Indemnisation; Partner; Poursuites judiciaires; Préjudices réparables; Repairable injuries; Right of action; Right to compensation; Titulaire du bien juridique; Validity

Le contrôle de la gestion des sociétés commerciales : approche systémique - Nicolas-Belizon, Delphine (Aix-Marseille Université, 2017)
Les sociétés commerciales sont un des piliers de l’économie française. Génératrices de richesses, il est important d’assurer leur bon fonctionnement. Selon la tradition française, les dirigeants sociaux sont seuls maîtres aux commandes de la gestion et disposent à cette fin des pleins pouvoirs. Si cette hégémonie est un gage de performance et de dynamisme économique, cette prévalence des dirigeants est aussi porteuse de risques. La bonne santé des sociétés et leur pérennité sont directement influencées par les agissements des dirigeants. Le besoin de contrôler la gestion de ces derniers n’est donc plus à démontrer. En revanche, la question de la réalité du contrôle se pose aujourd’hui. L’étude du contrôle des sociétés commerciales conduit à poser la théorie selon laquelle le droit a érigé un véritable système. En effet, le droit des sociétés appréhende la question du contrôle dans sa globalité. A ce titre, un contrôle conventionnel complète un contrôle légal relativement perfectionné. Pour cause, au-delà des instruments juridiques à disposition des contre-pouvoirs, les conditions du contrôle et ses conséquences sont également prises en compte par le législateur. D’ailleurs, l’imbrication entre ces différents éléments confirme l’intérêt d’une approche systématique du contrôle des sociétés commerciales. L’attention du législateur portée à ce système depuis plusieurs décennies le rend aujourd’hui pour le moins efficace. Si certaines réserves demeurent, le droit des sociétés permet un contrôle satisfaisant de la gestion des dirigeants. Commercial companies are one of key players of the French economy. Wealth generating, it is important to ensure their smooth operation. According to french habits, social leaders are the only masters in charge of management and have full powers. While this dominance is a success’ key factor and ensures economic dynamism, this omnipotence may carry potential risks. Good health and sustainability of companies depend directly on leaders’ decisions. Unnecessary to demonstrate it, we need to monitor their management. In return, reality of monitoring could also be asked today. The study of commercial companies’ monitoring requires to analyze legal basis which arises this system. Indeed, business law is based on overall control. For this reason, a conventional audit completes a rather sophisticated legal audit. As a result, beyond legal instruments in the hands of opposition, monitoring conditions and its consequences are also taken into account by the legislator. Besides, the imbrication of these different points confirms the interest of a systematic approach to check commercial companies. The legislator's attention to this particular system has proved to be effective since many years. Even if certain reservations remain, business law gives satisfaction regarding top management monitoring.
Keywords: Audit; Contrôle de gestion; Corporate law; Droit des sociétés; Droit des sociétés commerciales; France

L'agrément en droit des sociétés : contribution à une simplification du droit - Le Ruyet, Armel (Université de Rennes 1, 2017)
L’étude de l’agrément en droit des sociétés révèle que les règles l’encadrant ne sont pas exemptes de lacunes ou d’incohérences. Ces dernières résultent notamment de leur édiction dispersée, dans des textes légaux ou réglementaires, au cas par cas, individuellement pour chaque forme sociale. En outre, leur intelligibilité est amoindrie par la corrélation parfois faite par la loi entre les règles de son domaine et ses formalités procédurales. De cet ensemble découle une certaine complexité, incompatible avec le besoin de sécurité juridique requise pour exécuter toute procédure. En l’occurrence, l’atteinte à la liberté ne réside plus dans l’absence de forme protectrice mais, paradoxalement, dans un formalisme trop pointilleux, dont l’application suscite un important contentieux. Néanmoins, le constat de la présence éventuelle de l’intuitu personae dans l’ensemble des sociétés suggère la possibilité d’unifier le domaine de l’agrément et, corrélativement, de simplifier sa mise en œuvre, grâce à l’élaboration d’un droit commun. À cette fin, une conception contractuelle des rapports sociaux donne de nombreuses clés de résolution des problèmes posés actuellement par son régime. Cette analyse faite du droit positif ne remet pas pour autant en cause le juste équilibre établi par la loi au nom de l’ordre public sociétaire. Celui-ci s’exprime par l’exigence du respect de formalités et d’obligations visant à protéger tant la société que son associé cédant. Au contraire même, ce point de vue permet de dégager les champs d’intervention réservés au législateur ne portant atteinte ni à la substance des droits de l’associé, ni aux concepts juridiques de droit commun. Cette méthode de traitement des difficultés soulevées aboutit à une reconstruction de la législation de l’agrément, davantage intelligible, augurant par là-même, une perspective concrète de création d’un droit français des sociétés fermées.
Keywords: Associates; Associés; Autorisations; Cession de contrat; Common interest; Conflict of interest; Conflit d’intérêts; Contract-Organization; Contrat de société; Contrat-Organisation; Corporate law; Droit des sociétés; Décision sociale; Formalism; Formalisme; France; Intuitu personae; Intérêt commun; Ordre public sociétaire; Partnership agreement; Private companies; Procedure; Procédure; Public corporation order; Simplification; Social decision; Sociétés fermées; Transfer of contract; Transfers of social rights; Transferts de droits sociaux

Etude critique des modes de cession applicables au fonds de commerce dans le cadre de la réalisation des actifs en liquidation judiciaire - Bourdais, Matthieu (Université Lille 2, 2017)
Depuis la réforme du droit des procédures collectives par la loi de sauvegarde des entreprises du 26 juillet 2005, deux régimes de cession aux conséquences juridiques dissemblables restent applicables lors des réalisations d’actifs en liquidation judiciaire. Le fonds de commerce, bien particulier à la définition lacunaire, présente la particularité d’être éligible tant à l’application du régime de la cession d’entreprise des articles L 642-1 et suivants du Code de Commerce, qu’à celle de la cession de biens isolés de l’article L 642-19 du Code de Commerce. Les éléments guidant la répartition des ensembles cédés sous l’un ou l’autre régime restent cependant à ce jour imprécis, compromettant la sécurité juridique des différents acteurs de la procédure. Suite à l’étude des causes théoriques et pratiques de cette confusion, des propositions de réforme de ces régimes peuvent être formulées afin d’offrir aux intervenants à la procédure, qu’ils soient parties à la cession, créanciers, ou salariés, une meilleure lisibilité de leurs droits et obligations = Since the reform of the collective procedures by the July 26, 2005 Companies backup Act, two regimes of sales, of dissimilar legal consequences, can be applied during the divestments of the assets that takes place in the final stages of the judicial liquidation. The goodwill, specific asset of lacunar definition, has the particularity to be eligible both for the application of the system of transfer of companies mentionned at the article L 642-1, to that of isolated assets divestment regime mentionned at the article article L 642-19 of the French Commercial Code. Elements guiding the distribution of sets sold under one or the other regime remain however to this day unclear, compromising the legal security of the different actors in the process. Following the study of the theory and practice of this confusion causes, proposals for reform of these regimes can be formulated to provide to the participants in the proceedings, may they be parties to the sales, creditors or employees, a better readability of their rights and obligations
Keywords: Cession de biens isolés; Cession de l’entreprise; Company; Company transfer regime; Entreprise; Entreprises (disparition); Fonds de commerce; Fonds de commerce - France; France; Goodwill; Isolated assets divestment regime; Judicial liquidation; Liquidation Judiciaire; Redressement judiciaire

Le statut juridique des dirigeants de sociétés commerciales de l'OHADA à l'aune des contraintes de la responsabilité sociétale des entreprises - Ndong, Papa Keyi Abel Fademba (Université Cheikh Anta Diop, 2017)
Keywords: CSR; Dirigeant social; Droit OHADA; RSE; Responsabilité sociétale de l'entreprise; Société commerciale

Etude de la performance de la coopétition par le capital social : le cas des mines artisanales de diamant au Kasai, en République Démocratique du Congo - Ngidjima Loleke Lotshangola, Jose (Université de Limoges, 2017)
Dans une économie globalisée actuelle, où l’environnement entrepreneurial est défini comme incertain et turbulent, les entreprises choisissent les stratégies de coopétition pour avoir des avantages et performances. Mais, selon la littérature spécialisée, si les avantages et les performances, sont mis en avant pour justifier la pertinence des stratégies de coopétition, la notion d’opportunisme du partenaire est elle aussi largement investie et identifiée par des recherches comme un frein à la coopétition. C’est de cette façon, qu’on peut constater dans cette littérature, deux thèses différenciées qui caractérisent les analyses sur la coopétition ; une relation entre concurrents, source de performances hors normes et une relation fragile et instable à tout instant, à raison de l’opportunisme présumé du partenaire. L’opportunisme du partenaire s’avère particulièrement problématique en ce qu’il conduirait à limiter les performances et avantages attendus de la coopétition. L’objectif de cette recherche est d’établir un lien entre la performance de la coopétition et le capital social. Partant de l’opportunisme du partenaire, nous avons posé que la performance d’une coopétition est fonction de deux préalables : la réduction de l’opportunisme et l’augmentation de l’engagement des acteurs en relation. Une étude empirique est menée auprès des coopétitions des TPE minières exploitant le diamant au Kasaï, en République Démocratique du Congo. Une méthodologie qualitative permet le recueil des données par entretiens semi-directs, puis l’exploitation des termes des discours en se servant de l’outil lexicometrique, « Iramuteq ». L’objectif est de repérer les éléments déterminés de manière théorique, et qui traduisent soit les enjeux de la coopétition pour les TPE d’un environnement difficile, soit la pertinence du capital social dans la performance de la coopétition. Des liens établis entre la réduction de l’opportunisme, l’augmentation de l’engagement et les avantages tirés de la coopétition avec le capital social, constituent l’apport de cette recherche. Apport qui concerne les connaissances tant en management de la coopétition, que relatives aux TPE de contexte difficile. La variable-clé, « opportunisme » du partenaire, est la source du lien constaté entre la performance de la coopétition et le capital social. La logique suivie se décline en réponse aux interrogations formulées dans la littérature par différents auteurs au sujet de l’opportunsme qui conduit à la fragilité et à l’instabilité de la coopétition. Ce qui nous autorise de formuler un modèle vertueux de la performance de la coopétition par le capital social. A l’issu de notre étude empirique, une discussion sur des implications managériales est menée, aboutissant à une forme spécifique de coopétition mobilisant deux niveaux de réseau et des préconisations sont envisagées. In today’s global economy, where the entrepreneurial environment is defined as uncertain and turbulent, companies choses coopétition strategies to have advantage and performance. But, according to the specialized literature, if the advantage and the performance are highlighted to justify the relevance of the strategies of coopetition, the notion of opportunism of the partner is also widely invested and identified by research as a brake on coopetition. It is in this way that we can see in this literature two differentiated theses which goods the analyses on coopetition; a relationship between competitors, a source of exceptional performance and a fragile and unstable relationship at all times, on account of the supposed opportunism of the partner. The opportunism of the partner is particularly problematic in that it would lead to limiting the performance and advantages from expected coopetition. The aim of the research is to establish a link between the performance of coopetition and social capital. Based on the opportunism of the partner, we have posited that the performance of a coopetition depends on two prerequisites: the reduction of opportunism and the increase in the commitment of the actors in relationships. Year empirical study is being carried out on the coopetition of very small mining companies of diamond in kasaï in Democratic Republic of Congo. A qualitative methodology allows the collection of data by semi direct interviews and the operation of the terms of speech using the lexicon metric tool “Iramuteq”. The objective is to identify the theoretically determined elements, which reflect either the stakes of coopétition for very small mining companies in a difficult environment or the relevance of social capital in the performance of coopetition. The link between the reduction of opportunism, the increase in commitment and the advantages of coopetition with social capital are the contribution of the research, contribution that concerns the knowledge both in management if coopetition, and relating to the very small mining companies of difficult context. The key variable “opportunism” of the partner is the source of the link between the performance of coopetition and social capital. The logic followed us in response to the questions raised in the literature by different authors about the risk of opportunism that leads to the fragility and instability of coopetition. This allows us to formulate a virtuous model of the performance of coopetition through social capital. At the end of our empirical study, a discussion on managerial implications is conducted; leading to a specific form of coopetition invoicing two levels of network and recommendations are envisaged.
Keywords: Capital social; Coopétition; Diamant; Difficult environment; Environnement difficile; Kasaï (Congo; République démocratique); Opportunism; Opportunisme; Très petite entreprise; Very small company

L'inégalité entre associés en droit des sociétés - Ndiaye, Momath (Université Paris 1, 2017)
Initialement, le droit des sociétés était dominé par un principe général d'égalité. Par conséquent, la discrimination entre associés n'était admise que de façon exceptionnelle. Cette situation a, toutefois, évolué sous l'effet conjugué de deux phénomènes. D'une part, doctrine et jurisprudence s'accordent depuis longtemps à admettre que l'égalité entre associés n'a qu'une portée relative. Celle-ci doit s'apprécier in concreto et ne s'oppose pas aux traitements inégalitaires entre associés justifiés par la défense de l'intérêt social ou l'existence de différences de situations. D'autre part, le législateur a progressivement introduit dans le droit des sociétés de nombreux mécanismes ayant une fonction inégalitaire. Il en était ainsi des anciennes catégories d'actions, en l'occurrence les actions de priorité, celles à dividende prioritaire sans droit de vote, des certificats d'investissement ou de vote. Il en est de même des actions de préférence et des avantages particuliers. Tous ces dispositifs ont pour vocation de rompre l'égalité entre associés, en procurant à certains, des privilèges non partagés par les autres. Pourtant, la loi permet, ou permettait, largement leur instauration. Au regard de ces observations, il était devenu légitime de s'interroger sur l'existence d'un droit de discriminer entre les associés.L'ambition de cette étude est de démontrer que l'inégalité entre associés bénéficie d'une validité générale dans les sociétés. En clair, construire une définition, déterminer ses fondements juridiques, les possibilités et les limites ainsi que la procédure de sa création et de sa disparition, tels sont les éléments qui devaient être apportés à la réflexion juridique afin de permettre aux praticiens d'aborder la discrimination entre associés avec plus de sérénité. Initially, corporate law was dominated by a general principle of equality. Consequently, discrimination between partners was admitted only exceptionally. This situation, however, evolved under the combined effect of two phenomena. On the one hand, doctrine and jurisprudence have long admitted that equality between partners has only a relative scope. This one must be assessed ''in concreto'' and does not oppose unequal treatment between partners justified by the defense of the social interest or the existence of differences of situations. On the other hand, the legislator has gradually introduced into the law of companies many mechanisms having an inegalitarian function. This was the case with the old share classes, namely the priority shares, those with priority dividend without voting rights, investment certificates or voting certificates. The same is true of preferred stocks and special advantages. All these devices have the vocation of breaking the equality between partners, by providing to some of them, privileges not shared by others. However, the law largely allows, or allowed their institutionalization. In view of these observations, it became legitimate to question the existence of a right to discriminate between partners.Therefore, the ambition of this study is to demonstrate that inequality between partners enjoys general validity in companies. Clearly to construct a definition, to determine its legal foundations, the possibilities and limits, and the procedure for its creation and its disappearance, these were the elements that needed to be reflected in law in order to allow practitioners to approach discrimination between partners with more serenity.
Keywords: Actions de préférence; Associés; Avantages particuliers; Companies; Corporate law; Droit des sociétés; Désavantage particuliers; Equality; Inequality; Inégalité; Liberté contractuelle; Partners; Prefered stock; Sociétes; Special advantages; Égalité

Compra e venda de participações societárias de controle - Buschinelli, Gabriel Saad Kik (Universidade de São Paulo, 2017)
A compra e venda de participações societárias de controle é contrato de inegável relevância prática. Juridicamente, a sociedade permanece titular de seus bens. Economicamente, a transferência das participações societárias possui efeito similar à circulação dos ativos. É natural e intuitiva, portanto, a equiparação entre a alienação de quotas e de ações, de um lado, e a negociação da empresa, de outro. O estudo, porém, investiga os fundamentos e os limites das teorias que definem o regime do negócio jurídico com base na realidade econômica, defendendo sua inadequação. A tese sustenta que o contrato de compra e venda de participações societárias (i) é dotado de autonomia categorial; (ii) suscita problemas específicos, que devem ser assim analisados; e (iii) somente deve ser equiparado com outras formas de transmissão de bens integrantes do patrimônio de maneira excepcional e justificada. O trabalho é composto por cinco capítulos. No primeiro, questiona-se quais seriam os pressupostos metodológicos para o afastamento da personalidade jurídica societária. Assentadas as bases teóricas, passa-se, no segundo, à compreensão dos traços específicos que caracterizam o contrato. A partir de perspectiva funcional, o terceiro capítulo indaga a possibilidade de serem aplicados regimes jurídicos previstos para o trespasse de estabelecimento, para a transferência de imóveis ou para a cessão de posição contratual quando ocorre negociação de participações de controle de sociedade que seja titular desses bens. No quarto capítulo, são analisados o dever de informar e o ônus de se informar na fase pré-contratual. Ao final, é apresentado o regime de responsabilidade do vendedor e os mecanismos de tutela de que o comprador pode-se valer caso constate deformidades dos títulos ou dos elementos do patrimônio societário.
Keywords: Business establishment; Compra e venda; Contractual liability; Controle acionário; Corporate law; Duty to inform; Equity investments; Negócio juridico; Purchase and sale; Shares; Sociedade comercial; Société commerciale

Aspectos jurídicos do processo de formação de capital por meio do mercado de valores mobiliários: as alternativas de organização e capitalização das sociedades empresárias - Pitta, André Grünspun (Universidade de São Paulo, 2017)
O presente trabalho tem por objetivo avaliar o arcabouço jurídico e regulatório brasileiro relativo às formas de organização das sociedades empresárias e aos instrumentos de captação de recursos a elas disponíveis, de modo a verificar em que medida favorecem o processo de formação de capital por meio do mercado de valores mobiliários. Para tanto, são avaliados determinados aspectos associados à disciplina das sociedades empresárias e ao processo de captação de recursos, reputados relevantes sob a perspectiva do fomento à utilização do mercado de valores mobiliários para a formação de capital. O Capítulo 2 estabelece os elementos principais que justificam a pesquisa conduzida e as premissas adotadas na análise que se seguirá da disciplina jurídica que conforma o processo de formação de capital por meio do mercado de valores mobiliários. O Capítulo 3 analisa as estruturas jurídicas para organização das sociedades empresárias, com o objetivo de averiguar a natureza de determinados requisitos organizativos impostos como precondição para a utilização do mercado de valores mobiliários. Partindo de elementos advindos da teoria do contrato financeiro, busca-se analisar determinados aspectos da disciplina societária – associados à alocação de direitos políticos e econômicos entre investidores e empreendedores, à estrutura decisória e administrativa da empresa e ao regime de destinação de seus resultados – em relação aos quais um maior espaço para a autonomia privada é salutar à conformação dos arranjos subjacentes à relação de investimento que se estabelece entre investidores e empreendedores no âmbito do processo de formação de capital por meio do mercado de valores mobiliários. O Capítulo 4 trata de analisar as estruturas jurídicas e regulatórias que regem a captação de recursos por meio do mercado de valores mobiliários, especialmente a partir dos mecanismos de formação privada (private equity e venture capital), semipública (ofertas restritas, limitadas e dispensadas de registro) e pública de capital, com o objetivo de averiguar se as alternativas postas à disposição das sociedades empresárias e o balanceamento regulatório aplicável favorecem o processo de formação de capital por meio do mercado de valores mobiliários. Conclui-se, ao final, que a disciplina societária e do mercado de valores mobiliários brasileiro é dotada de elementos de rigidez e inflexibilidade em vários aspectos relevantes, especialmente em comparação com a disciplina norteamericana e europeia. A diminuição do espaço da autonomia privada em relação a tais aspectos pode afetar a atratividade do mercado de valores mobiliários enquanto alternativa de financiamento da atividade empresária.
Keywords: Capital formation; Capitalisation; Corporate law; Corporate structure; Formation de capital; Formação de capital; Marché des capitaux; Mercado de capitais; Securities market; Securities offers; Sociedade comercial; Société commerciale; Valeurs mobilières

A regra dos §§ 8º e 9º do art. 118 da Lei das S.A. e a possibilidade de abuso do poder de controle em companhias - Vilar, Bruno Haack (Universidade de São Paulo, 2017)
Esta tese trata do abuso do poder em companhias sob controle conjunto formado a partir da celebração de acordo de acionistas e o exercício das prerrogativas conferidas pelo art. 118, §§ 8º e 9º da Lei das S.A. aos acordantes e aos presidentes da assembleia geral e órgãos colegiados de administração da companhia. Seu objetivo precípuo é contribuir para a delimitação do risco de que tais prerrogativas sejam utilizadas para a prática de atos ilícitos. O tema é investigado dogmática e empiricamente - neste segundo caso, mediante um estudo de caso da capitalização de Oi S.A., realizada em 2014. No Capítulo I caracterizam-se o poder de controle conjunto e o acordo de acionistas sobre exercício do poder de controle. No Capítulo II, analisa-se o abuso do poder de controle, tanto no direito estrangeiro (escolhidos como paradigmas de análise os Estados Unidos da América e Reino Unido da Grã-Bretanha e Irlanda do Norte), quanto no brasileiro, e relaciona-se tal conceito ao de benefícios privados do controle (ou tunneling), desenvolvido por economistas. Por fim, no Capítulo III analisam-se as normas do art. 118, §§ 8º e 9º da Lei das S.A. Em cada um dos capítulos a análise dogmática é seguida de estudos empíricos que visam a aplicar os conceitos desenvolvidos ao caso estudado. Ao final, conclui-se que somente sob circunstâncias específicas os direitos e deveres decorrentes dos §§ 8º e 9º do art. 118 podem servir de instrumento ao abuso do poder de controle - quando não houver incentivos para que os acordantes cheguem a uma solução negociada, evitando os conflitos que levariam à aplicação de tais dispositivos. This thesis addresses the abuse of control power by controlling shareholders in companies under joint control based on a shareholders' agreement and the use of the faculties granted by Section 118, §§ 8th and 9th to the parties to shareholders' agreement and the chairmen of the general meeting and boards of the company. Its main objective is to contribute to delimitation of the risk of use of such faculties for the practice of illicit acts. The theme is analysed both dogmatically and empirically - in the latter case, via a case study of the capitalization of Oi S.A., which took place in 2014. In Chapter I joint control and shareholders' agreements for the exercise of control power are defined. In Chapter II, the abuse of control power is examined, both in foreign law (chosen analytical paradigms are the United States of America and the United Kingdom of Great Britain and Northern Ireland), and in Brazilian law, and said concept is related to that of private benefits of control (or tunnel - ling), as developed by economists. Finally, in Chapter III the rules of Section 118, §§ 8th and 9th of the Companies Act are reviewed. In each chapter dogmatic analysis is followed by empirical studies which aim at applying the concepts developed to the case studied. By the end, it is concluded that only under specific circumstances the rights and duties arising from §§ 8th and 9th of Section 118 may work as instruments for the abuse of control power - whenever there are no incentives for the parties to the shareholders' agreement to reach a negotiated solution, avoiding the conflicts that would lead to employment of said provisions.
Keywords: Abuse of control power; Abuso de poder; Brasil; Case study; Company; Control power; Controle acionário; Direito Comercial; Direito Comparado; Estados Unidos; Grã-Bretanha; Oi S.A.; Shareholders' agreements; Sociedade por ações

Intervenção judicial na administração de sociedade: nomeação de interventor provisório - Vidal Neto, Ademar (Universidade de São Paulo, 2017)
A tese propõe a sistematização da intervenção judicial na administração de sociedades no Brasil. Para tanto, adotou-se um conceito restritivo de intervenção judicial, assim consideradas apenas as hipóteses em que o magistrado nomeia interventor provisório (terceiro estranho ao quadro social) para integrar-se à administração da sociedade. Existem diversas modalidades de intervenção – da mais branda (nomeação de interventor-observador) à mais incisiva (nomeação de interventor-administrador) –, devendo o juiz eleger a que melhor atenda às necessidades do caso concreto. A aplicação do instituto deve ser encarada como medida excepcional, última alternativa, diante das graves consequências que pode produzir, circunstância que não pode e não deve, todavia, impedir a sua utilização sempre que necessário (manejada de forma adequada, a intervenção pode ser de grande valia para a solução do conflito societário). The thesis proposes the systematization of the judicial interference in the management of companies in Brazil. For that purpose, a restrict concept of judicial interference was adopted, considering as so solely the situations in which the judge appoints a temporary intervenor (a third party outside of the company's bodies) to integrate itself to the company's management. There are several types of interference - from the softer ones (appointment of an observing intervenor) to the stronger ones (appointment of a managing intervenor) -, being up to the judge to select the one that best suits the necessities of the specific case. The use of the institute should be faced as an extraordinary measure, a last resource, due to the serious consequences it can produce, circumstances which, however, should not and shall not prevent its use when necessary (if managed adequately, the interference can be of great value to the resolution of corporate conflicts).
Keywords: Appointment of temporary intervenor; Choice of the intervenor; Civil liability; Control mechanisms; Corporate conflicts; Direito Comercial; Interference decree; Judicial interference; Principle of the minimum interference; Responsabilidade civil; Sociedade comercial

La fiscalité des groupes de sociétés : étude comparée - Boumeddane, Zaza (Université d'Oran 2 Mohamed Ben Ahmed, 2017)
La fiscalité des groupes de sociétés intéresse le monde des affaires et tout contribuable. Le régime fiscal des sociétés est très incitatif à la création de groupes. Cela dit, c’est un régime fiscal récent en Algérie, son application nécessite des conditions. Il peut faire l’objet d’une révision. Le code fiscal algérien s’est ressourcé beaucoup du Code General des Impôts français. La détermination du résultat fiscal d’ensemble est restée une très grande problématique. Le résultat fiscal nécessite différents retraitements. Les transferts de bénéfices et le régime des restructurations donnent eux aussi droit à des impositions. Le régime de consolidation fiscale vise avant tout l’impôt sur les bénéfices des sociétés, cela dit les droits d’enregistrements, la taxe sur la valeur ajoutée, les cas de cessation du régime et les cas de sortie entrainent elles aussi des retraitements. Le groupe de sociétés peut être soumis à un contrôle fiscal en cas d’anomalies dans les déclarations fiscales. Company group’s taxation interests the business world and every taxpayer. Companies’ fiscal regime is very incentive to company creation. This type of regime is recent in Algeria. Its application regimes conditions, it is susceptible of revision. Algeria’s fiscal code has taken much from France’s general fiscal one. The determination of overall tax result is still a very large problematic. Tax result requires different adjustments. The transfer of profits and the regime of restructuring gives right to taxation. The tax consolidation regime aims primarily at taxing companies on their profits. Registration fees, the added tax value and cases of regime cessation, and cases of output causes retreatment. Company groups may be subject to tax control in case of anomalies in tax declaration.
Keywords: Account consolidation; Acte anormal de gestion; Consolidation des comptes; Consolidation fiscale; Division of taxation; Droit des sociétés commerciales; Fiscal consolidation; Fiscalité; Fiscalité des apports partiels d’actifs; Fiscalité des fusions; Fiscalité des scissions; Group of companies; Groupe de sociétés commerciales; Management act; Opérations de restructuration; Result owerall taw; Régime fiscal; Résultat fiscal d’ensemble; Tax; Tax asset partial contributions; Tax regime for restructuring commercial companies; Tax treatment of abnormal; Taxation of mergers; Taxe sur la valeur ajoutée; Transfer of profits to abroad; Transfert de bénéfices vers l’étranger; Value added tax

Sınır aşan şirket birleşmelerine uygulanacak hukuk - Kavlak, Bengül (Dokuz Eylül Üniversitesi, 2017)
Son yıllarda, uluslararası ticaret hukukundaki gelişmelerle birlikte sınır aşan şirket birleşmeleri de giderek önem kazanmıştır. Şirketler bakımından yabancı bir şirketle birleşmenin getirdiği pek çok avantaj yanında, çeşitli zorluklar da mevcuttur. Bu zorluklardan en önemlilerinden bir tanesini de sınır aşan birleşmelere uygulanacak hukukun tespiti oluşturmaktadır. AB hukukunda, sınır aşan şirket birleşmelerine ilişkin düzenlemeler öngörülerek üye devletler arasındaki uygulamanın yeknesaklaştırılması adına 2005/56/EC sayılı Direktif kabul edilmiştir. Türk hukuku bakımından ise, sınır aşan şirket birleşmelerinin önemine vurgu yapılmakla birlikte bu hususta henüz bir düzenleme getirilmiş değildir. Çalışmada, AB hukukunda bu hususta öngörülen düzenlemeler de değerlendirilmek suretiyle, Türk hukukunda sınır aşan şirket birleşmelerine uygulanacak hukukun tespiti üzerinde durulmuştur. Sınır aşan şirket birleşmelerine uygulanacak hukuka ilişkin görüşler de değerlendirilerek, AB hukuku ile de uyum sağlamak adına, Türk hukukunda her bir birleşme işlemi için uygulanacak hukuk değerlendirilmiş ve sınır aşan şirket birleşmelerine uygulanacak hukuka ilişkin düzenleme önerisinde bulunulmuştur. Anahtar Kelimeler: Sınır aşan birleşme, uygulanacak hukuk, şirket birleşmeleri, 2005/56/EC, AB hukuku. With the recent developments in international commercial law, cross-border mergers have been developed during the last few decades. Besides the advantages of merging with a company from a different country, there are also some difficulties especially about determining the applicable law. In European Union, Directive 2005/56/EC of the European Parliament and of the Council of 26 October 2005 on cross-border mergers of limited liability companies has been accepted to regulate this issue and harmonise the rules of substantive law of the member states. In Turkish law, despite the emphasize on the significance of the cross-border mergers at the preamble of Turkish Commercial Code, currently there is no codification about cross-border mergers. This study attempts to make a discussion about the applicable law to cross-border mergers from the perspective of Turkish law and a comparison between the regulations of European Union law and Turkish law. Yet, taking into consideration the EU-Turkey relations and the developments about the adaption of Turkish law to European Union law, the harmonization of rules about cross-border mergers must be inevitable. As the applicable law to cross-border mergers is topical and important subject for Turkish law, the study will also deal with the legislation proposal in accordance with European Union law. Key Words: merger, cross-border merger, applicable law, 2005/56/EC, EU law.
460545
Keywords: Avrupa Birliği hukuku; Birleşmeler; European Union law; Fusion d'entreprises; Intenational strategical mergers; International Law; International enterprises; International integrations; Mergers; Uluslararası Hukuk; Uluslararası bütünleşmeler; Uluslararası işletmeler; Uluslararası stratejik birleşmeler; Şirket birleşmeleri

Kurumsal yönetim ilkeleri bakımından halka açık anonim şirketlerde icrada görevli olmayan yönetim kurulu üyeleri - Küçükgüngör, Makbule Asli (Ankara Üniversitesi, 2017)
In publicly held companies where the shareholdership is differentiated from the control and the management of the company, the dispersed shareholding structure prevents the active involvement of the shareholders in the company management while the directors have the opportunity to act in their personal interests. The aforementioned conflict of interest between the shareholders and the directors in the management of the publicly held companies which has been identified as "Principle-Agent Problem" in economic literature has had substantial effect in modern company law. Accordingly, considerable work in the company law has been dedicated to the legal strategies developed to decrease the cost of monitoring directors for shareholders. One of the main corporate governance strategies that is developed to deal with the "Principle-Agent Problem" focuses on increasing the number and the effectiveness of the directors who are not involved in the managing activities of the company. The main principle of this legal strategy is the designing the structure of the board of directors on the basis of team spirit and mutual accountability. In that sense, non-management directors conduct their duties as directors without having management tasks in the company. As these directors work on a part time basis they are not fully depended to the company and in principle they receive symbolic amounts of remuneration. Under this incentive strategy it is accepted that the esteem and reputation that the non-management directors preserve in eye of the public are the main incentives that motivate them to monitor the managing directors. The corporate governance principles are designed as alternative to the rule based regulation approach in company law. The non-management directorship which is introduced as a corporate governance concept for solving the problem of conflict of interest between the shareholders and the directors is the focus area of this thesis. The thesis consists of five parts. In the first part of this study, the concept of corporate governance which is the source of non-management director concept and the conflict of intererest problem between the shareholders and the directors regarding the management of the publicly held companies have been introduced. In this regard, "Centralised Management" and "Principle-Agent Problem" are explained. Finally, based on the "Principle-Agent Problem" the legal theories that are developed to increase the effectiveness of the board of directors, the categorisation of those strategies that has been introduced and place of the non-management directors among those strategies are clarified. In the second part the emergence of the concept of non-management directorship system and the development of the mechanisms for increasing director independence are described and different forms of non-management directors in one-tier board structures are analysed. On this subject the legal designing of the concepts of independent and disinterested directorship which is developed in American law and non-executive directorship which is introduced in the British Law is analysed. In the third part, the concept of the supervisory directorship which corresponds to the non-management directorship in two-tier board system is examined. Forth part of the thesis focuses on the comparison of one-tier and two-tier board structures in application of the non-management directorship concept. Within this scope, it has been analysed whether there is a convergence in the functions of non-management directors in terms of supervision, strategy development and networking in the two types of board systems. Related to this analysis, the effectiveness of the non-management directors in one-tier and two-tier board systems and the role of the institutional investor regarding this effectiveness is evaluated. In recent years, depending on the inclination of convergence in different law systems, there has been an alignment effort in the European Union to have a single set of rules regarding the non-management directors. In this respect as a final focus point, in this part, the regulations of the European Union regarding the non-management directors are examined. The fifth part is dedicated to legal design of the independent directorship which is regulated under the non-management directorship concept in the Turkish law. Turkish Commercial Code is the general code that regulates all joint stock corporations including the publicly held ones. Therefore in order to explain the effects of Anglo-American approach on the administrative organ, the approach of the Turkish Commercial Code regarding the structure and functioning of the board of directors which are based on corporate governance principles are explained. Following that general introduction, the system change regarding the corporate governance principles in Turkey which consists of application of mandatory rules rather than "Comply or Explain" approach that is applicable to independent directors is explained. After that the independence criteria which are set for the independent directors under the capital market regulations for publicly held joint stock corporations and the role of independent directors in decision making mechanism are analysed. Finally, the structure and functioning of the board committees are evaluated by examining the functions of the independent board members.
482045
Keywords: Bağımsız idari otoriteler; Commercial law; Corporate governance; Halka açık ortaklıklar; Independent administrative authority; Kurumsal yönetim; Management; Members of the board directors; Principle; Public held companies; Representation; Ticaret hukuku; Vekalet; Yönetim; Yönetim kurulu üyeleri; İlke

Anonim ortaklık genel kurul toplantılarında pay sahibinin temsili - Tekten, Emel (Erciyes Üniversitesi, 2017)
Pay sahipleri genel kurula katılma maliyetlerinin fazla gelmesi, buna ayıracak zamanlarının olmaması veya sağlık sorunları gibi sebeplerle dolayı genel kurula katılmak istemeyebilir. Bunun sonucunda pay sahiplerinin şirketin işleyişine ve genel kurul kararlarına etki etme olasılıkları zayıfladığından; genel kurullarda, etkin ve iyi organize olmuş pay sahipleri gerçekte çoğunluk olmasalar da istedikleri kararların alınmasını sağlayabilmektedirler. Bu durum genel kurulda güç boşluğu sorununun doğmasına neden olmaktadır. Bu kapsamda anonim şirket genel kurulunda pay sahibinin temsilinin bu konudaki sorunları giderme de önemli bir rolü vardır. İşte tezimizin konusu, TTK ve SerPK çerçevesinde anonim şirket genel kurulunda pay sahibinin temsilidir. Bilindiği üzere 6102 sayılı TTK bir bütün olarak 01.07.2012 tarihinde yürürlüğe girmiş ve böylece elli yılı aşkın bir süredir uygulanan 6762 sayılı eTTK'yı yürürlükten kaldırmıştır. Yine 6362 sayılı SerPK 30.12.2012 tarihinde yürürlüğe girerek 2499 sayılı SerPK'yı yürürlükten kaldırmıştır. Bu yeni kanunlarda tez konumuzla ilgili olarak bir dizi değişiklikler yapılmış ve yenilikler getirilmiştir. Tez konusunun seçilmesindeki amaç, pay sahibinin temsiliyle ilgili olarak TTK ve SerPK mevzuatlarında getirilen yeni düzenlemelerin Yargıtay kararları, öğretideki görüşler ve mukayeseli hukuk ışığında değerlendirerek olası problemler karşısında çözüm önerileri getirip Türk Hukukuna katkı sağlamaktır. Bu tez çalışmasının ortaya konulması sırasında özellikle konuya kaynaklık eden İsviçre Hukuku ve literatüründen faydalanılmıştır. Konu, Türk Hukuku bakımından incelenirken İsviçre Hukukundan farklılıkları ve benzerlikleri ortaya konulmaya çalışılmıştır. Bunun dışında konumuzla ilgili olarak Alman, Amerikan, İngiliz ve Avrupa Birliği Hukuklarından da yararlanılmıştır. Yapılan değerlendirmeler sonucunda birçok sonuçlar elde edilmiştir. Ancak özellikle şunu belirtmeliyiz ki; halka açık anonim ortaklıklar düşünülerek getirilen TTK m. 428'de ifade edilen toplu temsilciler ile ilgili düzenleme, SerPK m. 30/4'te ve SPK II-30.1 sayılı Tebliğ m. 5/3 düzenlemeleri sebebiyle uygulanmayacaktır. Üstelik bu hükümler nedeniyle Türk Ticaret Kanunu ile Bazı Kanun ve Kanun Hükmünde Kararnamelerde Değişiklik Yapılmasına Dair Kanun Tasarısı Taslağı m. 12'de TTK m. 428, 430 ve 431 hükümlerinin yürürlükten kaldırılması öngörülmektedir. Getiriliş amacı geniş kitlelerin temsilini sağlamak olan bu hükümleri yürürlükten kaldırmak yerine, SerpK'nın ilgili hükümleri ile gerekli koordinasyon sağlanarak, bunların tüm ortaklıklar yönünden uygulanmasının yolu açılmalıdır. Anahtar Kelimeler: Anonim Ortaklık; Genel Kurul; Pay Sahibi; Temsil. Shareholders may refrain to join general assembly meetings due to the reasons like participation costs, lack of time and health issues. Since the possibility of the shareholders to have an impact on the functioning of the company and its general assembly gets weakened as a result of non-attendance, active and well-organized shareholder groups-despite the fact that they do not constitute the majority of the shareholders- may achieve their desired general assembly decisions. This particular issue causes an occurrence of a power gap in general assemblies. In this context, representation of the shareholders in the general assembly of the joint stock companies plays a role of utmost importance in eradicating such problems. Hence, the topic of my thesis is the representation of the shareholders in the general assembly of the joint stock companies within the legal framework of Turkish Commercial Code and Turkish Capital Market Code. As known, Turkish Commercial Code No. 6102 came into force in 01.07.2012, repealing former Turkish Commercial Code No. 6762 which was in force for more than fifty years. Also, Turkish Capital Market Code no. 6362 came into force in 30.12.2012, repealing former Turkish Capital Market Code no. 2449. There has been a series of amendments performed on those two codes concerning my thesis topic. My main goal on choosing this topic is to contribute to Turkish Law through assessing those amendments in the light of supreme court orders, scientific opinions and comparative law and to provide solutions to the existing and prospective problems. In preparation of this work, apart from Turkish Law, Swiss Law is highly referenced as it constitutes the main source of the issue. Therefore, while assessing the point, similarities and differences between Turkish and Swiss law is asserted. Besides, German Law, European Union Law, American Law and English law are also referenced for the sake of the proper assessment of the topic. As a consequence of made analyzes, a lot of conclusions are drawn. However, it is to be pointed out particularly that the regulations in Turkish Commercial Code No. 6102 article 428 which were provided considering open joint stock companies will not be applied because of Turkish Capital Market Code No. 2449 article 30/4 and the regulation of Turkish Capital Market Board no. II-30.1 article 5/3. Moreover, because of those provisions, repealing of the articles no. 428,430,431 of Turkish Commercial Code no. 6102 is at stake. Instead of repealing those provisions of Turkish Commercial Code no. 6102 -which aim at representation in a broader sense- establishing the coordination between those provision and related Turkish Capital Market Code provisions and enabling the application of those provisions on all sort of companies must be done. Keywords: Joint Stock Company, General Assembly, Shareholder, Representation
480444
Keywords: Actionnaires; Anonim ortaklıklar; Assemblée générale; Consumer right to representation; Genel kurul; Genel kurul kararları; General assembly; General assembly resdutions; Incorporated companies; Meetings; Pay sahipleri; Representation; Représentation; Shareholders; Temsil; Temsil edilme hakkı; Toplantılar; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Pay sahipleri sözleşmesinden doğan birlikte satma hakkı ve birlikte satışa zorlama hakkı - Yilmaz, Gülşah (Dokuz Eylül Üniversitesi, 2017)
Birlikte satma hakkı ve birlikte satışa zorlama hakkı pay sahipleri sözleşmesinde yer alan iki haktır. Bu hakların kaynağı Amerikan hukukudur. Bu haklar ülkemizde anonim şirket esas sözleşmelerinde sıklıkla yer almaktadır. Bu çalışmada Amerikan hukukundan gelen bu haklar Türk Ticaret Hukuku kuralları açısından incelenmiştir. İnceleme yöntemi ilk olarak hakların tanıtılması ikinci olarak ortaya çıkardığı hukukî ilişkinin niteliğinin tespiti ve son olarak hukukumuza ait yasal düzenlemeler karşısında ne derece geçerli kabul edilebileceğinin belirlenmesi şeklindedir. Çalışmada, hakların karşılaştırmalı hukuktaki yeri incelenmiştir. Bu kapsamda yabancı mahkeme kararları ve yasal düzenlemeler hakkında bilgi verilmiştir. Akabinde hakların hukukî niteliği ve haklardan doğan borçlar incelenmiştir. Son olarak hakların anonim ve limited şirket sözleşmelerinde yer alması durumunda meydana gelebilecek hukukî sorunlar tartışılmıştır. Bu kapsamda hakların yarattığı pay devir sınırlandırmasının anonim şirketler hukukunda yer alan kurallar karşısındaki durumu incelenmiştir. Ayrıca hakların limited şirketlerde pay devri ile ilgili düzenlemeler açısından geçerliliği tartışılmıştır. Anahtar Kelimeler: Birlikte Satma Hakkı, Birlikte Satışa Zorlama Hakkı, Pay Devrinin Sınırlandırılması, Pay Sahipleri Sözleşmesi, Anonim Şirket Esas Sözleşmesi. Tag along right and drag along right are two rights in shareholders' agreement. The source of these rights is American Law. These rights are frequently found in the articles of association of the joint stock company in our country. In this study, these rights coming from American law were examined in the terms of Turkish Commercial Law. The examination method is firstly the identification of the rights, secondly the determination of the nature of the legal relationship that emerges from the rights and finally the determination of the extent to which they can be regarded as valid under the legal regulations of our law. In the study, the position of the rights in comparative law were examined. In this context, information is given about the foreign court decisions and legal regulations. Then the legal nature of the rights and the obligations arising from the rights were examined. Finally, the legal issues that may arise in case of the rights are included in joint stock company and limited company contracts are discussed. In this context, the situation of the share transfer restrictions created by the rights against the rules in the corporation law has been examined. Furthermore, the validity of the rights in terms of the share transfer regulations in limited companies has been discussed. Keywords: Tag Along Right, Drag Along Right, Share Transfer Restriction, Shareholders' Agreement, Article Of Association.
486520
Keywords: Actionnaires; Anonim şirketler; Birlikte satma hakkı; Birlikte satışa zorlama hakkı; Birlikte vekalet; Drag along righ; Joint agency; Joint stock company; Pay devri; Pay sahipleri; Sale; Sales contracts; Sales methods; Satış; Satış sözleşmeleri; Satış yöntemleri; Shareholders; Tag along righ; Transfer of shares; Vente conjointe; Vente forcée

La fiducie et l'entrepreneur - Ody, Baptiste (Université de Rennes 1, 2016)
La fiducie a été introduite en droit français par une loi du 19 février 2007. Définie par l’article 2011 du Code civil, elle permet à une personne de transférer temporairement des éléments de son patrimoine vers un patrimoine fiduciaire qui est à la fois distinct du sien et de celui du fiduciaire qui en a la charge. Mécanisme sui generis relevant tant du droit des personnes que du droit des biens, la fiducie a été conçue par le législateur comme un mécanisme efficace de gestion et de sûreté. Près de dix ans après sa promulgation, sa pratique demeure pourtant confidentielle. Cette marginalité s’explique notamment par un régime juridique rigide et inadapté aux spécificités entrepreneuriales. Caractérisés tant par leur qualité de dirigeants que de propriétaires, les entrepreneurs sont pourtant les destinataires naturels de la fiducie. Ils cumulent en effet des considérations personnelles et professionnelles auxquelles l’opération fiduciaire répond utilement dans des juridictions étrangères. L’insuffisance du régime français de la fiducie est d’autant plus patente que les entrepreneurs disposent d’autres mécanismes d’affectation et/ou de rétention de propriété. Aussi, pour développer la fiducie, il apparaît nécessaire d’en libérer le potentiel en la rénovant au service des entrepreneurs.
Keywords: Affectation; Chefs d'entreprise; Contrats; Droit international privé; Entrepreneur; Entrepreneuriat; Entreprise; Fiducie; France; Gestion; Gouvernance; Gouvernement d'entreprise; Grande-Bretagne; Patrimoine; Propriété; Rétention; Sûreté; Transmission; Trust

Le pacte d'actionnaires en droit égyptien sous le prisme du droit français - Galal Sayed, Mazin (Université Lumière Lyon 2, 2016)
Les pactes d’actionnaires, conventions adoptées par les protagonistes des affaires internationales, répondent aux attentes des administrateurs et actionnaires quant à la circulation des actions et des parts sociales. Par contre, hors le marché règlementé, la liberté contractuelle accordée à la société – et actionnaires – de recourir à ce type d’arrangement contractuel, se heurte à la réalité légale et jurisprudentielle qui demeure la seule source de droit régissante cette convention. En optant pour la conclusion d’un pacte d’actionnaires, aucune disposition légale, notamment article de droit, ne régit cette convention. Ce contrat reste donc soumis aux règles de droit commun. Cette particularité accorde aux protagonistes une certaine liberté de rédaction, ce qui créé une originalité quant à la forme, au fond et aux effets de l’application du pacte. Reconnu, dans le monde des affaires français – tant par le législateur français que par les praticiens et protagonistes, comme étant une des formes adaptées à la gestion leurs sociétés, le législateur égyptien découvre encore cette forme contractuelle. La mondialisation, culturelle et commerciale, a non seulement permis de rapprocher entre les commerçants afin de trouver des solutions créatives quant à la conclusion des pactes d’actionnaires, mais aussi aux législateurs, autant bien français qu’égyptiens, de trouver des solutions quant aux problématiques qui s’opposent aux praticiens lors de la négociation, la conclusion ou même l’exécution de ces contrats. L’objet de cette étude sera d’examiner les particularités des pactes d’actionnaires dès la phase des négociations, passant par les phases de conclusion et exécution, jusqu’à la phase conflictuelle. Cette étude visera le modèle français, ayant déjà avancé sur ce domaine, en le comparant au modèle égyptien qui commence à se familiariser avec cette pratique. Bien que ces deux exemples demeurent toujours en voie d’évolution, le recours à ce type de contrat révèle des particularités et difficultés lors de son application, ce qui incitera les protagonistes à trouver des modalités novatrices permettant une mise en œuvre plus efficace de ces contrats et répondant à leurs attentes.
Keywords: Action; Actionnaire; Agreement; Authority; Bourse; Cession; Company; Company’s status; Competencia; Competition law; Concurrence; Contract; Contrat; Control; Contrôle; Convention de garantie; Conventions entre actionnaires; Corporate interests; Corporate law; Corporate liabilities; Droit des sociétés; Duration; Durée; Egypt; Enforcing contract’s execution; Expert; Exécution forcée; France; Guarantee agreement; Intérêt social; Investisseur; Investor; Minoritaire; Minority; Non-competition; Non-concurrence; Pacte; Pactes d'actionnaires; Passif social; Pouvoir; Price of shares’ transfer; Prix de cession d’actions; Publication; Share; Shareholder; Société; Sociétés; Statuts; Stock market; Stocks and shares; Titre financier; Transfer; Vote; Égypte

L'articulation entre la liberté d'entreprendre et la liberté d'association dans les cas de restructurations d'entreprises - Bourgault, Julie (Université Laval, 2016)
Au cours des dernières décennies, les restructurations d'entreprises ont connu une transformation majeure. En plus des restructurations ponctuelles, de type « crise » dans des secteurs de l'économie en déclin, il est possible de constater des restructurations de type « permanent » dont l'objectif principal est la quête de profit et l'augmentation de la productivité de l'entreprise. Perçus comme nuisibles à la rentabilité des entreprises, la syndicalisation, la négociation collective et les moyens de pression, poussent ainsi certaines entreprises à se restructurer. Les restructurations d'entreprises, produit de l'exercice de la liberté d'entreprendre, impliquent des conséquences importantes sur l'emploi des travailleurs, en plus d'affecter à bien des égards leur liberté d'association. Dans cette perspective, il est pertinent de s'interroger sur l'articulation entre la liberté d'entreprendre et la liberté d'association dans le contexte de restructurations d'entreprises. Les différentes théories du droit s'accordent quant à l'importance de la cohérence du système juridique tant à l'interne qu'à l'externe. L'essentiel de notre analyse repose, en conséquence, sur un souci de cohérence du système juridique lors de l'affrontement des libertés d'entreprendre et d'association dans le cadre de restructurations d'entreprises, par le biais, entre autre, de l'étude de la juridicité et de la normativité de ces principes du droit. D'une part, la liberté d'association est un principe du droit à statut constitutionnel, d'ordre public et qui occupe une place importante en droit international. D'autre part, la liberté d'entreprendre est un principe du droit implicite, dont les fondements et la mise en œuvre demeurent ambigus. Pourtant notre étude démontre que la jurisprudence accorde une interprétation restrictive à la liberté d'association et large à la liberté d'entreprendre. Cette réalité accorde à la liberté d'entreprendre une mainmise sur la liberté d'association, particulièrement dans les cas de restructurations d'entreprises. Il n'y a qu'à citer comme exemple le droit de cesser de faire affaire même pour des motifs socialement condamnables, énoncé à plusieurs reprises par la Cour suprême du Canada. Le principe de cohérence du système juridique devrait nous amener à une interprétation plus large de la liberté d'association afin de respecter la hiérarchie des droits et d'autres principes généraux du droit, tels que l'égalité, la dignité et la bonne foi, et ce, même si cette interprétation a parfois pour effet de restreindre la liberté d'entreprendre dans le contexte de restructurations d'entreprises.
Keywords: Canada; Entreprise (restructuration); Entreprises (réorganisation); Liberté d'association; Liberté économique; Québec

Hakim şirketin azınlığın paylarını satın alma hakkı - Tütüncü, Muharrem (İstanbul Kültür Üniversitesi, 2016)
Anonim ortaklıklar hukuku prensipleri çerçevesinde sermaye koyma taahhüdünü yerine getiren pay sahiplerinin ortaklıktan çıkarılmalarını sağlamak kural olarak mümkün değildir. 6102 sayılı TTK ile söz konusu prensibe iki önemli istisna getirilmiştir. Bunlardan ilki birleşme yoluyla ortaklıktan çıkarma (TTK md.141/2), diğeri ise hâkim şirketin azınlığın paylarını satın alma hakkıdır (TTK md.208). Satın alma hakkına ilişkin TTK md.208 hükmünün kaleme alınmasında, mukayeseli hukuktaki düzenlemelerden etkilendiği görülen yasa koyucu tarafından, Türk şirketler hukuku doktrini ve uygulamasının özellik arz eden yönlerini de dikkate alınmış ve neticede kendine özgü bir satın alma hakkı düzenlemesi ortaya çıkarılmıştır. Under the principles of the law of joint stock companies, it is not, at least in principle, possible to squeeze out the shareholders who had fulfilled their capital subcription. However, Turkish Commercial Code nr.6102 (TTK) contains two significant exceptions to this principle. These exceptions are: squeeze-out merger (TTK article 141/2) and the squeeze-out right of the controlling company (TTK article 208). Turkish legislator, considering the important aspects of the doctrine and practice of Turkish companies law and under the influence of the regulations in the comparative law, made a sui generis regulation of squeeze-out right in the article 208 of the Turkish Commercial Code.
422918
Keywords: Anonim ortaklıklar; Dominant position; Hakim durum; Incorporated companies; Satın alma hakkı; Squeeze-out right; Turkish Commercial Code; Turkish commercial law; Turkish law; Türk Ticaret Kanunu; Türk hukuku; Türk ticaret hukuku

La gouvernance d'entreprise face au respect de la vie privée des salariés - Athea, Valene (Université Paris-Est, 2015)
La notion de gouvernance semble recouvrir des thèmes proches du terme «gouverner», de la prise de décision et de l’évaluation.La gouvernance d’entreprise propose une nouvelle conception du processus de décision, accordant toute sa place à la concertation entre les parties prenantes. Le délégué syndical intervient dans ce sens, en effet, il a une mission de revendication (par exemple concernant la hausse des salaires), il est l’interlocuteur du syndicat auprès de l’employeur, il négocie avec ce dernier les normes de l’entreprise (accords et conventions collectives)Encadrée par des lois assurant l'indispensable transparence, la gouvernance d'entreprise serait théoriquement le moyen d'assurer au mieux les intérêts multiples des acteurs concernés (salariés et employeurs).C’est la raison pour laquelle il parait opportun de faire un parallèle entre l’exercice de la gouvernance d’entreprise par les acteurs concernés et le respect de la vie privée des salariés.Ce parallèle entre vie privée et gouvernance de l’entreprise a notamment été mis en exergue avec l’affaire Novartis (6 octobre 2004).L’entreprise Novartis a mis en place en 1999 un code de bonne conduite pour rappeler certains principes éthiques, seulement ce texte a été complété en juillet 2004 par de surprenantes dispositions jugées attentatoires à la vie privée des salariés par le Tribunal de Nanterre. Ce code de conduite demande notamment aux salariés de Novartis " qu'ils consacrent tout leur temps et toute leur attention au travail de Novartis pendant les heures de travail habituelles... Le temps requis pour une occupation extérieure peut générer une baisse de la productivité ". En outre, le groupe estime que "le temps requis pour une occupation extérieure, qu'elle soit de type gouvernemental, politique ou bénévole, peut générer une baisse de la productivité et de l'efficacité d'un collaborateur créant ainsi un conflit d'intérêts" Aussi Novartis exige également " une autorisation préalable " de la direction pour ce type d'activités.Le tribunal des référés de Nanterre va rendre une décision qui va porter en outre sur le fond en jugeant que ces " alinéas sont susceptibles de nuire à la santé mentale des salariés et portent atteinte à la vie privée ".La direction ne fera finalement pas appel et soumettra au Comité de groupe ainsi qu'au comité d’hygiène, de sécurité et des conditions de travail une nouvelle version de son code éthique.La gouvernance d’entreprise peut donc être limitée par le respect de la vie privée des salariés.La vie privée est l'ensemble des activités d'une personne qui relève de son intimité par opposition à la vie publique.Il parait plus juste de mentionner un "droit à l'intimité de la vie privée".En effet, il s’agit d’un droit fondamental, proclamé par la loi, inscrit dans la déclaration des droits de l'homme de 1948 (article 12), la Convention européenne des Droits de l’Homme et des libertés fondamentales (article 8), à l’article 9 du Code civil et à l’article 226-1 du Code Pénal.Les composantes de la vie privée n'ont pas fait l'objet d'une définition ou d'une énumération limitative afin d'éviter de limiter la protection aux seules prévisions légales. Les tribunaux ont appliqué le principe de cette protection, au droit à la vie sentimentale et à la vie familiale, au secret relatif à la santé, au secret de la résidence et du domicile, et au droit à l'image. Par ailleurs, il convient de préciser que c’est le contrat de travail qui détermine les règles, obligations et devoirs de chacune des parties (l’employeur et le salarié), il ne peut concerner que le temps passé au travail.Des circonstances extérieures à la vie professionnelle et tenant à la vie privée du salarié ne peuvent être prises en considération, sauf si elles affectent la relation salariale.
Keywords: Employees; Gouvernance d'entreprise; Gouvernement d'entreprise; Governance of company; Private life; Salariés; Travailleurs; Vie privée

L'aménagement conventionnel de la société commerciale en droit français et en droit OHADA - Djiguemdé, Wendkouni Judicaël (Université de Bordeaux, 2015)
Toute législation en matière économique se doit d’être souple et adaptée à l’évolution du monde des affaires. Le droit des sociétés OHADA, de même que celui français, n’échappe pas à ce principe. Très rigide à l’origine, et caractérisé par un ordre public omniprésent, le droit des sociétés commerciales OHADA est gagné par le mouvement de contractualisation des sociétés, apparu en France depuis les années 1990. Le droit des contrats s’est avéré un excellent moyen pour les praticiens d’apporter de la flexibilité au droit des sociétés. Les aménagements conventionnels, ou conventions sociétaires ou encore pactes d’actionnaires permettront aux associés d’adapter les règles légales sociétaires aux besoins deleurs activités économiques. Cession de titres sociaux, droit de vote, pouvoir de représentationdans la société, règlement des différends sont autant de domaines où se manifeste la liberté contractuelle des associés. Au-delà du caractère rigide du droit des sociétés français et OHADA, cette étude permet de rendre compte de l’importance de ces espaces de liberté dont disposent les associés. Ces pactes d’actionnaires, statutaires ou extrastatutaires, devront être encadrés par des critères précis de validité. Aussi, l’efficacité de ces aménagements dépendra en grande partie de la sanction applicable en cas d’inexécution par une des parties de ses obligations. Le dynamisme de la pratique et de la jurisprudence française permettra d’éprouver les solutions posées par le législateur OHADA en la matière. Cette étude participe ainsi de l’élaboration d’un régime juridique adapté, permettant de sécuriser ces aménagements conventionnels, signe d’une contractualisation du droit des sociétés. Any legislation concerning economic matters is expected to be flexible and adapted to the evolution of business. Company law in the OHADA (Harmonizing Business Law inAfrica Organization) as well as French company law, cannot be excluded from this principal. Although it was very strict to begin with, and characterized by omnipresent public order,company law in the OHADA was caught up by the contractualization movement which appeared in France in the 1990s. Contract law turned out to be a perfect means for practitioners to bring flexibility to company law. Contracting adjustments, company conventions or even shareholder agreements enable shareholders to adapt their legal company rules to their economic needs. Transferring titles, voting partners, ensuring the power of representation inside the company, or settling disagreements, are some examples amongst the variety of situations where the contracting freedom of partners can be seen. Despite the rigorous characteristic of French and OHADA company law, this study puts forward the importance of spaces of freedom that partners can use. These shareholders agreements, either statutory or extra statutory, will be dependent on precise validity criteria. Consequently, the efficiency of these adjustments will mainly depend on the sanction implemented when one ofthe parties does not execute the required obligation. The strength of both the practice and French case law will enable to test the proposals set down by the OHADA legislator. Therefore this study will contribute to the development of an adapted judicial system which will permit to secure these contracting agreements, as signs of the contractualization of company law.
Keywords: Actionnaires; Aménagements conventionnels; Associates; Associés; Company law; Contracting adjustments; Contractual freedom; Contractualisation; Contractualization; Conventions sociétaires; Corporate law; Droit des sociétés; Liberté contractuelle; OHADA; Ordre public; Organisation pour l'harmonisation en Afrique du droit des affaires; Pactes d'actionnaires; Public order; Shareholder agreements; Shareholders

Los Acuerdos abusivos en las sociedades mercantiles: el delito del art. 291 CP - Gramática Bosch, Gerard (Universitat Pompeu Fabra, 2015)
En este trabajo se realiza un análisis global del delito de acuerdos abusivos (art. 291 CP), principalmente de sus problemas axiológicos, de interpretación, de sistematización y de aplicación práctica. También se analiza su legitimidad penal, la naturaleza del delito y su estructura típica. En este sentido, se pretende elaborar una interpretación de lege lata y restrictiva que (1) permita una mejor comprensión dogmática del delito, una aplicación homogénea y menos conflictiva del mismo, en la que la construcción valorativa y dogmática se mantenga dentro del marco del Derecho vigente (tenor literal). Una interpretación que (2) consiga aportar algunos elementos teleológicos de interpretación restrictiva tendentes a solventar los riesgos que plantea la aplicación y sanción de esta figura delictiva en la práctica y permitan solucionar acertadamente los diversos grupos de casos conflictivos que se presentan. Por último, que (3) admita profundizar en nuevas propuestas jurídicas que puedan ser de utilidad para la interpretación y aplicación práctica de este precepto. En síntesis, se pretende realizar una aportación para una mayor concreción, normativización y sistematización del delito de acuerdos abusivos. En consecuencia, el presente es un texto dogmático jurídico-penal del delito de acuerdos abusivos y sistemático en relación a los distintos postulados normativos de la legislación española en su conjunto (p. ej., la Ley de Sociedades de Capital). También es descriptivo a los fines de presentar cuál es el estado de situación actual del tema en el ámbito legislativo, jurisprudencial y doctrinal y los principales problemas que lo afectan. Asimismo, es un texto crítico en el cual se presenta mi opinión personal. El trabajo está divido en dos partes que, a su vez, se subdividen en tres capítulos cada uno. En la primera parte, se tratan aspectos generales tales como el Derecho penal en las sociedades mercantiles (capítulo 1), los problemas del delito y el estado de la cuestión en cada caso (capítulo 2) y, por último, lo relativo a la adopción de acuerdos sociales y al mecanismo de impugnación civil de los mismos (capítulo 3). En la segunda parte del texto, en su primer capítulo, se analiza la legitimidad del delito de acuerdos abusivos, filtrándolo por el tamiz del principio de proporcionalidad en sentido amplio. Esto es, se evaluará si la intervención del Derecho penal en este contexto económico es idónea, necesaria y proporcional en sentido estricto. En el segundo capítulo se pone de manifiesto y se desarrollan los tres ejes principales del trabajo. El primero es el concepto de patrimonio y perjuicio por cuanto tienen incidencia directa en la estructura del tipo penal. El segundo es el contenido del abuso penalmente relevante como factor de delimitación del tipo penal. Y el tercero es la delimitación con el mecanismo de impugnación de acuerdos sociales. El análisis conjunto de todos estos elementos, sumados al resto de componentes típicos del delito, son los que permiten desentrañar la naturaleza del delito de acuerdos abusivos y su estructura típica. Finalmente, en el tercer capítulo se analiza la intervención delictiva en el delito de acuerdos abusivos, se resaltan algunos problemas de individualización de responsabilidad penal a título personal en órganos colegiados y se trata de brindar una respuesta a los mismos.
https://www.tdx.cat/handle/10803/370092
Keywords: Derecho constitucional; Derecho mercantil; Derecho penal

Géographie du capital et contrôle des grandes entreprises au Cameroun : impact du contexte socio-politique et culturel - Ckouekam, Odette (Université de Yaoundé 2 ; Université de Bordeaux, 2015)
Les scandales financiers dans le monde ont poussés les chercheurs ces dernièresannées à se pencher sur la question de gouvernance d’entreprise. Ainsi, de bonnes pratiquesde gouvernance d’entreprises ont été mises sur pied dans le but de protéger les créateursd’entreprises et de pérenniser ces dernières pour le bien-être de tous. De ce fait, le contrôlede l’entreprise par la gouvernance serait une priorité pour ceux qui y ont mis leur capital.Cependant, ces bonnes pratiques ne se sont pas toujours révélées fructueuses à cause ducontexte ou de l’environnement d’application qui n’est pas le même. Nos résultats issus de larégression logistique montrent des contrôles différents pour les entreprises camerounaisesnégativement corrélées aux éléments de contexte (corruption, relations interpersonnelles,clientélisme, obéissance aveugle, tribalisme, etc.) contrairement aux entreprises occidentales. Financial scandals around the world have pushed researchers in recent years to thinkabout corporate governance issue. And good governance practices of companies have beenestablished in order to protect entrepreneurs and sustain these for the welfare of all.Therefore, the company's control with governance would be a priority for those who put theircapital. However, these best practices have not always proven successful because of thecontext or the application environment is not the same. Our results of logistic regression showdifferent controls to Cameroonian companies negatively correlated to the contextualelements (corruption, interpersonal relations, cronyism, blind obedience, tribalism, etc.) incontrast to Western companies.
Thèse en cotutelle : Université de Bordeaux; Université Yaoundé 2
Keywords: Actionnariat; Control; Contrôle; Contrôle de gestion; Geography of the capital; Gouvernance; Gouvernement d'entreprise; Governance; Géographie du capital; Ownership

La protection des droits des créanciers dans les opérations de restructuration des sociétés - Boureima Soumana, Saadatou (Université de Bordeaux, 2015)
De nos jours, la restructuration est une réalité incontournable qui contribue audéveloppement et à la compétitivité des sociétés in bonis. En général, elle résulte d’une décisionprise par les dirigeants sociaux. Toutefois, sa réalisation peut contrevenir à l’exécution des droits descréanciers antérieurs des sociétés concernées par l’opération. Pour préserver leurs droits, cescréanciers disposent de nombreuses mesures de protection issues aussi bien du droit commun quedu droit spécial. L’identification du fondement de cette protection, à savoir la force obligatoire desengagements pris avant la restructuration de la société débitrice, permet de vérifier l’efficacité decette protection. Restructuring is a reality that contributes to the development and competitiveness ofcompanies in bonuses. It usually results from a decision taken by the companies executives. Itsimplementation, however, may undermine the enforcement of former creditors’ rights by thecompanies involved in the transaction. To preserve their claims, those creditors have manysafeguards from both the common law and the special law. The identification of the basis of suchprotection, namely the binding commitments made before the restructuring of the debtorcompanies, enable the verification of this protection’s effectiveness.
Keywords: Apport partiel d'actif; Assujettissement; Binding; Bona fides; Bonne foi; Capital reduction non motivated by loses; Companie; Companies executives; Creditor; Créancier; Dirigeants sociaux; Débiteur et créancier; Employees; Encorceability; Entreprises – Réorganisation; Force obligatoire; Fraud; Fraude; Fusion; Inopposabilité; Merger; Nullity; Nullité; Opposabilité; Opposition; Partial business transfer; Protection; Repair; Restructuration; Restructuring; Réduction de capital non motivée par des pertes; Réparation; Salariés; Scission; Société; Subjugation; Unenforceability

La rémunération des dirigeants sociaux - Sharkatli, Ammar (Université Lille 2, 2015)
Les rémunérations des dirigeants des sociétés cotées suscitent un vif débat tant sur leur montant que sur les principes guidant leur détermination. Ce débat est souvent intensifié par une forte médiatisation prompte à indigner l’opinion publique et à inciter le législateur à se saisir de la question. Celui-ci cherche alors à encadrer les pratiques litigieuses tantôt en imposant des mesures impératives, tantôt en favorisant l’autorégulation. La présente étude a pour ambition d’apprécier la pertinence et l’efficacité de l’ensemble de ces règles relevant du droit dur et du droit souple. Un tel examen du droit positif montre une réelle incapacité à apporter une réponse au problème de l’acceptabilité sociale des rémunérations par le biais de l’outil juridique. En témoigne l’évolution de la législation française depuis ces vingt dernières années, basée sur l’impératif de transparence et l’évolution des procédures de détermination et d’attribution des rémunérations des dirigeants. Les juges ne semblent pas davantage disposer de leviers efficaces de lutte contre l’excès des rémunérations en droit des sociétés. Maints espoirs ont donc été fondés sur les principes provenant du droit souple et en particulier de la gouvernance d’entreprise, espoirs cependant également déçus à bien des égards. Finalement, demeure particulièrement prégnante la question de savoir si le droit, qu’il soit dur ou souple, peut constituer cet outil utile et efficace de régulation du niveau de rémunérations des dirigeants de sociétés cotées
Keywords: Administrateurs de sociétés; Corporate directors; Direction générale; Dirigeants sociaux; Entreprises; Financial scandals; Infractions économiques et financières; Opinion publique; Public opinion; Remuneration; Rémunération; Salaires; Scandales financiers; Stakeholders vote; Transparence; Transparency; Vote des actionnaires

La gouvernance des sociétés commerciales en droit de l'OHADA - Ewane Motto, Patrice Christian (Université Paris-Est, 2015)
Dans l'espace de l'OHADA, la diffusion massive du terme de gouvernance relève essentiellement du contexte de la coopération internationale pour le développement. Ce nouvel impératif de gouvernance est depuis quelques années, dans le débat sur la construction d'une gouvernance d'entreprise, au cœur de tous les discours, des réformes, de toutes les initiatives en matière de développement des affaires et de fonctionnement efficace de l'entreprise. En réalité, dans cet environnement communautaire de l'OHADA, (CEMAC et UEMOA), il se trouve que la volonté politique est avant tout économique, le droit ne jouant qu'un rôle de second plan de mise en ordre a posteriori. Aussi, cela pose le problème suivant, à savoir : comment concilier d'une part, l'objectif de sécurité juridique et judiciaire indispensable pour drainer des flux importants d'investissements et, d'autre part, l'enjeu essentiel dont participe l'OHADA à l'établissement de ce qu'il est aujourd'hui coutume d'appeler « la bonne gouvernance » et de l'Etat de droit en Afrique comme vecteur de la performance économique.Au regard de l'ambition affichée par les rédacteurs de l'AUSCGIE et, sous le prisme des normes internationales, d'exigences nouvelles de développement économique et de la pérennité des entreprises, la gouvernance des sociétés commerciales pose la problématique de l'efficacité juridique de ce corps de règles. En d'autres termes, comment faire émerger dans un espace où le contrôle de l'Etat sur les activités économiques est mis à mal, des règles de gouvernance d'entreprise efficace au sein des sociétés commerciales ? Vaste programme.Dans la pratique, compte tenu des réalités, « la gouvernance dans les Etats membres de l'OHADA signifie souvent tout autre chose. Il ne s'agit pas de la gouvernance des sociétés dans le sens classique, mais au contraire, de l'influence politique ». De fait, il se trouve qu'aujourd'hui, la zone OHADA souffre avant tout, non pas de l'absence de règles, mais de la persistance de graves faiblesses et d'un manque cruel en terme de gouvernance et de contrôle de la bonne application des règles de droit, notamment, vis-à-vis de l'entreprise. Au regard de cette situation, l'on est tenté de dire que l'application des règles et principes de la gouvernance d'entreprise reste quelque peu limitée ou n'a pas encore porté les fruits escomptés. Une gouvernance d'entreprise dans l'espace OHADA est-elle une illusion ? Le constat objectif est bien évidemment non. C'est donc au prisme des enjeux économiques actuels et, face aux nouvelles attentes et défis des Etats membres, des axes de convergences ne seraient possibles qu'en vertu du réalisme du droit de l'OHADA, qui doit concilier à la fois, impératif économique (besoin d'investissement) et sécurisation juridique et judiciaire des activités économiques (quête de sécurité juridique).Mots clés : OHADA (Organisation pour l'Harmonisation en Afrique du Droit des Affaires), Droit, Gouvernance, Entreprise, Acte uniforme. The issue of governance is not frozen in time. It remains current. The legislature of OHADA, was inspired by the debate born in Anglo-Saxon countries where a thorough reflection of the principles of corporate governance has developed with different approaches and sometimes even contradictory. This has thus led to lay down a number of rules governing commercial companies, the rules contained in the Revised Uniform Act relating to Commercial Companies and Economic Interest Group, effective May 5, 2014. even if the revised uniform Act does not specifically about corporate governance, it does not affect fewer mechanisms and rules. Thus, the objective of these rules is still well the establishment of an appropriate legal framework, conducive to development, investment and economic attractiveness of the area of ​​OHADA. Otherwise considered in this light, the objectives of the OHADA founding fathers were they achieved? Given multiple issues, even as commercial companies hardly escape the globalization of trade, this study, which is a contribution to the debate on improving the state of economic law, the legal and judicial security economic activities, will try to clarify the question of the effectiveness and efficiency of the regulatory system of governance of corporations. Thus, this work is to contribute to the reflection of a uniform regulatory governance rules of commercial companies in the area of ​​OHADA. In short, address the issue of governance of commercial companies in OHADA law is clear, finally, in this study, the issue of adaptability of the rules of this governance in the economic and social context of commercial companies OHADA space. From the analysis of the revised Uniform Act relating to commercial companies, the study deals in the first part, the question of whether the rules of governance of corporations. And, in a second part, I analyze the necessary changes in governance rules commercial companies.
Keywords: Acte uniforme; Africa; Afrique; Business law; Company; Droit; Droit des affaires; Entreprise; Gouvernance; Gouvernement d'entreprise; Governance; OHADA; OHBLA; Société commerciale; Uniform Act

La lex societatis en droit international des affaires - Youbo, Lou Bouinan Sonia (Université de Bordeaux, 2015)
La recherche de la loi applicable à la société, lex societatis, est incontournable carc’est de cette loi dont dépendront les règles de constitution, de fonctionnement et dedissolution de la société. Mais la problématique de la détermination de la lex societatis enDroit International des Affaires réside dans l’identification d’un mode adéquat derattachement des sociétés transfrontalières à un territoire national. Le caractère transfrontalierdes sociétés actuelles accentue le conflit entre les différents systèmes de rattachement dessociétés traditionnellement retenus par les législations. La pluralité de système derattachement des sociétés est à l’origine de conflits auxquels l’uniformisation de la règle deconflit de lois en matière de détermination de la lex societatis peut être une solution.Le droit des sociétés doit être un instrument au service des affaires, et non un frein àleur évolution et à leur développement. Ainsi pour répondre aux besoins des affairesinternationales, outre l’élimination des entraves aux échanges il faut envisager une adaptationdu contenu des règles de conflit de lois actuelles qui permettent la détermination de la lexsocietatis ainsi qu’une modification de leur source.
Keywords: Applicable law; Choice of law for companies; Conflict societies attachment systems; Conflit de lois; Conflit de systèmes de rattachement des sociétés; Conflits négatifs; Conflits positifs; Connecting factor; Corporate recognition; Critère de rattachement; Cross-border company; Droit OHADA; Droit européen; Droit international privé; Economic link; European law; Extraneous; Extranéité; Harmonisation; Harmonization; Incorporation; Lex societatis; Lien économique; Loi applicable; Mobilité des sociétés; Nationality of companies; Nationalité des sociétés; Negative conflict; OHADA law; Points de rattachement (droit international privé); Positive conflict; Reconnaissance des sociétés; Registered office; Siège social; Société commerciale; Société transfrontalière; Sociétés; Standardization; Uniformisation

L’apport de l’audit opérationnel interne dans la réduction des abus de la rémunération des dirigeants : Etude exploratoire dans les sociétés par action en Algérie - Belhachemi, Amina (Université Abou Bekr Belkaid, 2015)
تواجه حوكمة الشركات عدة مخاطر بالأخص فيما يتعلق بمسألة تعويضات المديرين التنفيذيين، و التي تتمثل اساسا في النزاعات القائمة بين المساهمين و المديرين التي قد تهدد كل مستويات الاداء و جودتها. في هذا الصدد تأتي استراتيجية حوكمة الشركات لضمان التوازن بين صلاحيات المساهمين ومسؤوليات المديرين التنفيذيين من خلال تحسين سير مختلف آليات المراقبة و تعزيزها. في هذا السياق، يأتي هدف هذه الأطروحة المتجسد في التركيز على اظهار مدى نجاعة التدقيق التشغيلي فى حوكمة الشركات، من خلال التدقيق في الكيفية أو الطريقة المتبعة في تحقيق الأهداف المتعلقة بتعويضات المديرين و بالتالي الحد من التلاعب و السلوكيات المنحرفة التي تعمل على حساب غيرهم من اصحاب المصلحة عموما و المساهمين على وجه الخصوص في شركات المساهمة بالجزائر . La gouvernance d’entreprise a toujours été confrontée à des aléas multiples et divers et notamment celui de la problématique de la rémunération des cadres dirigeants. Ceci, étant, dans un sens, où le risque de conflit d’intérêts entre ces derniers et les actionnaires, qu’il soit potentiel ou réel, peut menacer d’une façon ou d’une autre les niveaux de performance attendus. Ainsi, une stratégie de gouvernance d’une société par action doit nécessairement promouvoir, entre autre, une politique des équilibres entre les pouvoirs des actionnaires et les responsabilités des cadres dirigeants, tout en faisant valoir un bon fonctionnement des différents mécanismes des contrôles nécessaires. A ce titre, notre travail de recherche s’est focalisé, justement, sur l’audit opérationnel que nous avons jugé comme étant l’un des principaux moyens de contrôle qui puisse, à la fois, stimuler la dynamique de l’effort de gestion des cadres dirigeants à travers un contrôle sur leurs rémunérations qui risquent d’être abusives et contribuer à assurer un climat des affaires positif pour les actionnaires dans les sociétés par action en Algérie.

Concentração e dispersão do poder político nas organizações coletivas finalísticas. Regime jurídico da companhia aberta integrante do novo mercado da bolsa de valores: o papel decisivo desempenhado pelos instrumentos jurídicos de dissociação entre representatividade política e participação economica de acionistas no âmbito da companhia - Azevedo, Luís André Negrelli de Moura (Universidade de São Paulo, 2015)
Ao redor do mundo, a maioria das companhias listadas de grande porte tem acionista controlador, à exceção dos EUA e do RU, em que o comando da atividade empresarial é exercido, de fato, pelos administradores. A conformação de controle dominante em cada país resulta de uma série de fatores, muitos deles de ordem jurídica, os quais levam ao surgimento e permanência de uma dessas variantes, ao mesmo tempo em que parecem inibir o desenvolvimento da estrutura alternativa. A gradativa convergência global dos padrões de propriedade acionária a um denominador comum, aparentemente em curso - dos extremos da dispersão e concentração absolutas para o cenário intermediário dos blocos de participação minoritária relevante detidos por investidores institucionais não tem sido acompanhada de transformações significativas nas estruturas de poder de controle interno dominantes em cada país, as quais, em essência, continuam as mesmas. Isso significa que os fatores (jurídicos, especialmente) que levam à predominância de tais estruturas continuam em atuação, não obstante modificações havidas no grau de dispersão do capital com direito a voto de companhias listadas. Este trabalho visa apresentar um conjunto mais específico de fatores jurídicos que, ao mesmo tempo e de modo decisivo, favorecem a proliferação de uma dentre as duas estruturas de controle consideradas (controle acionário ou gerencial) e inibem o desenvolvimento de outra. Trata-se dos instrumentos jurídicos de dissociação entre representatividade política e participação econômica de acionistas, os quais exercem papel central na conformação do regime jurídico das companhias abertas com elevada dispersão do capital votante, integrantes do Novo Mercado da BVSP. Most of the large listed companies outside USA and UK have a controlling shareholder. The dominant control structure in each country is the result of multiple determinants, many of them arising from the legal system. The gradual convergence of ownership patterns around the world from the extremes of the total concentration and separation of ownership and control to the intermediate scenario of significant blockholdings held by institutional investors - has not been accompanied by a relevant shift in the control structures in listed companies of most of the countries, specially those in the Brazilian Novo Mercado. This Doctorate Thesis presents a specific subset of legal factors contributing for that outcome: the legal instruments separating voting rights from cashflow rights.
Concentration et dispersion du pouvoir politique au sein d'organisations collectives aux objectifs spécifiques. Régime juridique de l'entreprise publique intégrée au nouveau marché boursier : le rôle déterminant des instruments juridiques de dissociation entre représentation politique et participation économique des actionnaires au sein de l'entreprise.
Keywords: Capital markets law; Cash-flow rights; Companhia aberta; Controle acionário; Corporate law; Legal instruments; Listed companies; Mercado de capitais; Ownership and control structures; Sociedade comercial; Voting rights

A admissibilidade e a conveniência da exclusão do controlador em S.A. - Prado, Maria da Glória Ferraz de Almeida (Universidade de São Paulo, 2015)
O estudo refere-se à verificação da admissibilidade e da conveniência da exclusão facultativa de acionista controlador em sociedade anônima. O tema não é propriamente novo no Brasil. Intenciona-se, no entanto, construir a hipótese a partir de fundamento legal diferente. A Lei 6.404/76 (LSA) apenas destina a exclusão para casos de acionista remisso (artigo 107, II), permanecendo silente com relação ao inadimplemento de deveres de colaboração e lealdade (em conjunto, deveres de cooperação). Nesse contexto, a doutrina e a jurisprudência brasileiras tendem a admitir a hipótese de exclusão em tais casos por aplicação do artigo 1.030 do Código Civil, destinado a regular a matéria no âmbito das sociedades simples. Para tanto, aproximam a companhia fechada das sociedades de pessoas a fim de justificar, dada a alegada omissão da lei especial a esse respeito, o tratamento por analogia. A partir do estudo sistemático da LSA, que compreende, entre outros, o entendimento do princípio da circulação de ações e da extensão dos deveres de boa-fé entre os sócios, pretende-se admitir a hipótese com base na própria lógica acionária, em razão da eventual relevância do relacionamento societário para a consecução do fim social. Em tais companhias, o adimplemento dos deveres de cooperação torna-se tão imprescindível quanto o adimplemento do dever de conferimento para o alcance do escopo comum. Em decorrência desse raciocínio, a exclusão torna-se admissível na ocorrência de inadimplemento de qualquer dever social que inviabilize, real ou potencialmente, o preenchimento do fim social. A identificação de eventual affectio societatis entre os acionistas, portanto, passa a ser irrelevante. Admitir a hipótese no que se refere a acionista controlador se revela ainda importante instrumento de limitação do exercício ilegítimo do poder de controle e não se confunde com a sanção de perdas e danos prevista na LSA por abuso de poder de controle. Por fim, será analisada a conveniência da exclusão do controlador, em razão de sua relevância pessoal para a consecução da atividade, a participação societária por ele detida e da possibilidade de dissolver-se parcialmente a sociedade, com a saída do acionista minoritário descontente.
Keywords: Acionista majoritário; Controlling shareholder; Corporate law; Corporation; Dirigeant social; Exclusion; Sociedade anônima; Société Anonyme

Sociedades anônimas fechadas: direitos individuais dos acionistas e cláusula compromissória estatuária superveniente - Silva, Rodrigo Tellechea (Universidade de São Paulo, 2015)
A tese propõe uma análise multidisciplinar e dogmática da arbitragem societária, notadamente do processo de inclusão de cláusula compromissória no estatuto social de sociedades anônimas fechadas, com base em uma deliberação assemblear tomada pela regra da maioria (fase pré-arbitral). O ponto de partida do trabalho é o exame da dimensão jurídica do contrato de sociedade aliado à verificação dos limites da autonomia privada dos sócios na definição da estrutura do negócio jurídico societário, à compreensão da categoria dos direitos subjetivos e dos traços fundamentais que formam a tipologia das anônimas fechadas, incluindo o tratamento dado aos direitos individuais dos acionistas. Ato contínuo, desloca-se a discussão para as esferas arbitral e constitucional, com especial atenção para os pressupostos da arbitragem como método de resolução de conflitos. O cerne do trabalho reside na relação entre a situação subjetiva ativa do acionista de manifestar sua vontade favorável ou contrariamente à escolha da arbitragem e a eficácia da regra da maioria como pilar de funcionamento das sociedades anônimas. Sustenta-se que a escolha da arbitragem constitui um direito fundamental de todo o acionista, cuja renúncia depende de manifestação, expressa ou tácita, de sua vontade, a qual não pode ser elidida ou alterada pelo estatuto ou pela assembleia geral majoritária sem o seu consentimento. Após examinar as correntes doutrinárias sobre o tema no Brasil e as possíveis alternativas para resolver o imbróglio, o estudo concluiu que a alteração legislativa que cria uma hipótese adicional de recesso representa a melhor solução para a problemática. The thesis examines arbitration in corporate law, namely the inclusion of a statutory arbitration clause in the by-laws of a closely held corporation based on a deliberation taken by the majority rule (pre-arbitration phase). The study starts by analyzing the legal aspects of the corporate contract together with the limits of shareholders autonomy in defining the structure of such contract and the characteristics that form the typology of corporations, including shareholders individual rights. The discussion then moves on the arbitration and constitutional spheres, particularly to the premises of arbitration as a form of settling conflicts. The core of the thesis is the relation between the prerogative of a shareholder to express its will in favor of or against arbitration and the incidence of the full effects of the majority rule as an essential element in the structure of a corporation. The study sustains that the choice for arbitration is a fundamental right of all shareholders, which is why renunciation depends on their express or tacit individual manifestation and therefore, majority deliberation cannot in itself insert or remove it from by-laws. Finally, the thesis provides different scholars understandings on the issue as well as the main possible alternatives to dealt with it. The creation of an additional hypothesis of appraisal right within the existing law is suggested as the best solution to solve this conundrum.
Keywords: Acionista majoritário; Actionnaire; Appraisal right; Arbitrage; Arbitragem; Arbitration; Clause d'arbitrage; Cláusula compromissória; Contrato comercial; Contrats commerciaux; Corporate contract; Corporations; Majority rule; Shareholders autonomy; Shareholders individual rights; Sociedade anônima; Société Anonyme; Société à capital fermé; Statutory arbitration clause

Suspensão do exercício de direitos do acionista - Mussi, Luiz Daniel Rodrigues Haj (Universidade de São Paulo, 2015)
O tema desenvolvido na tese diz respeito à suspensão do exercício de direitos do acionista, por deliberação da assembleia geral, na hipótese de descumprimento de determinados deveres societários pelo sócio. A suspensão de direitos tem como fundamento legal os artigos 120 e 122, V, da Lei n. 6.404, de 15 de dezembro de 1976 (Lei de Sociedades Anônimas). Não há previsão legal homóloga em direito comparado. No Brasil, a temática não foi objeto de estudo monográfico específico e detalhado. A tese procura, assim, sistematizar a matéria e oferecer contribuição original para o desenvolvimento do tema investigado. Na primeira parte, apresenta-se o tratamento normativo em matéria de suspensão de direitos do acionista a partir de escorço histórico da legislação brasileira e analisam-se os fundamentos teleológico e dogmático do instituto. A segunda parte estrutura-se em torno das posições jurídicas subjetivas passivas e ativas do acionista. Identificam-se, nesse contexto, quais são os deveres do acionista que, uma vez violados, constituem-se como hipótese de aplicação do art. 120 da Lei de Sociedades Anônimas e quais direitos, poderes e faculdades podem ter o seu exercício suspenso pela assembleia. Na terceira e última parte são destacados os aspectos controvertidos em torno da assembleia geral na qual se pretende deliberar sobre a suspensão dos direitos do acionista. Em especial, os problemas vinculados à competência privativa da assembleia, ao método assemblear e aos efeitos da deliberação e o controle desta.
Keywords: Acionista; Actionnaire; Annual meeting; Assembleia geral; Assembly method; Incompliance; Joint-stock company; Legal duties; Shareholders; Sociedade anônima; Statutory duties; Suspension of the exercise of rights

Le nouveau droit de la restructuration des sociétés commerciales des pays de l'OHADA, comparaisons avec le droit français - Ahoua, Désiré (Université de Bordeaux, 2015)
Dans un contexte de mondialisation, les entreprises africaines doivent s'adapter en permanence aux diverses contingences économiques, juridiques ou sociales. Conscient de cette réalité, le législateur africain a mis en place dans le cadre de la reforme de l'OHADA, un arsenal juridique afin de leur permettre de s'acclimater en permanence aux tendances et pressions du marché : le droit de la restructuration qui désigne l’ensemble des techniques conçues par le législateur pour réorganiser l’entreprise. Ces techniques ont eu pour source d’inspiration le droit français des restructurations qui a connu des mutations. La confrontation des deux systèmes de droit permet de constater que si dans les principes fondamentaux les deux systèmes répondent aux mêmes objectifs à savoir assurer la pérennisation des entreprises par la promotion de la croissance de l’entreprise et sa survie lorsqu’elle est le seuil de difficultés diverses, il existe toutefois des différences d’ordre pratique et technique consécutives aux dernières réformes intervenues.
Keywords: Augmentation de capital; Bankruptcy; Conversion de créance en capital; Corporate law; Debt equit swap; Droit des sociétés; Fusion; Increasing of shares; Insolvency; Merger; Organisation pour l'harmonisation en Afrique du droit des affaires; Plan de restructuration; Restructuring plan; Règlement préventif; Sauvegarde

L’Application des textes de l’OHADA aux entreprises publiques: l‘exemple de l’AUSC et GIE - Boukari, Salifou (Maastricht University, 2015)
Without a precise definition either legally or on the judicial basis, public company owes its name through the participation of public power in its capital. Also, one has to make it clear that the concept of public power is not itself very clear. It is estimated that the state which became a shareholder and guarantor of social interest. The public company is regarded as the one which belongs wholly to the state and at the same time enjoying autonomy, cannot have its "survival" thanks to a law adapted to its nature and a good organization bodies that comprise it. Thus, it can only work function if the tasks to be performed by the corporate bodies are distributed accurately and if the roles in the public company are clearly defined by law. OHADA legislators did not hesitate to submit to the public company the Uniform Act related to commercial enterprises (AUSC) and Economical interest groups (GIE). But public behind it is, ever so slightly, an obstacle to its strict submission of AUSC and Economical interest group. Hence, a necessary approximation of national and community by coordinating legal systems. This implies interdependence between the provisions of the Uniform Act related to commercial enterprises and the Economical interest groups and those from national laws. The two national legal systems remain autonomous and do not influence each other. The results are in OHADA space textual duality to meet the demands of commercial enterprise, with the base and mark of the Uniform Act related to commercial enterprises and the Economical interest group; national texts playing a complementary and subsidiary role.
Keywords: AUSCGIE; corporate bodies; national legal systems; public company shareholder; social interest; state governing bodies

Anonim şirketlerde pay devrinin sınırlandırılması (Bağlam) - Bozkurt, Tamer (Ankara Üniversitesi, 2015)
Anonim şirkette geçerli temel ilkelerden birisi, pay devrinin serbestliği ilkesidir. Anonim şirkette üyeliği temsil eden paylar, serbestçe devredilebilir ve miras yoluyla geçişe konu olabilir. Yeni dönemde, İsviçre Hukuku'nu takip eden TTK, pay devri sınırlamalarını "borsaya kote edilmiş" ve "borsaya kote edilmemiş" paylar üzerinden kurgulamıştır. Borsaya kote edilmemiş paylarda bağlam, gerçek bir devir sınırlamasıdır ve şirket devre onay vermeden, işlem geçerlilik kazanamaz. Ayrıca onay olmadan, payı devralan müktesibe, hiçbir hak geçmez. Kanun şirkete üç red nedeni vermiştir. Birincisi, şirket sözleşmesine yazılacak "önemli nedenler," ikincisi esas sözleşmede bir devir sınırlaması iradesi olmak kaydıyla, uluslararası literatürde "kaçınma klozu" olarak geçen "Escape-Clause" ve inançlı iktisaba karşı korunmadır. Borsaya kote edilmiş paylarda ise TTK ve SPKn. devrededir. TTK'da, borsaya kote edilmiş paylarda sadece "yüzdelik sınırlama"ya izin verilmekte ve payın geçişi ile birlikte (borsa dışı iktisapta bildirim), katılım hakları hariç, diğer haklar müktesibe intikal etmektedir. Bu paylar, yasal yolla intikal ettiğinde ise (miras, miras paylaşımı, cebri icra veya eşler arası mal rejimleri hükümleri), şirket müktesibi tanımak zorunda kalmaktadır. Buna karşılık, SPKn.'nın 137/3. maddesi gereğince şirket, borsada gerçekleşen işlemler sonucu payı edinen kişiyi, pay defterine kayıttan kaçınamaz. Bu tercih tartışmalar getirebilecektir. Özellikle borsa şirketlerinin kendini bağlamla koruyamayacak olmaları ile borsanın yapısına uygun olarak "mutlak devredilebilirlik" arasındaki çatışmanın sonuçlarını ilerleyen yıllar gösterecektir. Bağlam, anonim şirket düzeni ile temelde çatışan bir kurumdur. Ancak şirketin yabancılaşmaya karşı veya kendine özgü niteliklerinin korunması bakımından yararlıdır. Ancak bağlamın yasadaki düzenleniş şekli, devrin fiilen (de facto) engellenmesi şekline bürünmemelidir. Buna rağmen şirket düzeni ile temelde çelişki yaratan bir kurum olan "bağlam" ile ilgili tartışmalar, hiçbir zaman bitmeyecektir. One of the main respected principles in stock companies is the principle of transferability of shares. Shares representing membership in a stock corporation shall be freely transferred and inheritted. According to this principle each shareholder may depart from the stock company by transferring his/her share/shares principally whenever he wants. The Turkish Commercial Code based on Swiss Law regulated restriction of transferability as "Listed registered shares" and "Not listed registered shares". Restriction on transferability in "Not listed registered shares" is an exact restriction. Because where the consent required for transfer of shares is not given, the ownership of the shares and all attendant rights remain with the alienator (Turkish Commercial Code, Art. 494/1). Listed registered shares are regulated in both The Turkish Commercial Code and the Capital Market Law. In the case of listed registered shares, the company may refuse to accept the acquier as a shareholder only where the articles of association envisage a percentage limit on the registered shares for which an acquirer must be recognised as shareholder and such a limit is exceeded. But according to the art. 137/3 of Capital Market Law a stock corporation can not refrain from registering a shareholder who acquired listed registered shares to share register. Especially is protection of a stock corporation itself against hostile take-over by means of "restrictions on transferibility" important or absolute transferibility which is appropriate for the structure of stock-exchange? The results of the art. 137/3 of Capital Market Law will occur in the future.
Tez N° 425406
Keywords: Anonim ortaklıklar; Anonim şirketler; Commercial law; Incorporated companies; Joint stock company; Pay devri; Restrictive provisions; Sınırlayıcı hükümler; Ticaret hukuku; Transfer of shares; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Anonim ortaklıkta ayni sermaye - Çonkar, Mustafa Halil (İstanbul Üniversitesi, 2015)
Tez N°451645
Keywords: Anonim ortaklıklar; Anonim şirketler; Ayni haklar; Capital; Capital companies; Commercial companies; Commercial law; Incorporated companies; Joint stock company; Real rights; Sermaye; Sermaye şirketleri; Ticaret hukuku; Ticari şirketler; Turkish commercial law; Türk ticaret hukuku

Limited ortaklıklarda ortakların ek ödeme ve yan edim yükümlülükleri - Di̇nç, Serhan (Gazi Üniversitesi, 2015)
Bu çalışmanın amacı, 6102 sayılı Türk Ticaret Kanunu sistemi ile limited ortaklıklar hukukuna getirilen iki yeni müessesenin incelenmesidir. Ek ödeme ve yan edim yükümlülükleri incelenmiştir. Ortak, ortaklık, pay senedi, limited ortaklık sözleşmesi, esas sermaye, esas sermaye payı, bilânço, bilânço açığı, zarar, zararın kapatılması, edim, yükümlülük, ek finansman araçları, ortaklıktan çıkma ve çıkarılma kavramları ışığında ek ödeme ve yan edim yükümlülüklerinin bu kavramlarla irtibatı açıklanmıştır. Bu incelemeler sonucunda ek ödeme ve yan edim yükümlülüklerinin ülkemizde limited ortaklıkların ticaret hayatında yer edinebilmelerini ve gelişmesini temin edecek faydalı hukuki müesseseler olduğu tespit edilmiştir. Anahtar Sözcükler 1. Limited Ortaklıklar 2. 6102 sayılı Türk Ticaret Kanunu 3. Yükümlülük 4. Ek Ödeme Yükümlülüğü 5. Yan Edim Yükümlülüğü. The main purpose of this thesis is to research the new two concepts which were ordered by the system of new Turkish Commercial Code numbered 6102. In this thesis, the concepts of supplementary obligation of subscription and obligation of fulfilment were researched. The relationships between the concepts of supplementary obligation of subscription and obligation of fulfilment and the shareholder, limited company, certification of share, contract of limited company, capital, balance, deficit of balance, damage, annihilation of damage, fulfilment, obligation, departation and taking off were explained. The results of these research shows us that the concepts of supplementary obligation of subscription and obligation of additional fulfilment are beneficial concepts which are useful and necessary for surviving and developing materials for limited companies in Turkish business life. Key Words 1. Limited Companies 2. Turkish Commercial Code numbered 6102 3. Obligation 4. Supplementary Obligation of Subscription 5. Obligation of Additional Fulfilment
405733
Keywords: Ek ödeme sistemi; Limited company; Limited şirketler; Obligation; Obligation of additional fulfilment; Ortaklar; Ortaklık; Ortaklık hakkı; Partners; Partnership; Partnership right; Supplementory payment system; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yan edim yükümlülüğü; Yükümlülük

Anonim şirketin haklı sebeple feshi - İlbasmiş Hizlisoy, Özlem (Ankara Üniversitesi, 2015)
413801
Keywords: Anonim ortaklıklar; Anonim şirketler; Azınlık hakları; Cancellation; Cancellation right; Fesih; Fesih hakkı; Haklı neden; Incorporated companies; Joint stock company; Just cause; Minority rights; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Anonim şirketlerde örtülü kâr dağıtımı - Karslioğlu, Hasan (Gazi Üniversitesi, 2015)
Anonim şirket pay sahiplerinin temel amacı, şirkete koydukları sermaye karışlığında kâr elde etmek ve bu elde ettikleri kârı artırmaktır. Kâr dağıtımı ve şartları genel olarak Türk Ticaret Kanunu'nda düzenlenmiş olup, uygulamada da kâr dağıtımı bu düzenlemelere göre yapılmaktadır. Ancak vergi kanunlarında ve uygulamasında, Ticaret Kanunu'ndaki bu düzenlemeler dışındaki bazı ödemeler için de "örtülü kâr" nitelendirmesi yapılmıştır. Örtülü kâr dağıtımı konusu, genellikle vergi hukukçuları tarafından ele alınan bir konu olup, bu konu şimdiye kadar kâr payının temel unsurlarının düzenlendiği ticaret hukuku açısından detaylı olarak ele alınmamıştır. Bu nedenle hem vergi kanunları, hem de Türk Ticaret Kanunu kapsamında kâr dağıtımının, hangi hallerde örtülü olduğunun ele alınması gerekmektedir. Bunun yanında Sermaye Piyasası Kanunu'nda örtülü kâr dağıtımına benzer uygulamaların olup olmadığı ve halka açık anonim şirketler açısından konunun öneminin de ortaya konulması, meselenin daha net ele alınmasını sağlayacaktır. Çalışmamızda bu amaca yönelik tespitler yapılmış olup, konu tüm yönleri ile ele alınmıştır. İncelemelerimiz sonucunda; vergi kanunlarında "örtülü kâr" olarak nitelendirilen haksız menfaat ödemelerinin, Ticaret Kanunu'ndaki "kâr payı" düzenlemeleri ile açıkça çeliştiğini değerlendirmekteyiz. Bu nedenle vergi güvenliği amacıyla yapılmış da olsa "örtülü kâr dağıtımı" nitelendirmesinin ticaret hukuku genel ilkeleri ile çeliştiği tespitinde bulunduk. Çalışmamızda bu değerlendirmenin gerekçelerini ortaya koymaya gayret ettik. The principal purpose of the shareholders in a joint-stock company is to get profit in consideration of the capital provided and to increase the level of such profit. The profit distribution and the relevant conditions are defined in the Turkish Commercial Law in general and the profit distribution in practice is performed according to these stipulations. However, there is the term i.e. "concealed profit" for some payments in the tax laws and practice apart from these stipulations in the Commercial Law. The concealed profit distribution is a subject that is generally handled by the tax jurists and this subject has not been studied in detail so far in terms of trade law where the main factors of the dividend are defined. For this reason, it is necessary to study on the cases where the profit distribution is deemed ad "concealed" within the scope of both tax laws and Turkish Commercial Law. Besides, whether there are similar practices to the concealed profit distribution in the Capital Markets Law and putting forward the importance of this subject in terms of the public joint-stock companies will enable to handle the subject more clearly. The determinations for this purpose are provided in our study and this subject is handled in all aspects. As a result of our analysis, we have revealed that the unjust interest payments characterized as "concealed profit" in the tax laws are clearly in conflict with the stipulations of "dividend" in the Commercial Law, and therefore, "concealed profit distribution" conflicts with the general principles of trade law even though it is performed for tax safety. We have tried to put forward the justifications of this evaluation in our study.
Tez N°384579
Keywords: Anonim şirketler; Camouflage of earning distribution; Dağıtım; Distribution; Droit des sociétés commerciales; Joint stock company; Kar dağıtımı; Profit distribution; Örtülü kazanç dağıtımı

Anonim ortaklıkta şirkete borçlanma yasağı - Toraman Çolgar, Emek (İstanbul Üniversitesi, 2015)
Çalışmamız, 6102 sayılı Türk Ticaret Kanunu'nda ilk kez düzenlenen anonim ortaklıkta şirkete borçlanma yasağını konu edinmektedir. Anılan yasak, pay sahipleri için TTK m. 358'de, pay sahibi olmayan yönetim kurulu üyeleri içinse TTK m. 395'te düzenlenmiştir. Her iki hüküm de Türk hukukuna özgüdür ve Kanun'da yalnızca ana hatları ile düzenlenmiştir. Bu nedenle çalışmada, düzenlemelerin kapsamı, istisnaların sınırı ve yasağa aykırılığın sonuçları incelenmiş ve değerlendirilmiştir. The subject matter of this thesis is the prohibition to be indebted to the company in the form of a joint stock partnership, which has been regulated in the Turkish Commercial Code for the first time. Said prohibition is regulated in the article 358 of TCC for shareholders and in the article 395 for the board of directors who are not a shareholder. Both provisions are unique to Turkish law and introduced with their essential points only. Therefore in this thesis, the scope, limitation of exceptions and the consequences of the breach of the prohibition are analysed and assessed.
422225
Keywords: Anonim şirketler; Borrowing; Borçlanma; Borçlanma yönetimi; Company law; Debt management; Joint stock company; Kanunlar 6102 sayılı; Laws 6102 numbered; Prohibitions; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yasaklar; Şirketler hukuku

Protection de l’entrepreneur individuel et droits des créanciers : étude comparée droit français - droit de l’OHADA - Diallo, Abdoulaye (Université de Poitiers, 2014)
Au regard du principe de l'unité du patrimoine, l'entrepreneur individuel engage tout son patrimoine. En cas de survenance de difficultés, ses créanciers pourront saisir ses biens professionnels et ses biens personnels. Cette responsabilité illimitée de l'entrepreneur individuel peut avoir des conséquences redoutables, notamment lorsqu'il est marié ou pacsé ou vivant en concubinage. Cette fragilité de l'entrepreneur individuel a poussé le législateur, aussi bien en droit français qu'en droit de l'OHADA, à créer des mécanismes lui permettant de mettre son patrimoine personnel à l'abri de la poursuite de ses créanciers professionnels. Ainsi, en dehors de toute affectation sociétaire, l'entrepreneur individuel peut, désormais, en droit français, soustraire ses biens personnels du droit de gage de ses créanciers professionnels, par le biais de la déclaration notariée d'insaisissabilité ou par le recours au statut de l'EIRL. Également, par le jeu des régimes matrimoniaux ou de la technique de la fiducie, il peut limiter les droits de ses créanciers. Cependant, l'efficacité des mécanismes de protection de l'entrepreneur individuel n'est pas absolue. En effet, elle est souvent remise en cause par les créanciers antérieurs, et même par l'entrepreneur individuel qui peut y renoncer, parfois dans le but d'obtenir du crédit. En outre, lorsque l'entrepreneur individuel est soumis à une procédure collective, l'efficacité des mécanismes de protection n'est que relative. Le cloisonnement des patrimoines recherché ou la soustraction de certains biens personnels du gage des créanciers est remis en cause. Dès lors, la protection qu'offrent ces mécanismes n'est que illusoire, d'où la nécessité de renforcer leur efficacité. A défaut de mécanismes de protection efficaces, l'entrepreneur individuel peut recourir aux différentes procédures de prévention comme alternative aux mécanismes de protection.
Keywords: Droit comparé; Droit de gage des créanciers; Débiteur et créancier; Déclaration notariée d'insaisissabilité (DNI); Entrepreneur individuel à responsabilité limitée (EIRL); Entreprises individuelles; Fiduciary transfer of amounts of money; Fiducie; Individual Entrepreneur with Limited Liability (EIRL); Lienholder rights; Notarized declaration of non-Seizability; Over-Indebtedness procedures; Patrimoine d'affectation; Patrimoine fiduciaire; Procédures de surendettement; Special purpose assets; Transfert fiduciaire de sommes d'argent; Trust; Trust patrimony

Les privatisations en Tunisie - Noomane-Bejaoui, Dorra (Université Paris-Dauphine, 2014)
La Tunisie n’a pas échappé au mouvement universel de privatisation. Sous l’effet conjugué du poids de ses entreprises publiques, et de la dette extérieure et de la conditionnalité des bailleurs de fonds internationaux (Banque Mondiale et FMI), la Tunisie s’est engagée dans un vaste programme de privatisation. Cet ouvrage cerne les objectifs, les modalités et les enjeux qui accompagnent le processus de privatisation tunisien, en le comparant à la mise en œuvre du programme français de privatisation. Dans une seconde partie, l’étude présente les alternatives possibles aux privatisations, particulièrement les partenariats public-privé, largement diffusés de nos jours.
Keywords: Actionnariat public; Corporate governance; Entreprises privatisées; Entreprises publiques; Gouvernement d'entreprise; Nationalisation; Partenariat public-privé; Privatisation; État actionnaire

The position of the whistle-blower in South African law - Isparta, Louise Dorothy (University of South Africa, 2014)
The position of the whistle-blower is known to be a precarious one, with the whistle-blower often either regarded as a hero or a reprehensible traitor. Various pieces of legislation have attempted to remedy their precarious position, especially within the employment relationship, and in which the whistle-blower more often than not has the most to lose. The study at hand has the specific objective of comparing the position of the whistle-blower in terms of South African Law, against 16 specific measurables, and in comparison with the position of the whistle-blower in New Zealand, Australia (Victoria) and the United Kingdom. In the main, the protection offered to the whistle-blower within the South African context, is embodied within the Protected Disclosure Act 26 of 2000 (hereinafter referred to as the “PDA”).In examining the protection afforded to the whistle-blower in South Africa, it is concluded that the framework involved extends much further than just the mere provisions in the PDA. However, there are admitted challenges in respect of this framework as discussed, both legislative and non-legislative, especially in respect of duties of disclosures placed on persons in circumstances in which concurrent protection is not afforded to the whistle-blower. With reference to the comparison in respect of the measurement parameters set, it was found that the PIDA (UK) meets the least amount of the measurements set, with the PDA A (Australia, Victoria) meeting the most of the measurements; the PDA NZ is equally balanced in meeting and not meeting the measurements and the PDA meeting less of the measurements than not, but still meeting more than the PIDA. It was found that had it not been for the catch-all provision contained in section 4 (1) (b) of the PDA, the PDA would have ranked last.
Keywords: Disclosure of information; Lanceur d’alerte; Protected Disclosure Act; Protected disclosure; Public Interest Disclosure Act; Whistle blowing; Whistle-blower

Complex ownership structures, banks' capital structure and performance - Zedek, Nadia (Université de Limoges, 2014)
Cette thèse examine l’impact de la structure actionnariale sur la structure du capital et la performance des banques commerciales européennes sur la période 2002-2010. Elle est composée de trois essais empiriques. Le premier chapitre teste l'effet de la divergence entre les droits de contrôle et les droits pécuniaires d'un actionnaire ultime sur l’ajustement du ratio du capital à son niveau optimal et sur l’offre de crédit par les banques. Les résultats montrent qu’en présence de divergence entre les droits de contrôle et les droits pécuniaires, les banques n’émettent pas du capital pour augmenter leur ratio et, au contraire, elles réduisent leur taille en ralentissant leur offre de prêts. Le chapitre 2 teste l’effet de cette divergence sur la rentabilité et le risque bancaires en temps normal et en temps de crise. Les résultats montrent que bien qu'une divergence entre les droits de contrôle et les droits pécuniaires soit associée en temps normal à une rentabilité plus faible et un risque plus élevé elle a, à contrario, amélioré la rentabilité et contribué à la résilience des banques pendant la crise financière de 2007-2008. Le troisième chapitre teste si le réseau des actionnaires auquel la banque est liée au sein d’une chaîne de contrôle affecte la relation entre la diversification et la performance. Les résultats montrent que la présence des investisseurs institutionnels dans les chaînes de contrôle aide les banques à tirer des bénéfices lorsqu’elles diversifient leurs activités.
Keywords: Actionnariat; Banques; Banques européennes; Capital; Capital Structure; European Banking; Ownership; Structure du capital

El protocolo familiar mortis causa - Cucurull Poblet, Tatiana (Universitat Internacional de Catalunya, 2014)
La disciplina de la empresa familiar ha dado lugar a numerosos pronunciamientos doctrinales en el ámbito del Derecho. Sin embargo, y aunque este tipo de entidades tienen un gran impacto sobre la economía de un país, no existe una legislación específica que regule sus necesidades. Este tipo de empresas se diferencian del resto, como bien indica su nombre, por su componente ¿familiar¿. Tal atribución caracteriza su esencia y peculiaridad, como, a su vez, la problemática que sufren. De ello deriva la necesidad de tratarlas de una forma concreta y diferenciada. No existe ningún texto legal que defina de una manera clara e inequívoca qué debe entenderse por empresa familiar. Por ello, se examina de manera separada los dos conceptos que la componen: empresa y familia, estableciendo los parámetros que delimitan su ámbito de aplicación. Igualmente se conjugan las normas que, de alguna forma, se refieren a ellas. Consecuencia de su indefinición legal provoca que estas entidades deban adaptarse a la legislación existente conforme a su forma jurídica. De este modo, carecen de una regulación suficiente para solventar los conflictos que surgen de la combinación de los valores de la familia y la entidad propios de este tipo de organizaciones. Concretados los parámetros que permiten delimitar y definir la naturaleza de estas entidades, el estudio se centra en la transmisión intergeneracional de las empresas familiares. Este trance supone el principal motivo de su desaparición. Conciliar la relación entre empresa y familia no siempre resulta sencillo. Los problemas propios que derivan de esta situación, conducen a realizar un análisis detallado del denominado protocolo familiar. Este documento, propio de tal tipo de entidades, tiene por objeto la satisfacción de las necesidades específicas no cubiertas por la legislación. El protocolo familiar establece el marco en el cual deben desarrollarse los tres pilares fundamentales que componen esta tipología de entidades: familia, propiedad y empresa. De esta forma abarca no solo aquellas circunstancias económicas, patrimoniales y de organización, sino también los valores propios de la familia que se quieren reflejar en la entidad. Su contenido está compuesto por un conjunto de acuerdos adoptados por los integrantes de la empresa en cuestión, que incorporan una serie de principios y reglas. Estos son tanto de contenido moral como jurídico, y servirán de guía de actuación para la entidad familiar. Armonizar y dar contenido jurídico a las necesidades tan dispares que conviven en esta clase de organizaciones es el principal objetivo del presente estudio. La finalidad es hallar una fórmula concreta que garantice el éxito de la transmisión generacional. A pesar de que el protocolo haya sido elaborado a través de un proceso de diálogo y culmine en el consenso de todos los firmantes sobre sus cláusulas, no comporta garantía de cumplimiento por parte de quienes lo suscriben. Una vez abierta la sucesión, y cuando el protocolo deba desplegar sus efectos, se advierte que este documento por sí mismo no será suficiente para lograr tal fin. Para ello será necesario contar con la ayuda de otros instrumentos jurídicos, que también son estudiados en profundidad: los estatutos sociales; la importancia en la elección del régimen económico matrimonial al que deben someterse tanto los intervinientes como sus futuros sucesores; así como el testamento. Por último, y al ser las cuestiones sucesorias las más sensibles de tratar en la elaboración del protocolo familiar, se procede al estudio de una serie de figuras jurídicas que adquieren especial relevancia en la cuestión: el usufructo universal a favor del cónyuge viudo; la fiducia sucesoria y la sucesión contractual. Asimismo, también se ha realizado un estudio comparado de dos figuras jurídicas de Derecho francés. En concreto, la renuncia anticipada a la acción de reducción de liberalidades por lesión a la reserva, así como la donation-partage. Ambas son figuras propias de una legislación muy próxima a nuestro entorno jurídico y social, que podrían constituir una alternativa eficaz para la transmisión de las empresas familiares, si éstas pudiesen ser incorporadas en nuestra legislación.
https://www.tdx.cat/handle/10803/386452
Keywords: Derecho; Derecho Mercantil; Derecho civil; Empresa familiar; Entreprise familiale; Protocolo familiar; Successions; Sucesiones

Human capital disclosure in corporate annual reports - Adelowotan, Michael Olajide (University of South Africa, 2014)
It is generally acknowledged that human capital intangibles are major value drivers in the new economy characterised by information and technology. The main purpose of this study is to examine the extent to which companies listed on the Johannesburg Stock Exchange disclose information on human capital related issues. The study combined both qualitative (literature reviews and content analysis) and quantitative (survey questionnaire) methods to collect data of 60 corporate annual reports (CARs) of listed companies in South Africa from survey questionnaires administered on various categories of preparers and users of these CARs. The study made use of 91 human capital disclosure checklists developed from literature reviews for the purpose of data collection. The data analysis was done with the aid of Atlasti-a qualitative data analysis software and SPSS- a quantitative data analysis software. The findings show that majority of the items on the disclosure checklist are not yet disclosed in the CARs even though most of the items on the checklist are adjudged to be useful for organisational value creation. In view of the initial findings of this study, a human capital disclosure framework is recommended.
Keywords: Annual report; Corporation reports; Discretionary disclosures; Human capital; Human capital disclosure framework; Intangible assets; Intangible property; Intellectual capital; Mandatory disclosures; Personnel management

La notion de fruits : étude de droit privé - Jaoul, Mélanie (Université Montpellier 1, 2014)
La notion de fruits est une notion qui souffre d'un manque de modernité. Présente dans de nombreux articles du Code civil, la notion de fruits joue un rôle central sur le plan conceptuel mais semble cantonnée aux seconds rôles dans la pratique. Ce paradoxe a été rendu possible car la notion n'a ni définition pertinente, ni critères de qualification efficients. Ce travail met en exergue l'ensemble des vices de construction qui affectent la notion que ce soit sur la définition ou sur le régime. Ces défaillances sont le résultat d'une construction par sédimentation de la notion qui n'a jamais fait l'objet d'une réfection d'ensemble. Une fois le constat dressé, nous avons donc tenter de proposer une modernisation de la notion de fruits mais aussi de ses catégories. Dans ce but, nous avons purgé la notion de ses « scories » liées à une conception agraire. En se recentrant sur le bien frugifère, les modalités de naissance des fruits et leur destination à l'autonomie juridique, nous avons tenté de mettre en exergue qu'il s'agissait d'une notion transitoire, dont l'existence est « à durée très limitée ». Une fois l'ébauche d'un renouveau de la notion de fruits achevée, il semblait indispensable de mettre en avant l'utilité d'une telle démarche. En effet, si l'opération de qualification entraîne la mise en œuvre du régime, le désintérêt de la pratique pour le régime des fruits à souvent conduit à éluder la qualification de fruits. La proposition d'une notion de fruits libérée de son lien à la terre, renouvelle l'utilité de la notion et notamment face à l'incorporel. Ainsi, la notion de fruits rentre de plein pied dans le XXIe siècle pour pouvoir être utilisée dans le processus de qualification de biens incorporels. La notion de fruits prend alors tout son sens : que le fruits soit généré par un bien incorporel puisque la notion de fonds de l'article 583 du Code civil ne doit plus s'entendre que comme le fonds de terre, ou que le fruits soit lui-Même un bien incorporel. Cette rencontre du droit des biens et de l'incorporel permet alors d'offrir des pistes de réflexions en terme de régime : à côté des droits spéciaux, le droit civil, et en particulier les textes régissant les fruits, peut alors permettre de régler les conflits relatifs aux modes de naissance et d'appropriation des biens incorporels.
Keywords: Biens incorporels; Contracts; Corporate law; Dividendes; Droit des biens; Droit des sociétés; Fruits; Fruits civils; Fruits industriels; Fruits naturels; Intangible law; Intellectual property; Notion of funds; Property law; Propriedade intelectual; Propriété industrielle; Propriété intellectuelle; Revenu

Le statut des dirigeants sociaux en droit de l'OHADA - Folly, Messan Agbo (Université Montpellier 1, 2014)
Le statut des dirigeants sociaux en droit de l’OHADA présente une physionomie homogène. Il est rigide dans l’exercice de la direction sociale mais souple dans l’organisation de la direction sociale. La rigidité garantit à la société une direction responsable. En cela, les dirigeants sont dotés de pouvoirs légaux dans le cadre des actes courants pour qu’ils disposent d’une liberté d’action dans la réalisation des buts de la société. Ces pouvoirs connaissent un accroissement sans précédent à cause du déclin des contre-pouvoirs classiquement destinés à les modérer dans le cadre des actes graves. Les dirigeants peuvent donc accomplir valablement des actes graves au mépris des prescriptions qui les encadrent. Face à cet accroissement inquiétant de la souveraineté des dirigeants, les sanctions ont ravi la légitimité aux contre-pouvoirs classiques pour postuler en véritable contre-pouvoir. Les sanctions s’appliquent aux dirigeants chaque fois qu’ils portent atteinte à un intérêt protégé. Leur application s’impose qu’il s’agisse d’actes courants ou graves, qu’il s’agisse de dirigeant associé unique ou non, que la société soit in bonis ou en difficulté, ou encore que le dirigeant soit de droit ou de fait. Mais, la rigidité de la direction ne garantit pas toujours son efficacité. De plus, trop de rigidité tue la rigidité. L’introduction d’une dose de souplesse dans la direction des sociétés peut contribuer à la rendre plus dynamique. Le cadre approprié de cette souplesse est l’organisation de la direction. Ce cadre offre des ressources pour rendre la direction plus performante et très bien structurée. La performance peut être atteinte à travers le renforcement de la direction en la dotant de ressources humaines suffisantes, compétentes et stables. Elle se reflète par le succès de la politique managériale voire les résultats sociaux positifs. Sans doute, une meilleure structuration de la direction contribuerait au même résultat. Certes, la liberté d’organiser la direction est réduite lorsqu’elle porte sur ses structures. Mais cette liberté peut s’exprimer dans le respect de l’ordre public sociétaire. Ainsi, mis à part la nécessité de redéfinir le rapport des structures de l’exécutif des sociétés, il importe de consolider le contrôle des actes des dirigeants en facilitant l’implication d’organes externes à la direction pour aboutir à une gouvernance sociale dynamique.
Keywords: Abus de pouvoir; Chefs d'entreprise; Corporate law; Dirigeants; Droit des sociétés; Gouvernement d'entreprise; Managers; Organisation pour l'harmonisation en Afrique du droit des affaires; Powers; Sanctions; Sanctions (droit)

Confusão patrimonial nas sociedades isoladas e nos grupos societários: caracterização, constatação e tutela dos credores - Scalzilli, João Pedro de Souza (Universidade de São Paulo, 2014)
A presente tese versa sobre o fenômeno da confusão patrimonial nas sociedades isoladas e nos grupos societários. A tese propõe-se a: conceituar patrimônio social, examinando as suas principais características, funções e sua interatividade com o capital social; situar a pessoa jurídica como técnica de separação patrimonial; tentar alcançar um conceito de confusão patrimonial, diferenciando-a da confusão de esferas e apontando as insuficiências do estado atual da dogmática jurídica sobre a questão; examinar as principais características da confusão patrimonial, a saber a sua natureza, suas causas e seus efeitos (mais especificamente, os efeitos sobre os credores); caracterizar as diferentes formas pelas quais o fenômeno da confusão patrimonial se manifesta, bem como trabalhar com as exteriorizações desse fenômeno (indícios); apontar elementos que possam contribuir para a constatação judicial da confusão patrimonial; e apresentar e examinar algumas soluções para tutelar o interesse dos credores das sociedades que se encontram em situação de promiscuidade patrimonial. This thesis discusses the phenomenon of commingling of assets in isolated companies and in groups of companies. It proposes to: define a concept of corporate asset, examining its main characteristics, roles and interaction with shareholders' equity; assert the legal entity as a technique of separation of assets; attempt to reach a concept of commingling of assets, differentiating it from the mingling of spheres and pointing out current inefficiencies of the existing legal doctrine on the same issue; examine the leading characteristics of commingling of assets, namely its nature, causes and effects (more specifically, the effects on creditors); describe the different ways in which the phenomenon of commingling of assets is manifested, as well as discuss the materialization of this phenomenon (indicia); point out elements that may contribute to judicial analysis of issues related to commingling of assets; and, finally, propose and examine a number of solutions to safeguard creditors' interests that find themselves in situations of asset promiscuity.
Keywords: Characterization; Commingling of assets; Companies; Creditors protection; Créancier; Direito empresarial; Groupe de sociétés; Groups of companies; Observation; Patrimoine; Pessoa jurídica; Protection; Responsabilidade patrimonial; Société commerciale

A exclusão de sócio por falta grave na sociedade limitada: fundamentos, pressupostos e consequências - Spinelli, Luis Felipe (Universidade de São Paulo, 2014)
A tese propõe a análise dogmática da exclusão de sócio por falta grave na sociedade limitada, prevista nos arts. 1.030, 1.085 e 1.058 c/c 1.004 do Código Civil, tema que, apesar da enorme relevância e da existência de muitos estudos, comporta grandes dificuldades teóricas e práticas, carecendo a doutrina brasileira de uma análise sistemática e detalhada dos seus diversos aspectos. Assim, busca-se a sistematização da matéria e a construção de um modelo hermenêutico compatível com a nossa realidade normativa, além de tratar de questões pouco (ou nada) debatidas, pautando critérios a fim de que tal instituto tutele adequadamente o interesse e a funcionalidade da sociedade limitada e os direitos dos sócios. Para tanto, analisa-se, no primeiro capítulo, o pressuposto material (falta grave) da exclusão de sócio diante do descumprimento de seus deveres. Já no segundo capítulo são estudados os procedimentos possíveis (exclusão judicial ou extrajudicial) para a exclusão de sócio que comete uma falta grave. Finalmente, o terceiro capítulo aborda as consequências da exclusão de sócio por falta grave na sociedade limitada (perda do status socii, apuração e pagamento dos haveres, tratamento dado às quotas do excluído e alteração do nome social). This thesis examines the expulsion, for serious fault, of partners from limited liability companies, provided for in articles 1030, 1085, and 1058 read with 1004 of the Brazilian Civil Code. Despite the subjects enormous importance, and the various studies that exist, the expulsion of partners presents many theoretical and practical difficulties, and there has been no systematic, detailed study of the subject in its various aspects by Brazilian legal scholars. Thus, this work seeks to present a systematic analysis of the subject, constructing an interpretative model that is consistent with the reality of Brazils legal system, addressing questions that have been the subject of little (if any) debate, and suggesting criteria that will ensure that expulsion of partners adequately protects the interests and functionality of the limited liability company and the partners rights. The first chapter analyzes the substantive premise (serious fault) for expulsion of a partner that has breached his duties. The second chapter studies the possible procedures (judicial and non-judicial) for expelling a partner that has committed a serious fault. Lastly, the third chapter addresses the consequences of expulsion of a partner from a limited liability company for serious fault (loss of status socii, calculation and payment of the value of the expelled partners equity interest in the company, treatment given to the quotas held by the expelled partner, and change of the companys name).
Keywords: Breach; Cláusula contratual; Consequences; Defaulting partner; Duties; Expulsion; Grounds; Limited liability companies; Partners; Procedure; Responsabilidade contratual; Serious fault; Sociedade comercial; Sociedade por cotas de responsabilidade limitada

Alienação de controle: limitação do poder do controlador como mecanismo de proteção dos acionistas minoritários de companhias fechadas - Bezerra, Andréia Cristina (Universidade de São Paulo, 2014)
Esta tese tem como propósito o estudo da limitação dos poderes do controlador como mecanismo fundamental de proteção dos demais acionistas que integrem as companhias fechadas, sobretudo no contexto das operações de transferência de controle, nas quais é frequente que os minoritários fiquem impossibilitados de vender conjuntamente suas ações na mesma operação em que o controlador tiver transferido a sua participação a terceiros. A questão possui relevância na medida em que o art. 254-A da Lei das Sociedades por Ações (LSA Lei no 6404/1976) não cuida das companhias fechadas, e a obrigatoriedade da realização de oferta pública decorrente de alienação de controle nele prevista destina-se tão somente às companhias abertas. Na análise do assunto, discute-se a limitação dos poderes do controlador como o núcleo dos mecanismos de proteção das minorias, tendo em vista principalmente que as decisões nas companhias fechadas brasileiras são tomadas, como regra, por uma maioria estável, ficando os demais acionistas em uma posição de mera subordinação às decisões tomadas pelos controladores. É imperativo esclarecer que não se pretende assumir uma posição estanque de defesa dos minoritários, tampouco uma postura de ataque ao controlador. Ao revés, o verdadeiro desafio está em contrabalancear o legítimo poder conferido ao controlador, com os interesses dos minoritários. Para tanto, ao tema é conferido um tratamento de composição de interesses mediante o estabelecimento de limites aos poderes do controlador na exata medida necessária à proteção das minorias, sem, contudo, destronar o predomínio da maioria. Utilizam-se como fontes de pesquisa a literatura revisada nacional disponível em livros, periódicos, jurisprudência, decisões administrativas e na legislação pertinente ao tema. Na escassez de regulamentação substanciosa, complementa-se o estudo com teoria extraída da doutrina e da jurisprudência estrangeiras. This thesis aims to study the limitation of the powers of the controller as a fundamental mechanism for the protection of the other shareholders that are part of the closely held companies, especially in the context of transfer of control transactions, in which it is common for minority remain unable to jointly sell their shares in the same transaction that the controller has transferred its equity interest to third parties. The matter is relevant as the article 254-A of Corporate Law (LSA Lei no 6.404/1976) does not regulate closely held companies, and the obligation to make public offering resulting from de transfer of control provided in such article is intended solely to publicly held companies. In analyzing the subject, it is discussed limiting the powers of the controller as the minority protection mechanisms core, especially in view of the fact that decisions in Brazilian closely held companies are taken, as a rule, by a stable majority, being the other shareholders in a position of mere subordination to the decisions taken by controllers. It is imperative to clarify that it is not intended to assume a standing position defending the minority, nor a posture of attack the controller. To the contrary, the real challenge is counterbalance the legitimate power given to the controller with the minority interests. Therefore, the subject is addressed in a sense of composition of interests by establishing limits to the powers of the controller in the exact extent necessary for the protection of minorities, without, however, dethrone prevalence of majority. As sources of research are used the national reviewed literature available decisions and pertinent legislation. In dearth of material rules, the study will be complemented with foreign doctrine and case law.
Vente de contrôle : limitation du pouvoir du contrôleur comme mécanisme de protection des actionnaires minoritaires des sociétés privées
Keywords: Acionista minoritário; Closely held companies; Corporate law; Limiting controller power; Mecanismos de defesa; Mechanisms of protection; Minority shareholder; Sociedade anônima; Sociedade comercial; Sociedade por ações; Société commerciale; Transferring of control

La bonne gouvernance à l'épreuve des faits : le cas des entreprises publiques du secteur maritime au Bénin - Yasso, Désiré (Université Paris 1, 2014)
L’évolution du secteur public au cours de ces dernières décennies, a poussé les décideurs politiques au niveau international à réfléchir à des méthodes différentes pour la gestion publique. Cette volonté politique des instances supranationales de répondre aux impératifs de gestion des affaires publiques en vue de garantir leur performance a mobilisé les décideurs des pays du Sud autour de la notion de « bonne gouvernance » considérée comme un levier de paix et de stabilité. La notion de bonne gouvernance est introduite dans le discours des politiques de développement à la fin des années 1980 sous l’égide de la Banque Mondiale qui établi un lien entre la qualité du système de gouvernance d’un pays et sa capacité à promouvoir un développement économique et social durable. Elle sera suivie par les autres institutions de Bretton Woods. De même l’adhésion de la communauté internationale vient accroître la légitimité et donne autorité à la bonne gouvernance dans les conditionnalités d’aide au développement. La bonne gouvernance est ainsi perçue comme un produit mieux élaboré et plus rentable que les programmes d’ajustement structurel autrefois en vigueur. Mais la mise en œuvre de la bonne gouvernance se trouve confrontée aux réalités locales. Dans les entreprises publiques, la bonne gouvernance se heurte au régime de gouvernance de la corruption, très ancrée dans les pratiques et assez adaptatif en fonction du contexte. La bonne gouvernance dans les entreprises publiques devrait donc être le fruit d’une démarche inclusive, qui commence par un changement de mentalité, le respect des règles du jeu, l’adoption des pratiques de gouvernance généralement admises en management public. The evolution experienced by the public sector in recent decades has pushed policy makers at the international level to think about different methods for public management. This political will of supranational institutions to meet the requirements of public management to ensure their performance raised makers from the countries of the South around the notion of ''good governance'' considered as a lever for peace and stability. The concept of good governance is introduced into the discourse of development policies in the late 1980s under the auspices of the World Bank established a link between the quality of the governance system of a country and its capacity to promote a sustainable economic and social development. It will be followed by Institutions coming from Bretton Woods agreements. The support of the international community also comes to increase the legitimacy and gives authority to the good governance in the conditionality of development aid. Good governance is thus perceived as a product better developed and more profitable than structural adjustment programs, once in force. But the implementation of good governance is confronted to local realities. Public companies, good governance are facing the governance regime of corruption, very rooted in practices and quite adaptive according to the context. Good governance in public companies must be the result of an inclusive approach, which begins with a change of mentality, respect for rules of the game, the adoption of the governance practices generally admitted in public management.
Keywords: Administration publique; Bonne gouvernance; Bénin; Corruption; Entreprises publiques; Entreprises publiques (gestion); Good governance; Gouvernement d'entreprise; Management public; Public companies; Public management

Chapter 4 offer regulation under the 2008 Companies Act - Labuschagne, Frederik J. (University of Pretoria, 2014)
Chapter 4 of the Companies Act of 2008 aims to regulate offers to the public of securities and is reviewed against the principles which underscore the regulation of offerings. An overview of the historical development of the company which is parallel to the regulation of securities shows the crystallized principles which are compared against the development and enactment of the current regulatory regime. The concept of “complete law” as key element to effective regulation is discussed and applied in the review of Chapter 4 determining the effectiveness of the dispensation. The three determining concepts of regulation: the “offer,” “securities” and “public” are studied against the definitions which determine regulation and the inclusion of secondary market regulation of unlisted securities. Serious shortcomings in the process are identified. These errors, together with the practical problems of defining and regulating the secondary market in Chapter 4 read with the remainder of the delineating definitions, concludes that the current system is not in line with the principles of regulation and the Grundnorm of fraud prevention, resulting in Chapter 4 falling under the concept of “incomplete law” resulting in a high probability of enforcement failure and inefficiency. A comparative overview related to the jurisdictions of the United Kingdom and the United States follows with recommendations aimed at amending Chapter 4 relating to the regulatory regime in toto as well as the regulation of unlisted securities in the secondary market.
URI: https://repository.up.ac.za/handle/2263/45981
Keywords: Companies Act; Offer regulation

The requirement of consent for the transfer of shares and freedoms of movement : toward the liberalization of private limited liability companies : a comparative study of the laws of Portugal, France, Italy, Spain, the United Kingdom and the United States and its interplay with EU law - Vicente, Lécia (European University Institute, 2014)
Toward the Liberalization of Private Limited Companies – A comparative study of the laws of Portugal, France, Italy, Spain, the United Kingdom and the United States and its interplay with EU law’, I try to shed light on the dynamics of private limited liability companies (PLLCs), and how they can be legally designed to become efficient units of economic development in Europe and the United States. I take a social sciences approach to the legal question: How does the design of clauses establishing restrictions on transfer of shares of private limited liability companies affect investment made in these companies and their consequent development? To answer this question, I develop two parallel lines of investigation. First, I undertake an embedded historical study to trace the evolutionary patterns of PLLCs in six countries. Furthermore, I longitudinally track the standards of behavior of market agents in the selected jurisdictions. Second, I develop my legal research by looking at an anomaly regarding the transfer of shares and changes in the ownership structure of these business organizations. Transfer of shares in PLLCs is, for the most part, regulated by default rules which impose restrictions on transfers. Typically, the parties do not contract around these default rules. The anomaly lies in the fact that, even though shareholders of these companies do not opt out of these rules, shareholders often ignore them and/or breach them at a later stage.
Keywords: Business enterprises; Corporate law; Limited liability; Private companies

La dépénalisation du droit des sociétés et l'extension de la responsabilité des personnes morales - Bloch, Anne-Cécile (Université du Maine, 2013)
A l'heure actuelle, les règles du droit des sociétés et plus particulièrement du droit pénal des affaires imposent aux dirigeants le respect de très nombreuses normes. Pour autant dans les faits on ne peut dénombrer qu'un très faible taux de condamnations qui sont limitées à quelques incriminations ciblées tels les abus de biens sociaux, les délits d'initiés, les banqueroutes ... C'est pourquoi il semble impératif de procéder à une dépénalisation de cette matière, nécessité qui transparaît à travers différentes lois et directives depuis le début des années 2000. Mais pour que la dépénalisation aboutisse, il est aujourd'hui nécessaire de déterminer dans quel cadre l'utilisation du droit pénal doit perdurer. D'autre part, il appert que la substitution d'une sanction pénale par une sanction ayant un caractère civil, commercial ou administratif peut avoir un effet contraire à celui escompté. Enfin, il convient également de prendre en compte l'impact de la responsabilité pénale des personnes morales comme source de dépénalisation. Responsabilité qui est aujourd'hui appliquée de manière trop fluctuante et qui doit de ce fait faire l'objet d'une redéfinition par le législateur afin de se substituer à notre sens dans de nombreux cas à la responsabilité des personnes physiques dirigeantes.
Keywords: Abus de biens sociaux; Abuse of social assets; Administrative authority; Autorité administrative; Decriminalization; Depenalisation; Dispositions pénales; Décriminalisation; Dépénalisation; France; Infractions économiques et financières – France; Personnes morales; Responsabilité pénale; Sanctions civiles; Sociétés

De la gestion sans représentation : L'encadrement juridique des parties prenantes - Ropenga, Philippe (Université Paris-Est, 2013)
Les situations de gestion sont souvent complexes. Il faut faire appel à différents professionnels lorsque l'on souhaite accroître la valeur de son patrimoine. Les protagonistes de la gestion, qu'ils soient notamment mandataires, fiduciaires, salariés ou dirigeants sociaux, interviennent dans un cadre légal qui leur est propre. Le propriétaire use de son droit de propriété afin de conclure les contrats qui lui permettent de valoriser ses biens comme il l'entend. Ce travail porte sur la gestion conventionnelle des biens d'un bénéficiaire capable du vivant de celui-ci. Le gestionnaire gère les biens sur la durée et ignore l'état du patrimoine à la fin de la gestion. Le juriste français aborde spontanément la question sous l'angle de la représentation ou de la propriété qu'il s'agisse de la fiducie ou des trusts. Cette technique anglo-saxonne repose sur un rapport d'obligations particulier unissant le trustee au bénéficiaire qu'il est intéressant d'examiner afin de mieux comprendre la gestion. L'imputation systématique des actes du gestionnaire sur le patrimoine du bénéficiaire n'est pas souhaitable. C'est pourquoi l'hypothèse de travail est celle d'une gestion sans représentation. L'analyse du droit positif menée en première partie montre que, nonobstant la représentation, une technique de gestion efficace sur la durée repose sur les pouvoirs d'organisation et de direction conférés au gestionnaire. Le premier est celui d'accomplir une action c'est-à-dire un acte ou une série d'actes juridiques ou matériels. Le second permet d'apprécier l'opportunité d'une action. La seconde partie est consacrée à la recherche d'un cadre juridique adapté à la gestion.
Version incomplète
Keywords: Droit des affaires; Gestion; Intérêt; Propriété; Représentation; Temps; Trusts

La Force obligatoire du contrat de société : contribution à l'étude des relations entre droit des contrats et droit des sociétes - Receveur, Bee (Université de Cergy Pontoise, 2013)
La rumeur s'est répandue depuis plus d'un siècle dans le monde juridique que la société aurait quitté la sphère contractuelle provoquant ainsi la rupture du droit des contrats et du droit des sociétés. Et les auteurs, qui n'en sont pas convaincus, pensent néanmoins que la société se serait recluse dans une catégorie contractuelle singulière, celle des contrats-organisation au régime bien spécifique. Une des principales raisons de la remise en cause de la nature de la société réside dans l'avènement de la loi de la majorité jugée incompatible avec la conception volontariste de la force obligatoire du contrat forgée par le droit commun.Une étude approfondie de la force obligatoire du contrat de société révèle cependant que la société souffre d'une marginalisation excessive. Ses particularités ne l'empêchent pas en effet d'appliquer le principe de la force obligatoire : la société est soumise au principe d'intangibilité contractuelle et toute atteinte se résout par une sanction effective, exécution forcée ou résiliation.Mieux encore, à l'analyse, on constate qu'un certain nombre des spécificités dénoncées de la société, en particulier la durée, l'intérêt commun et l'intérêt social, se retrouvent en réalité à des degrés différents dans les autres contrats. Aussi, cette nouvelle perception du contrat à l'image de la société incite à une appréhension moins rigoureuse de la force obligatoire et de ses corollaires que sont l'immutabilité et l'irrévocabilité contractuelles. L'alliance du droit des contrats et du droit des sociétés favorise, ce faisant, l'élaboration d'une force obligatoire renouvelée plus adaptée à la réalité contractuelle.
Keywords: Compagny; Contact; Contrat; Force obligatoire; Mandatory strengh; Pérennité contractuelle; Société; Solidarisme contractuel; Unilatéralisme

L'actionnaire de court-terme dans les offres publiques - Jaeglé, Thomas (Université Paris 5, 2013)
Cette thèse vise à analyser les aspects juridiques du rôle joué par les acteurs ayant une stratégie actionariale de court-terme (hedge funds,...) dans le cadre des offres publiques d'acquisition. Outre l'identification de ces acteurs et la description des méthodes employées, il s'agit aussi de s'interroger sur les moyens à disposition de la société cible pour se défendre et de se demander si des évolutions législatives ne seraient pas nécessaires. The purpose of the Phd is to analyze questions raised by short-termism in takevoer bids. As a matter of fact, some shareholders only have short-terme strategies (such as Hedge funds,...) and takeover bids provide some fantastic arbitration opportunities. First, one should clearly identify these actors. Products which might be used in such situation will also have to be studied. Second, one should analyze which defence could provide the target. Third, a study of the opportunity or repealing or amending french legislation on these issues will be done.
Keywords: Actionnaires; Arbitrage; Bourse; Court-termisme; Droit de vote; Hedge Funds; Offres publiques d'achat; Opa; Short-termism; Spéculation; Takeover

Three Essays on Bank Lending and Corporate Finance - Chen, Liqiang (McMaster University, 2013)
This thesis includes three essays on several important topics in empirical finance: Chief Executive Officer (CEO) risk-taking incentives, the cost and syndicate structure of bank loans and corporate investments with internal funds. This thesis contributes to these aspects of finance literature and the three essays are presented in Chapter 2, 3 and 4. The first essay investigates how implicit contractual relationship between creditors and borrowers attenuates the conflict of interest between creditors and shareholders that arises from CEO compensation contracts when a corporation can be considered a nexus of explicit and implicit contractual relationships among stakeholders. We find that bank loans for firms with CEOs who are provided with risk-taking incentives have higher spreads and shorter maturities. A relationship between the lender and its borrower mitigates the influence of incentives for CEO risk-taking on loan spread and loan maturity. Such a relationship is especially beneficial for informationally opaque firms. The results are robust to the endogeneity of relationships and the simultaneous determination of loan spread, loan maturity and collateral requirements. Our results highlight the importance of the interaction between explicit and implicit contractual relationships to a firm’s borrowing cost. The second essay investigates the effects of a borrowing firm’s CEO risk-taking incentives on the structure of the firm’s syndicated loans. The conflict of interest between creditors and shareholders arising from CEO risk-taking incentives is a major concern of borrower moral hazard for syndicate lenders, which require intensive monitoring by lead arrangers in a syndicate. When CEO risk-taking incentives are high, syndicates are structured to facilitate better due diligence and monitoring efforts. These syndicates have a smaller number of total lenders and are more concentrated, and lead arrangers will retain a greater portion of the loan. Moreover, we examine the factors that affect the link between CEO risk-taking incentives and syndicate loan structure. CEO risk-taking incentives have a lesser effect on the syndicate structure when lead arrangers have a good reputation and have a prior lending relationship with a borrowing firm. By contrast, CEO risk-taking incentives have a greater influence on syndicate structure when borrowing firms are informationally opaque, are financially distressed or have low growth prospects. The third essay studies corporate investments with internal funds when firms face real investment friction using a sample of U.S. oil companies from 2003 to 2011 before and after the 2008 financial crisis. We show that firms’ capital expenditures are more sensitive to their lagged cash holdings than to their contemporaneous cash flows. By making investments with realized cash holdings, firms can avoid the investment adjustment costs that are incurred when investing with uncertain cash flows. We also show that cash flow policies are affected by liquidity constraints following the 2008 financial crisis: firms build up more cash reserves from cash flows, cut back payouts and raise more debt to maintain cash holdings.
Keywords: Bank lending; Cash flows; Cash holdings; Corporate Finance; Executive compensation; Financial Management; Investments; Managerial incentives

El régimen jurídico del protocolo familiar - Valmaña Cabanes, Antonio José (Universitat Rovira i Virgili, 2013)
La tesis arranca con un primer estudio general acerca de la empresa familiar, sus particularidades como sociedad mercantil y su encaje con los tipos sociales existentes. Considerando que uno de los elementos que la distinguen es su vocación de continuidad y, también, que los problemas a la hora de afrontar el relevo generacional son la principal causa de mortalidad de este tipo de empresas, se analiza el papel que el protocolo familiar puede jugar para resolverlos. Dentro del análisis del protocolo, se repasan sus antecedentes históricos, las experiencias en otros ordenamientos y, sobre todo, los problemas de eficacia que lo aquejan en España. Se trata de los problemas propios de todo pacto parasocial, agravados con un elemento adicional: no todos sus contenidos pueden ser vinculantes, porque choca con cuestiones de derecho necesario. Por ello, se plantea cómo mejorar esa eficacia a través de determinadas figuras jurídicas (cláusulas penales, prestaciones accesorias), algunas posibilidades relativamente recientes (acceso al Registro Mercantil) y, sobre todo, la plena convicción de sus firmantes, fruto sobre todo del consenso entre todos ellos.
https://www.tdx.cat/handle/10803/292369
Keywords: Derecho mercantil; Empresa familiar; Entreprise familiale

Le gouvernement d'entreprise dans les sociétés familiales non côtées - Kitsou, Anthi (Université de Strasbourg, 2013)
L’objectif de cette thèse est de discerner les originalités des sociétés familiales non cotées par rapport au gouvernement d’entreprise. On s’intéresse aux sociétés non cotées parce que les préoccupations sur le gouvernement d’entreprise se focalisent plutôt sur les grandes entreprises multinationales. Cependant, les sociétés familiales non cotées, actuellement la forme la plus répandue de l’initiative privée, posent de problèmes particuliers de gouvernement d’entreprise, parce que le lien entre famille et entreprise génère de conflits d’intérêts que la grande société cotée ne connaît pas. Premièrement, on expose les raisons pour lesquelles le gouvernement d’entreprise prend une importance plus cruciale dans ces sociétés. Il s’agit de montrer l’existence d’un particularisme s’agissant de la configuration de propriété, de gestion et de contrôle, puisque ces sociétés comportent la particularité de se trouver au croisement de deux systèmes ; la famille et l’entreprise (TITRE I). L’entreprise familiale se comporterait différemment vu que la composante familiale prédomine et influence le processus de prise de décision et les mécanismes de contrôle de la direction. LE TITRE II est consacré à la proposition d’ un ensemble de mesures susceptibles, à notre avis, de rendre son efficacité au système de gouvernance de la société familiale non cotée : une modification de la culture qui prévaut au sein des conseils; un renforcement de l’expertise et une amélioration de l’information des administrateurs ; la stricte séparation des fonctions de direction et de contrôle. This thesis aims to discern the particularities of family non -listed companies in relation to corporate governance. It isspecially focussed in non-listed companies, because research on corporate governance has been so far focussed on largemultinational firms. Non-listed family firms, nowadays the most common form of private initiative, pose particular problems of corporate governance, since the interconnection between family and company is a source of conflicts of interest that a public company does not face. Initially, the reasons why corporate governance has a crucial importance in this type of enterprise – due to its unique nature- are presented. This is to demonstrate the existence of uniqueness with regard to the configuration of ownership, management and control, as these companies have the distinction of being at the crossroads of two divergent systems: family and enterprise (Part I). The family business behaves differently because the family component predominates and undoubtedly influences the processes of decision making, control mechanisms and overall management. Part 2 is devoted to the proposal of a set of measures which, make ensure the effectiveness of the governance system of a non-listed family enterprise. It essentially entails a step change in the prevailing culture of the boards, a strengthening of expertise and improved information and management. The strict separation of management and control is also proposed.
Keywords: Actionnaires; Conseil d'administration; Corporate governance; Entreprises familiales; Famille; Family companies; Gouvernement d'entreprise; Minoritaires; Non cotées; Non-listed; Sociétés familiales; Valeurs mobilières

Réflexion sur l'abus en droit des sociétés dans l'espace OHADA : contribution du droit français - Aguemon, Khaled (Université Jean Moulin Lyon 3, 2013)
Depuis des lustres, les sociétés commerciales n’ont cessé d’être l’accessoire juridique favori des entrepreneurs dans l’exercice de leur activité. La société commerciale est créée par deux ou plusieurs personnes qui conviennent, par un contrat, d’affecter à une activité des biens en numéraire ou en nature, dans le but de partager le bénéfice ou de profiter de l’économie qui pourra en résulter. Cette définition découle de l’article 4 de l’AUSCGIE qui constitue une transposition de l’article 1832 du Code civil. L’AUSCGIE rassemble toutes les normes juridiques qui ont pour objectif de gouverner la constitution, l’activité et la fin de la société. Une des prérogatives les plus importantes des associés est de prendre part à la vie sociale, ils peuvent participer à cette vie sociale en dirigeant la société ou de façon plus réservée, en votant dans les différentes assemblées. Toutefois ce droit, comme tout droit est susceptible d’abus ; l’abus étant un usage injustifié ou excessif de quelque chose ou d’un pouvoir par son titulaire. D’un point de vue impartial avec les autres associés, l’AUSCGIE a codifié dans ses dispositions des sanctions contre les abus commis à l’occasion de l’exercice du droit de vote. Toutefois, l’abus ne se révèle pas uniquement lors de l’exercice du droit de vote. De multiples abus se révèlent aussi dans la direction et la gestion d’une société. Là encore, l’AUSCGIE a prévu des dispositions et laissé le soin aux Etats-parties d’instaurer dans leur législation des lois pour sanctionner ces abus. Le concept d’abus nous pousse donc à étudier les sources de sanction de ce dernier dans l’espace Ohada.
Keywords: Abus de biens sociaux; Abus de majorité; Abus de minorité ou d’égalité; Abuse of majority; Abuse of minority or equality; Administration provisoire; Agreement of vote; Alert; Alerte; Arbitrage; Arbitragem; Arbitration; Arbitration refereeing; Conflicts of interests; Conflits d’intérêts; Conventions de vote; Conventions réglementées; Expertise de gestion; Expertise of management; Intérêt social; Misuse of corporate assets; Organisation pour l'harmonisation en Afrique du droit des affaires; Prevention of the abuses; Prévention des abus; Refereeing; Regulated agreements; Sanction of the abuses; Sanctions des abus; Temporary administration; Transparence; Transparency

Contribution à la connaissance de la gestion du résultat des sociétés cotées en bourse : cas de la Bourse Régionale des Valeurs Mobilières - Diallo, Mouhamadou Saliou (Université Cheikh Anta Diop, 2013)
Cette recherche porte sur les déterminants de la gestion des résultats au sein des entreprises cotées en BRVM. Nous étudions la relation entre la gestion des résultats (mesurée à partir des accruals) et les motivations du dirigeant (rémunération, sécurité de l'emploi et réputation ou évaluation correcte du cours des titres) afin de tester deux hypothèses de gestion des résultats. Les analyses confirment plusieurs hypothèses de gestion des résultats et suggèrent que les déterminants de la gestion des résultats dépendent plus dans une perspective informationnelle que dans une perspective opportuniste.
Keywords: Accruals; BRVM; Bourse; Earnings management; Société commerciale; Valeurs mobilières

Le contrat de société en participation - Vierling-Kovar, Emmanuelle (Université de Strasbourg, 2013)
La société en participation ne s’analyse pas comme une société classique. Elle ne se dissout pas, elle est résolue ou résiliée, comme tout contrat de partenariat. Sa force, sa réalité, demeure dans le contrat librement choisi par les participants, tant dans son élaboration que dans l’organisation même de la société, situation intermédiaire entre un contrat classique et les sociétés institution. C’est l’application du principe d’autonomie de la volonté. Dans ce cas de figure, l’affectio societatis se rapproche le plus de la notion de jus fraternitatis, du moins lors de l’élaboration des statuts, ce que certains auteurs nomment l’affectio contractus. Finalement, en raison de son caractère éminemment contractuel, à la place de société en participation, ne faudrait-il pas plutôt l’appeler contrat de société en participation ? Il s’agit dès lors de lui reconnaître son caractère de contrat à part entière, un contrat nommé du Code civil. La jurisprudence semble aller dans ce sens. The joint-venture company cannot be analysed like a typical firm. It cannot be dissolved; it is solved or cancelled, as is any partnership agreement. Its strength, its reality, remains in the contract freely chosen by the participants, both in its elaboration and in the very organization of the firm, which consists in an intermediate situation between a classic contract and an “institution firm”. It is the application of the principle of will autonomy. In such a case, the “affectio societatis” is as close as it gets to the notion of “jus fraternitatis”, at least during the elaboration of the statutes which some authors name the “affectio contractus”. Eventually, because of this eminently contractual character, instead of joint-venture firm, should we not call it a firm participation partnership? What’s at stake here is the acknowledgment of its full contract character, as a contract named by the Civil code. The jurisprudence seems to go in that direction.
Keywords: Adhocratie; Affectio societatis; Agent; Apparence; Appearance; Banking pool; Bilan fiscal; Cession; Chef de file; Collective procedures; Commissionnaire; Contrat de société; Coproduction; Cotraitance; Fiscal balance sheet; Heritage; Indivision; Innovation; Joint-venture; Leader; Mise à disposition; Not revealed society; Patrimoine; Pool bancaire; Pool d’actionnaires; Pool d’investissement; Pool of investment; Possession; Procédures collectives; Provision; Public works; SEL; Shareholder’s pool; Society created de facto; Society of liberal exercise; Société créée de fait; Société non révélée; Sociétés en participation; Transfer; Travaux publics

La gouvernance des sociétés anonymes dans la zone OHADA - Sidibé, Issa (Université Cheikh Anta Diop, 2013)
L’examen de la pratique de la gouvernance des sociétés anonymes de la zone O.H.A.D.A. révèle des éléments de la « corporate gouvernance » avec des insuffisances. A l’aide de l’approche de l’analyse, de la synthèse et d’une démarche comparative, cette étude met en évidence l’existence de ces éléments et leurs limites, afin de proposer une convergence vers des pratiques harmonisées de gouvernance dans la zone O.H.A.D.A. par l’adoption d’un code de gouvernance et d’un code de bonne conduite des sociétés anonymes. Lesdits éléments sont relatifs à l’organisation des pouvoirs, des droits et de la protection des actionnaires. En effet, la hiérarchisation des pouvoirs des organes d’administration, de direction et de gestion est reconnue par l’AUSC. La société anonyme peut être administrée selon le cas par un conseil d’administration dirigé par un Président du conseil d’administration ou par un Directeur général, ou par un Président–Directeur-Général. Le législateur O.H.A.D.A. a aussi organisé la protection des actionnaires par la consécration à leur profit des pouvoirs de contrôle de la gestion, mais également des droits sur les résultats de l’entreprise. Ainsi dans diverses dispositions, l’AUSC organise la participation de l’actionnaire à l’assemblée générale, son droit de vote, de poser des questions, de communication et d’alerte. Il a, à sa disposition l’expertise de gestion, un outil juridique original qui lui permet de contrôler les dirigeants sociaux. Les principes de la « corporate gouvernance » a toujours prôné la lutte contre l’asymétrie d’informations au profit des dirigeants sociaux. Or il a été constaté que la concentration de pouvoirs dans la structure moniste de direction et l’institution d’un administrateur général ne sont pas de nature à favoriser la transparence. L’étude a, par conséquent, recommandé un code de gouvernance et un code de bonne conduite pour rendre plus performantes les sociétés anonymes par la convergence vers des pratiques universelles de gouvernance tout en tenant compte la prise en compte des éléments régionaux.
Keywords: Actionnaires; Administrateurs; Bonne pratique; Dirigeants sociaux; Pouvoirs; Responsabilité des dirigeants sociaux; Responsabilité sociétale; Société Anonyme; Transparence

L'unité économique et sociale - Cloître, Morgane (Université de Rennes 1, 2013)
L’unité économique et sociale, communément appelée « UES » est une pure création jurisprudentielle. Elle est apparue au début des années 1970 afin de mettre fin à la fraude de certains employeurs qui entendaient scinder leur société en de petites sociétés pour éviter la mise en place des institutions représentatives du personnel. Ces petites structures étaient alors considérées par le juge comme formant une seule et même entreprise pour la représentation du personnel puisque la même personne dirigeait une communauté de travail laquelle travaillait autour de la même activité. Utilisée rapidement en dehors des seules hypothèses de fraude, l’UES s’est également émancipée du droit de la représentation salariale. Ce travail d’émancipation est essentiellement le fruit de la jurisprudence, le législateur ayant très peu légiféré sur l’UES. Les relations collectives de travail essentiellement et les relations individuelles de travail dans une moindre mesure sont ainsi devenues accessibles à l’UES. Jusqu’au début des années 2000, la doctrine était très enthousiaste sur la notion d’UES et estimait même que l’UES devait être considérée comme l’entreprise en droit du travail. Aujourd’hui, cet élan est quelque peu retombé. L’UES est constituée de plusieurs personnes juridiques, lesquelles gardent leurs caractéristiques propres malgré la reconnaissance de l’UES. L’application de l’UES dans l’ensemble des domaines du droit du travail apparaît alors aujourd’hui inenvisageable. Mais, pour autant, l’UES constitue l’un des périmètres sociaux de l’entreprise en droit du travail. Il s’agira alors de savoir quelle place doit être conférée à l’UES en droit du travail.
Keywords: Comités d'entreprise; France; Représentation du personnel; Société; Unité économique et sociale

La protection des créanciers au sein des groupes de sociétés - Hmoda, Farag (Université de Franche-Comté, 2013)
L’étude juridique du groupe de sociétés fait apparaître une difficulté majeure qui émane de la grande différence entre le droit et le fait. En effet, bien qu’elles soient liées par un intérêt commun, les sociétés membres d’un groupe ne font toujours pas l’objet d’une réglementation détaillée qui prendrait en considération leur entité et leur unité économique et sociale distinctes. Il découle de cet antagonisme un risque de non correspondance des intérêts particuliers des sociétés membres avec la prévalence juridique de l'intérêt du groupe, lequel pourrait induire des effets préjudiciables aux différentes catégories des créanciers de ces sociétés.Toutefois, cette absence d’une loi particulière aux groupes a donné lieu à une réglementation ponctuelle qui vient modifier des règles du droit des sociétés ou qui régit certains domaines particuliers. De même, en raison d'une telle insuffisance de normes écrites, une importante partie du droit positif des groupes semble d’origine jurisprudentielle. Soutenus par la Cour de cassation, les juges du fond ne cessent de circonscrire les différents aspects de ce phénomène en vue de combler des lacunes juridiques qui heurtent l’équité. Plusieurs théories ont été instaurées en la matière, construisant ensemble une base importante pour la protection des créanciers, des salariés et des associés minoritaires liés à l’ensemble des sociétés regroupées. Legal study of the group of companies reveals a major difficulty which emanates from the big difference between law and reality. Indeed, although they are linked by a common interest, the member companies of a group are not always the object of a detailed ruling which would take into consideration their entity and their economic unity and social distinctions. From this antagonism follows a risk of not connecting the particular member companies with the legal acceptance of the group’s interest, which might lead to prejudicial actions towards the different categories of creditors and companies.However, this absence of a special law for groups gave rise to a timely rule which modifies the rules of the rights of companies or which rules certain particular fields. In the same way, because of an insufficiency of written standards, an important part of the actual right is derived from the origins of precedent. Supported by the Supreme Court of Appeal, the the trial judges do not cease to draw a line around the different aspects of this occurrence in the light of closing a legal loop hole which goes against fairness. Several theories have indeed been established on the subject, forming together an important base for the protection of creditors, wage earners and minor partners linked to the whole of the amalgamated companies.
Keywords: Action to fill in the debit; Conflict of interest; Conflits d'intérêts; Corporate law; Droit des sociétés; Effective director; Extension of joint procedure; Groupe de sociétés; Groupes de sociétés; Mother company; Mère filiale sous-filiale; Obligataires; Protection de créanciers des sociétés filiales; Protection des créanciers internes et externes des filiales; Rapports de contrôle entre sociétés; Redeployment of wage earners; Responsabilité de la société mère; Subsidiary company

Les fusions-acquisitions bancaires au Maroc et leurs conséquences juridiques et fiscales - Safi-Eddine, Hicham (Université Paris 1, 2013)
Quelles sont les conséquences juridiques et fiscales des opérations de fusions acquisitions bancaires au Maroc ? Sur le plan juridique, les opérations de fusion des banques sont régies, au même titre que les sociétés, quelques soient leur forme et leur objet, par deux textes fondamentaux : le Dahir des Obligations et des Contrats (D.O.C) et la loi sur les sociétés anonymes qui règlement les procédures d’élaboration du projet de fusion et de réalisation définitive de la fusion des sociétés concernées. En effet, la loi sur la liberté des prix et de la concurrence intervient, par le biais du Conseil National de la Concurrence, pour ne pas remettre en cause le principe de libre concurrence. Sur le plan fiscal, les fusions obéissent à deux régimes, le régime de droit commun et le régime de faveur, dont les conséquences fiscales sont très différentes. Pour le régime de droit commun, la fusion est une cession de sociétés de fin d’exercice. Quant au régime de faveur, la fusion est assimilée à la prolongation de l’activité au profit de la société absorbante. Dans ce cas, la plus-value réalisée par la société absorbée n’est pas immédiatement taxée en son nom mais est différée, dans le temps, est imposée au nom de la société absorbante. Pour évaluer l’impact des deux régimes de fusion, la recherche s’est appuyée sur deux cas : La fusion BCP-SMDC qui a été réalisée sous le régime de droit commun et celle de la BCM-WAFABANK qui a été effectuée sous le régime de faveur.
Keywords: Banking mergers; Banque du Maroc; Banques; Competencia; Concentration industrielle; Concurrence; Contrôle fiscal; Fusion d'entreprises; Fusions au Maroc; Impact du régime fiscal; Impôts; Maroc; Morocco; Régime juridique et fiscal; Sociétés; Tax; Taxe sur la valeur ajoutée

Entrepreneurial financing decisions, venture capital ownership and bargaining power - Heughebaert, Andy (Ghent University, 2013)
It is widely acknowledged that entrepreneurial companies play a key role in shaping a local economy. Entrepreneurial companies are a source of growth and innovation for an industry and provide jobs for the local population. However, entrepreneurs of high growth oriented companies rarely have the capital to finance their innovative ideas themselves and therefore also have to accept the risks associated with assessing and acquiring the necessary finance resources from other investors. The goal of this dissertation is to study the impact of venture capital (VC) finance on such entrepreneurial finance decisions. Although VC investors are a highly focused and specialized kind of investors that offer a wide range of differentiated services, it is to date still unclear how VC investors may reduce agency costs for other potential investors. The first study of this dissertation studies the effect of VC finance and associated VC ownership for finance decisions from other investors who have the potential to invest in these companies. This study demonstrates that VC ownership results into a larger supply of finance for the entrepreneurial company. Second, I find that VC ownership results into an even larger positive effect on capital investment decisions from equity investors as VC finance is typically also associated with the implementation of an equity-oriented corporate governance mechanism in entrepreneurial companies. VC ownership does not have an effect on the supply of finance from financial debt investors, however. Nevertheless, I find that debt finance is equally available for companies with VC ownership as compared to companies without VC ownership, which is a surprising result given the high risk associated with high growth companies that raise VC finance. Another important finding of this study is that the positive effect of VC ownership is stronger for repeated VC finance versus non-repeated VC finance. In fact, these results indicate that the effect of VC finance for entrepreneurial companies’ finance decisions is considerably larger if VC investors commit to further finance the company. The second study of this dissertation extends the first study and explores the effect of VC ownership on entrepreneurial finance decisions in different institutional settings. Although the effect of VC ownership is not limited to one specific institutional context, this study shows that its impact on entrepreneurial finance decisions is stronger in countries with a better quality of law enforcement and in countries where the entrepreneur is able to obtain a fresh start after bankruptcy. Specifically, in countries with a better enforcement of law, VC investors are more effective in reducing agency problems between entrepreneurs and potential investors. The attractiveness of a fresh start after bankruptcy will also be higher for an entrepreneur who raised VC finance, as VC investors focus more on maximizing the value of their portfolio rather than on the survival of individual firms. The third study acknowledges the fact that VC investors are not all equal and explores which VC investor types have more bargaining power versus the entrepreneur and how such differences in VC investor bargaining power affect company valuations in VC investment rounds. VC investor bargaining power is important because company valuations are the outcome of negotiations between the VC investor and the entrepreneur. We show that university VC firms and government VC firms negotiate lower valuations compared with independent VC firms. The proprietary deal flow of university VC firms and the limited competition in niche markets in which government VC firms compete will directly increase their bargaining power versus the entrepreneur, which these VC investor types then further exploit by negotiating lower company valuations compared with independent VC investors. Although differences in VC investor type did not affect entrepreneurial finance decisions in the first and second study, they do affect the equity stake that an entrepreneur will have to give up in order to raise VC finance and in order to a have a greater access to entrepreneurial finance from potential investors in the future.
http://hdl.handle.net/1854/LU-4096609
Keywords: Bargaining power; Financing decision; Venture capital

Corporate Restructurings in Zimbabwe : a Legal Analysis of the Regulation of Corporate Mergers and Acquisitions in Zimbabwe - Nzero, Ignatious (University of Pretoria, 2013)
The Zimbabwean economy rapidly declined over the past two decades. A record hyperinflationary environment and a collapse of the financial service sector coupled by lack of external lines of credit created a difficult operating environment for corporate businesses. Businesses thus either closed down operations or resorted to survival strategies. Corporate mergers and acquisitions emerged as natural favoured strategies in implementing survival corporate restructuring transactions. However, the success of such strategies largely depends on the effectiveness of the merger regulatory framework, that is, its ability to promote beneficial corporate restructuring transactions on one hand and to maintain the competitive structure of the market on the other hand. This research analyses the current merger regulatory framework in Zimbabwe and assesses whether it is suited to promote beneficial corporate restructuring transactions implemented through mergers and acquisitions without unnecessarily distorting the competitive structure of the market. Employing the failing firm doctrine as the focal point, the research identified a number of shortcomings within the current merger regulatory framework that impacts upon its ability to effectively promote beneficial corporate mergers and acquisitions without sacrificing the competitive market structure. Selected comparative jurisdictions were used to draw various lessons for Zimbabwe. The aim of the comparative study was not to provide an exhaustive analysis of these jurisdictions but to identify specific arrears that can be used to develop and suggest an effective merger regulatory framework for Zimbabwe. In order to remedy the identified shortcomings inherent within the current Zimbabwean merger regulatory framework, this thesis proposes a number of amendments to the current Competition Act [Chapter 7:01] of 1996. These proposed amendments are aimed at bringing clarity, flexibility and strengthening the merger regulatory framework including the institutions tasked with such. The research is primarily a legal analysis of the Zimbabwean merger regulating statute and its implications on any decisions made by the competition authority. As such, the thesis states the status of legal development in Zimbabwe and the selected comparative jurisdictions as of 31 July 2013.
URI: https://repository.up.ac.za/handle/2263/53211

Los sindicatos de bloqueo en las sociedades anónimas - Moreno Utrilla, David (Universidad de Sevilla, 2012)
La Constitución Española reconoce y protege el derecho de la persona a asociarse para los más diversos fines y propósitos lícitos con independencia de la causa, lucrativa o no, de la agrupación de personas o de su calificación técnica como mercantil o civil. Esta libertad de asociación se reconoce sin que pueda desmerecerla la ausencia de personalidad jurídica de la realidad asociativa creada (asociaciones sin personalidad) o la concurrencia o no de una voluntad electora de un tipo legal (asociaciones o sociedades atípicas). Esa misma libertad de asociación se refleja en toda clase de uniones, desde aquellas que persiguen fines de carácter ideal no lucrativo, hasta las sociedades de capitales, tanto de responsabilidad limitada como anónimas , y dentro de las últimas, tanto en las sociedades cotizadas o públicas (public companies) de estructura abierta como en las sociedades privadas de estructura cerrada (closely held). En concreto, en el ámbito de las sociedades anónimas resulta especialmente relevante cómo los accionistas se agrupan cada día por los más diversos motivos, pero con la intención última de modular el estatuto normativo típico en el ámbito de las relaciones existentes entre ellos y entre éstos y la sociedad. En nuestro Derecho de sociedades vigente una de las cuestiones que ofrecen mayor interés práctico es la integración, y en ocasiones la superación, de la normativa reguladora de las diversas relaciones jurídicas que se establecen, como consecuencia de la creación y funcionamiento de una sociedad, por medio de la formación de vínculos entre los socios con el fin, desde el punto de vista funcional, de concretar, completar o modificar, en el marco de sus relaciones internas, las reglas legales y estatutarias que rigen a la sociedad. El campo de aplicación natural de esta práctica es el de las sociedades cerradas, privadas o familiares, en las que la relación de confianza entre los socios, el intuitus personae, sustituye o, al menos, modula el intuitus pecuniae típico de las sociedades abiertas . En estas sociedadescerradas los socios mediante los citados vínculos pretenden crear una estructura similar, en el plano orgánico, al de la sociedad colectiva dentro del tipo normativo de la anónima, que determine con pautas propias la organización y el funcionamiento de la sociedad al objeto de conseguir una configuración cerrada o personalista en una sociedad prevista inicialmente por el legislador para ser abierta o capitalista. Sin embargo, esta realidad asociativa no solo se produce en las sociedades cerradas, en las sociedades abiertas también se dan estas agrupaciones de socios con el fin de reforzar la situación de quienes las integran; ya sea para conseguir o consolidar situaciones de dominio por los sindicados, ya sea para defender o ejercitar sus derechos de minoría. En estos casos los socios pueden acudir legítimamente a la solución de establecer convenios extraestatutarios, estipulados al margen del contrato de sociedad, que, ajustados a sus necesidades, respondan a sus intereses específicos. Con este propósito quienes son parte de estos convenios (socios o no, administradores de la sociedad o pertenecientes a un grupo familiar) aspiran a integrar, modular e incluso corregir o derogar el régimen estatutario, y en ocasiones el régimen legal, de la sociedad a la que se refieren tales convenios. La doctrina ha caracterizado estos convenios como acuerdos, pactos o contratos parasociales. El término “parasocial” quiere decir al margen de la sociedad, ya que etimológicamente proviene de vocablo griego para, que significa “al margen de”, y del vocablo latino sociales, que significa “relativo a la sociedad”. Con esta expresión se identifican aquellos convenios o acuerdos que son firmados por todos o algunos de los accionistas de una sociedad y que no se incorporan a los estatutos de ésta, quedando en el ámbito privado de sus suscriptores. El origen de esta práctica extraestatutaria o parasocial se encuentra en la organización de las distintas relaciones entre los accionistas y, sobre todo, entre los accionistas de control ya que, en muchas ocasiones, es difícil regularlas en el ámbito estatutario como marco aplicable y susceptible de surtir efectos sobre la totalidad de los socios. Por ello esta posibilidad constituye un tema de actualidad para la doctrina, ya que son frecuentes los conflictos que se generan en la vida societaria por la variedad y complejidades tipológicas de estos acuerdos que, lógicamente, no están plenamente acomodados a las normas de derecho necesario desarrolladas por el legislador y objeto de interpretación por los Tribunales. Esta realidad societaria se ha visto realzada aún más, de una parte, con la reciente LSC que recoge la definición legal de pactos parasociales que dio, por primera vez en el ámbito de las sociedades cotizadas, la Ley 26/2003, de 17 de julio, por la que se modificaba la Ley 24/1988, de 28 de julio, del Mercado de Valores; y, de otra, con el Real Decreto 171/2007, por el que se regula la publicidad de los protocolos familiares, que considera el contenido de éstos como pacto parasocial, si bien esta norma no es de aplicación a las sociedades anónimas cotizadas. Como más adelante se verá, estos convenios parasociales o, también, extraestatutarios se encuentran amparados por la libre iniciativa privada y por la libertad de empresa, constituyendo una manifestación de la autonomía de gestión en el ejercicio de la actividad empresarial y de la libertad negocial que preside la actuación de los operadores económicos en el desarrollo de su actividad. Lo expuesto nos introduce en el ámbito de la sindicación de acciones, que puede ser definida como la asociación, afectación o unión de acciones (rectius, de socios o de accionistas) por un período de tiempo determinado, con el fin de facilitar la celebración, fuera del contrato de sociedad, de acuerdos o convenios entre todos o algunos de los accionistas destinados a concretar, completar o modificar la normativa legal y estatutaria que regula sus relaciones internas, obligándose, entre sí, frente a la propia sociedad o frente a terceros, a actuar de un modo determinado para la defensa de intereses comunes a todos ellos. En esta definición estarían incluidos, como categorías con entidad propia, tanto la sindicación de voto (también sindicato de voto: afectación de acciones con el fin de que sus titulares se obliguen a emitir los votos correspondientes a las mismas en el sentido acordado por el sindicato), como la sindicación de bloqueo (también sindicato de bloqueo: afectación de acciones con la finalidad de imponer a sus titulares determinadas obligaciones, restricciones o limitaciones a la transmisión de las mismas). A efectos sistemáticos, para una mejor comprensión del estudio que se pretende realizar a partir de ahora, los sindicatos de voto y bloqueo se considerarán como supuestos concretos de la sindicación de acciones y, en sentido general, como acuerdos o convenios parasociales.

Abuso de voto na recuperação judicial - Mariano, Alvaro Augusto Camilo (Universidade de São Paulo, 2012)
O presente trabalho trata do abuso de voto na assembleia geral de credores que decide sobre o plano de reorganização apresentado pelo devedor na recuperação judicial. O trabalho ressalta que a função social da empresa é objetivo também da falência, conforme disposto no art. 75 da Lei n.º 11.101/05. Assim, o voto contrário ao plano não pode ser considerado, de per se, abusivo. Para tratar do tema, examina-se antes a figura do abuso de direito na teoria geral (capítulo segundo) e o abuso de voto nas companhias (capítulo terceiro). Por fim o tema é analisado no âmbito da recuperação judicial.
Keywords: Abus de vote; Abuse of rights; Abuse of voting; Abuso do direito; Bankruptcy; Direito Societário; Faillite; Falência; Insolvabilité; Insolvency; Recouvrement judiciaire; Recuperação Judicial; Reorganization; Social function; Sociedade anônima; Sociedade comercial; Société Anonyme; Société commerciale; Voto

Transações entre partes relacionadas: um desafio regulatório complexo e multidisciplinar - Camargo, André Antunes Soares de (Universidade de São Paulo, 2012)
Transações entre partes relacionadas são cada vez mais discutidas por reguladores, agentes econômicos e pela academia, não só no Brasil. Tal decisão empresarial, muito comum em grupos de sociedade que buscam eficiências gerenciais, suscita preocupações crescentes pelo potencial de conflito de interesses que traz em seus termos e condições, podendo beneficiar injusta e até fraudulentamente controladores e administradores de determinadas sociedades. Uma devida regulação da matéria faz-se imprescindível no crescente e promissor mercado de capitais brasileiro. Estruturada em três capítulos, esta tese parte da discussão sobre grupos e as transações entre suas partes relacionadas com o objetivo de delimitar o seu escopo. Em seguida, trata da regulação da matéria no direito brasileiro, culminando com seu estudo empírico e multidisciplinar. Observa-se, nessa investigação, a multiplicidade e a descoordenação regulatória que existe sobre o assunto em nosso país, seja em razão das estratégias regulatórias existentes, seja pelas diversas soluções jurídicas adotadas. O tema demanda uma reflexão profunda para receber uma nova e adequada regulação, não podendo seus aspectos jurídicos, econômicos, sociológicos e estratégicos ser ignorados, mas considerados de forma complementar. Contribuições da governança corporativa, ética empresarial e contabilidade precisam ser igualmente incorporadas nessa análise integrada. Este trabalho chega a quatro conclusões: (a) compreender grupos e suas relações contratuais internas é cada vez mais complexo e multidisciplinar e sua regulação precisa ser bem pensada e adequada, sob pena de intervenção indevida, desnecessária e excessiva na liberdade de organização empresarial; (b) os conceitos que existem sobre o assunto são demasiadamente amplos, extrapolando relações societárias, ajudando a fomentar uma regulação genérica e descoordenada; (c) a regulação do tema sempre foi reativa a crises, com modelos e soluções jurídicas pontuais e não coordenados entre si, desprezando-se custos organizacionais e outros efeitos negativos internos e externos, em vez de serem claros e lógicos e envolverem uma política pública mais direcionada, considerando estudos empíricos e dados oficiais já disponíveis; e (d) a realidade do mercado de capitais brasileiro está em crescente mutação e possui características peculiares, razão pela qual qualquer regulação do tema não se deve simplesmente importar soluções estrangeiras.
Keywords: Acionista; Capital markets; Conflicts of interest; Conflit d'intérêts; Direito comercial; Direito empresarial; Groups; Marché des capitaux; Regulation; Related party transactions; Sociedade comercial

Ato de preenchimento de orgão de administração: natureza jurídica da relação entre o administrador e a sociedade anônima - Sacramone, Marcelo Barbosa (Universidade de São Paulo, 2012)
Com o propósito de conceituar a natureza da relação jurídica entre o administrador e as sociedades anônimas, expõem-se, inicialmente, os centros institucionalizados de poder, suas formas de estruturação e funções desenvolvidas na companhia. Delimita-se, então, a quais desses núcleos de poder as atividades de direção, execução e supervisão ordinárias da atividade corporativa foram atribuídas pela Lei. Caracterizado o administrador, aprecia-se a qualidade na qual este age e produz determinados efeitos com seu comportamento. Para a definição dessa posição ocupada na companhia, afere-se a natureza da atribuição da personalidade jurídica ao ente coletivo e sua independência em face dos membros subjacentes. O vínculo criador dessa posição jurídica, entretanto, não possui fundamento teórico uníssono da doutrina estrangeira, tampouco é consenso entre os doutrinadores brasileiros. Aprecia-se, assim, a adequação dos principais argumentos de cada teoria frente ao ordenamento jurídico pátrio mediante a abordagem dos elementos estruturais do ato de preenchimento de órgão. A modalidade do referido ato é definida pela análise da natureza da eleição, mediante a apreciação da deliberação dos órgãos legitimados, da possibilidade de manifestar a vontade social diretamente a terceiros e de produzir efeitos determinados com autonomia, bem como da função integradora da aceitação, como condição de existência de um negócio jurídico bilateral ou de eficácia de um negócio jurídico unilateral. Por fim, confrontam-se as principais características dessa relação jurídica aos contratos de mandato, de prestação de serviço e de trabalho para possibilitar a verificação de sua adequação típica e a definição de um conceito ao ato de preenchimento de órgão de administração das sociedades anônimas. Aiming to create the concepts for the nature of the juridical relation between the officer and the joint-stock companies, this work initially exposes the institutionalized power centers, their structures composition and roles developed in the company. In the sequence, the essay outlines to which of those power nuclei the Law has ascribed the ordinary activities of direction, performance and supervision of the corporate activity. After the officer is characterized, the work analyzes the quality under which such officer acts and produces certain effects on his/her behavior. To define such position held with the company, it is verified the nature of the assigning the legal personality to the collective entity and its independence towards the underlying members. The bond creating such legal position, however, does not have unified theoretical ground in the foreign doctrine and neither is it a consensus among the Brazilian teachers. Hence, adequacy of each theorys main arguments is assessed against the countrys legal system by addressing the structural elements in the act of fulfilling the body. Modality of such act is defined by analysing the nature of the election, assessing deliberation of the empowered bodies, the possibility of manifesting the social will directly to third parties and to produce certain effects in autonomous manner, as well as the integration roles of the acceptance as a condition for existence of a bilateral juristic act or condition for efficacy of an unilateral juristic act. Finally the main characteristics of such legal relation are confronted with the power-ofattorney, service rendering and employment agreements to enable verification of their typical adequacy and definition of a concept to the act of fulfilling the administration body of the joint-stock companies.
Keywords: Acionista; Act of fulfilling; Administrateur; Administration; Conseil d'administration; Constitution; Joint-stock company; Legal nature; Negócio jurídico; Officers; Responsabilidade contratual; Sociedade anônima; Société Anonyme

La société unipersonnelle - Shyyab, Fuad (Université de Grenoble, 2012)
La présente contribution a pour objet d'effectuer une analyse critique de la société unipersonnelle. Une approche conceptuelle démontre qu'une théorie unitaire et cohérente de la notion de société suppose de réserver celle-ci à l'idée d'association entre deux ou plusieurs personnes. De même, en mettant l'accent sur l'utilité de la personnalité morale, celle-ci devrait être réservée aux groupements dotés d'un intérêt collectif. Dans la réalité, la société unipersonnelle n'est qu'une appellation légale consistant à introduire le patrimoine d'affectation d'une seule personne et cela sans fournir des justifications juridiques ou économiques validant sa responsabilité limitée. En outre, la société unipersonnelle n'est pas dépourvue de certaines conséquences négatives pour celui que l'on entend protéger, l'associé unique, alors qu'elle se révèle généralement peu efficace. La société unipersonnelle doit surtout être dénoncée comme une institution entraînant un divorce entre le droit et les faits. The present contribution is to carry out a critical study of single-member limited liability Company (Sole Proprietorship Company). A conceptual approach shows that a unitarian and coherent theory of the notion of société [company] suggests to reserve it to the idea of association between two or several persons. Also, focusing on the usefulness of the legal personality, it should be reserved for groups endowed with a collective interest. In the reality, the SMC (single-member Company) is a legal denomination consisting in introducing a special purpose patrimony (autonomous patrimony by appropriation) for a single person while the legal and economics bases of limited liability are not satisfied. Moreover, the SMC is not without certain negative consequences for the one that we intend to protect, the only partner (the sole owner), while it is generally proves irrelevant. Especially, the SMC must be denounced as an institution entailing a divorce between law and practice.
Keywords: Engagement unilatéral; Entreprise individuelle; France; Individual enterprise; Legal personality; Limited liability of Company; Notion de société; Notion of company; Patrimoine d'affectation; Personnalité morale; Responsabilité limitée; Sociétés unipersonnelles; Special purpose patrimony (autonomous patrimony by appropriation); Unilateral commitment

Responsabilité civile et contrôle de la société - Grosbois, Etienne (Université de Caen Basse Normandie, 2012)
Les sociétés, commerciales ou civiles, font l’objet d’un contrôle très important. L’analyse détaillée des fonctions respectives des différents organes sociaux démontre qu’en réalité le contrôle-direction et le contrôle-surveillance se rejoignent en une définition unitaire du contrôle. Cette définition s’applique à tous les intervenants dans la vie sociale et permet d’écarter de toute responsabilité du fait du contrôle les personnes qui ne sont titulaires que d’un simple droit à l’information. Si le contrôle doit être conçu comme une seule et même opération, la question se pose alors du bien-fondé de la multitude de régimes de responsabilité qui pèse sur les titulaires d’une mission de contrôle. L’étude des conditions et du régime de leur responsabilité permet de constater que, par delà les divergences de régime, les conditions de mise en jeu de cette dernière : la faute, le dommage et le lien de causalité sont identiques, quel que soit son fondement. Il est alors permis de critiquer les inégalités de régimes de responsabilité pesant sur les contrôlaires et les contrôleurs et de proposer un retour à une certaine cohérence par une révision, somme toute peu difficile, de la responsabilité du fait du contrôle
Keywords: Administrateurs de sociétés; Banques; Circuits de distribution; Competencia; Competition law; Concurrence; Contrôle; Corporate law; Droit des sociétés; Droit du travail; Entreprises en difficulté (droit); Labour law; Marché financier; Responsabilité civile

Board Structure, Ownership Concentration and Intellectual Capital - Zhang, Meiyi (Victoria University of Wellington, 2012)
This thesis investigates the influence of board structure and ownership concentration on the level and value relevance of intellectual capital disclosure. This thesis is motivated by the limited post-IFRSs (International Financial Reporting Standards) adoption intellectual capital disclosure studies carried out in a less stringent regulatory environment of New Zealand, and limited research addressing the determinants of the level and value relevance of intellectual capital disclosure. Based on an application of agency theory, cost-benefit theory and value relevance approach, this thesis argues that firm-specific factors are expected to have a significant impact on the level and value relevance of intellectual capital disclosure. Within the agency theory, board structure and ownership concentration mitigate agency costs by enhancing the monitoring function of the board over managers’ opportunistic behaviour, which consequently influence the level of intellectual capital disclosure. In addition, as New Zealand has less tough rules in relation to board structure and ownership concentration, it is expected that these relationships will be more easily identified in the New Zealand context. Second, as most of the intellectual capital disclosure is voluntary, this disclosure is subject to a firm’s cost-benefit analysis. Cost-benefit theory suggests that a firm should not fully disclose its information unless the benefits outweigh the costs of the disclosure. Therefore, the level of intellectual capital disclosure is also influenced by the factors that determine the costs and benefits of the disclosure. Finally, this thesis adopts the value relevance approach to measure the quality of the disclosure. It is expected that the factorsassociated with the level of the disclosure also influence the value relevance of the intellectual capital disclosure. This thesis is based on a sample of 155 firms listed on the New Zealand Exchange covering a total of 519 firm-years over the period between 1 January 2008 and 31 August 2011. A self-developed disclosure index and multiple regression analysis are employed to test the hypothesised relationships. Overall, the results indicate that the average level of intellectual capital disclosed by New Zealand listed firms is low and the human capital component is the most frequently disclosed intellectual capital component. The results provide strong evidence that board structure characteristics, including board size and independence, have a significant positive impact on the level of intellectual capital disclosure. There is strong evidence for a non-linear relationship between ownership concentration and the level of intellectual capital disclosure, which is robust to various types of intellectual capital (i.e. human, relational and structural capital). The results show marginal evidence that board gender diversity has a positive impact on the level of intellectual capital disclosure. In terms of the value relevance of intellectual capital disclosure, only board size has a positive impact on the value relevance of the intellectual capital disclosure. In the individual component analysis, board independence is found to have a significant positive impact on the value relevance of the human and relational capital disclosures. This thesis provides the most recent evidence on the influence of board structure and ownership concentration on the level and value relevance of intellectual capital disclosure in a less stringent regulatory environment of New Zealand. These findings have important implications to regulators, and assist information users in the interpretation of the voluntary intellectual capital disclosure.

Les succursales en droit international et européen. - Lagtati, Kamal (Université d'Auvergne Clermont-Ferrand 1, 2011)
Les succursales implantées dans un pays étranger sont plus autonomes que leurs consoeurs situées dans le même pays que la maison mère. Elles évoluent dans un environnement juridique différent et par conséquent les liens avec la maison mère sont distendus. Le tribunal de l’Etat d’accueil de la succursale est compétent et les lois de ce pays sont applicables. Toutefois, les lois du pays d’accueil ne sont pas les seules à être applicables. L’absence de personnalité juridique des succursales aura pour conséquence la sollicitation des lois de la maison mère. La cohabitation entre territorialité et extraterritorialité des lois peut donner lieu soit à des conflits soit à des situations de fraude. En l’absence de coopération entre Etats, les succursales qui sont des formes de rayonnement extérieur de la société deviennent des instruments pour pratiquer non seulement le forum shopping mais aussi le law shopping et le tax shopping.
Keywords: Agrément; Approval; Branch; Droit commercial (droit européen); Droit international économique; Extraterritoriality; Extraterritorialité; Fiscalité; Harmonisation (droit); Harmonization (law); Insolvabilité; Insolvency; Nationalisation; Nationalization; Succursale; Succursales; Tax system; Territoriality; Territorialité

The external relations of company groups in South African law : a critical comparative analysis - Stevens, Richard Arno (University of Stellenbosch, 2011)
Groups of companies are part of the realities of the modern economic system. Despite the fact that such groups often function as a single economic entity, the legal point of departure remains that each company within the group of companies is a separate juristic person. The result of this is that a creditor of a company within the group can, in principle, only enforce his claim against the company which he contracted with or which caused him harm. Should he wish to claim from the holding company or other solvent companies within the group, he would have to rely on an exception to the doctrine of separate juristic personality, viz the possibility of piercing the socalled corporate veil. This dissertation is a comparative study of the extent to which the law protects a creditor of an insolvent company within a group. The applicable laws of Australia, Germany, New Zealand, the United Kingdom and the United States of America, were investigated and compared to the South African position. The dissertation concludes that the South African legal treatment of the problem is unsatisfactory and that the law should be amended through appropriate legislation.
URI: http://hdl.handle.net/10019.1/6883
Keywords: Company groups; Creditors; South African companies; South African law

Vergi Hukukunda birleşme, bölünme ve hisse değişimi işlemleri - Göktuna, Hamdi Deniz Ege (Marmara Üniversitesi, 2011)
Kurumların birleşme, bölünme, kısmi bölünme ve hisse değişimi yoluyla yeniden yapılandırılma işlemleri başta ticaret hukuku olmak üzere, rekabet hukuku, sermaye piyasası hukuku ve vergi hukuku gibi birçok hukuk dalını ilgilendiren çok disiplinli bir alandır. Ticaret hukuku, genel olarak yeniden yapılandırma işlemlerinde şirket alacaklarının ve ortaklarının haklarının korunmasını amaçlamaktayken, vergi hukuku söz konusu işlemler sonucunda ortaya çıkan kâr ile ilgilenmektedir. Yeniden yapılanma işlemlerin vergisel maliyeti, bunların önündeki en önemli engeli teşkil etmektedir. Bu sebeple, tüm hukuk sistemlerinde vergisel açıdan tarafsızlığı sağlayıcı hükümler yer almaktadır.Çalışmamızda, özellikle, üye devletler arasındaki ekonomik ilişkilerin artırılarak, ekonomik gelişmenin ve refahın sağlanması yoluyla güçlü bir topluluk yaratma amacı taşıyan Avrupa Birliği Hukuku ve Türk Hukukunda yeniden yapılandırma işlemlerinin vergisel boyutu incelenmiştir. Avrupa Birliği Mevzuatına uyum sağlama çalışmaları çerçevesinde dolaysız vergiler alanında yapılması gereken düzenlemelerden birisi de vergi kanunlarında şirketlerin bölünmesini ve hisse değişimini kolaylaştırıcı, kalıcı mahiyette hükümler getirmek olmuştur. Dolayısıyla Avrupa Birliği Birleşme mevzuatı, tam üyelik sürecindeki ülkemiz açısından önem arz etmektedir.Çalışmamızın birinci bölümünde birleşme, bölünme, kısmi bölünme ve hisse değişimi müesseselerinin kavramsal esasları, Kurumlar Vergisi Kanunu, Türk Ticaret Kanunu ve Yeni Türk Ticaret Kanunu ile ilgili Avrupa Birliği mevzuatı çerçevesinde ortaya konulmaya çalışılacaktır. İkinci bölümde, birleşme, bölünme, kısmi bölünme, aktif transferi ve hisse değişimine ilişkin temel Avrupa Birliği düzenlemesi olan Birleşme Direktifi, Avrupa Birliği Adalet Divanı kararları çerçevesinde incelenecektir. Son bölümde ise Türk vergi mevzuatındaki, birleşme, bölünme ve hisse değişimine ilişkin hükümler tereddütlü noktalara da değinilmek suretiyle ele alınacaktır. Sonuç bölümünde birleşme, bölünme, kısmi bölünme ve hisse değişimi müesseselerine ilişkin değerlendirmelerimize yer verilmiştir. Transactions concerning the restructuring of companies through mergers, divisions, partial divisions and exchanges of shares relate to a multi disciplinary domain, including commercial law, competition law, capital markets law and tax law. While commercial law generally aims at the protection of rights of company's creditors and shareholders, tax law is mostly interested with the profit generated through these transactions. The tax cost of restructuring transactions, constitutes the main obstacle for those. For this reason, all legal systems include provisions providing tax neutrality regarding these transactions.In this study, we have analysed the tax law dimension of restructuring transactions especially in Turkish Law and Law of European Union which aims at the creation of a strong community through the development of economic relations between member states. Within the context of harmonisation to the European Union Legislation, one of the necessary regulations concerning direct taxes has been the enactment of tax law provisions enabling the division of companies and exchanges of shares thereof. Consequently, EU Merger Legislation is of utmost importance for Turkey as a candidate state.The first chapter of this study presents the conceptual basis of the transactions in question within the context of Corporate Tax Law, Commercial Law and the New Commercial Law and EU Legislation. The second chapter examines the Merger Directive within the framework of jurisprudences of European Court of Justice. The last chapter deals with problematic issues in Turkish Tax and Commercial laws. We conclude by presenting our evaluations based on previous chapters.
Tez N° 291505
Keywords: Avrupa Birliği hukuku; Avrupa Topluluğu hukuku; Birleşmeler; Change; Corporate Tax Law; Değişim; Division of company; European Community law; European Union law; Hisse senedi devri; Hisse senetleri; Kurumlar Vergisi Kanunu; Mergers; Stock transfer; Stocks; Tax harmonisation; Tax law; Vergi hukuku; Vergi uyumlaştırması; Şirket birleşmeleri; Şirket bölünmesi

Anonim ortaklıklarda anasözleşme değişikliği - Hamamcioğlu, Esra (Ankara Üniversitesi, 2011)
Tezimizin amacı, ortaklığın anayasası niteliğinde sayılan anasözleşmedeki değişikliklerin, hangi temel esaslar dahilinde yapılabileceğini ortaya koymak, değişikliğin şekli, kapsamı, usulü, sınırları ve sonuçları konusundaki mevzuat hükümlerini, doktrin görüşleri ve uygulama sorunları ile birlikte incelemektir. Çalışmamızda, ayrı birer tez konusu yapılmış veya yapılabilecek ayrıntılar içeren, esas sermaye artırımı, sermaye azaltımı gibi özel anasözleşme değişiklikleri tek tek incelenmek yerine, tüm anasözleşme değişikliklerinde geçerli olan temel esaslar incelenmeye çalışılmış, esas sermaye artırımı ve azaltımına özgü ve genel değişikliklerden farklı olan özel düzenlemeler kapsam dışı bırakılmıştır. 1 Temmuz 2012 tarihinde yürürlüğe girecek olan Yeni Türk Ticaret Kanununun konumuzla ilgili hükümleri de 6762 Sayılı Türk Ticaret Kanunu hükümleri ile karşılaştırmalı olarak tezimizde incelenmiştir. Üç ana bölümden oluşan tezimizin ilk bölümünde anasözleşme kavramı ve hukuki niteliği üzerinde durulmuş ve Alman, İsviçre, Türk öğretisindeki görüşler doğrultusunda anasözleşmenin hukuki niteliği konusunda bir sonuca varılmaya çalışılmıştır. Anasözleşme değişikliği konusunda çıkış noktamız olan anasözleşme içeriği de yine bu bölümde TTK ve YTTK hükümleri karşılaştırmalı olarak ele alınarak incelenmiştir. İkinci bölümde, öncelikle değişiklik kavramı üzerinde durulmuş ve hangi tür değişikliklerin anasözleşme değişikliği kapsamında değerlendirilmesi gerektiği tespit edilmeye çalışılmıştır. Değişiklik usul ve şartları konusu ise, değişiklik metninin hazırlanması, gerekiyorsa Sanayi ve Ticaret Bakanlığından izin alınması, değişikliğin genel kurulda karara bağlanması, imtiyazlı paysahiplerinin onayı ile ticaret siciline tescil ve ilan alt başlıkları çerçevesinde ele alınmıştır. Çalışmamızın son bölümü anasözleşme değişikliğinin sınırları ve denetimine ayrılmıştır. Bu kapsamda özellikle vazgeçilmez ve müktesep haklarla, imtiyazlı paylardan doğan hakların anasözleşme değişikliklerine çizmiş oldukları sınırlar kanun hükümleri kapsamında tespit edilmeye çalışılmıştır. Aynı bölümde, anasözleşme değişikliğinin hükümsüzlüğü ve denetimi başlığı altında, yokluk, butlan, iptal edilebilirlik ve askıda hükümsüzlük halleri üzerinde genel hatlarıyla durulmuştur. The purpose of this thesis is to put forward the main principles through which the amendments in the main contract, considered to be the constitution of partnership, could be made and to analyze provisions of the legislation together with doctrinal views and implementation issues regarding the form, scope, procedures (mode), limits and results of amendment.In this study, rather than focusing on specific main contract amendments with details that have been or could be the subject of a separate thesis such as the increase or reduction in authorized capital, the basic principles that apply to all main contract amendments were analyzed and the arrangements specific to increase and reduction in authorized capital and special arrangements, which are different from general amendments, were left out of the scope of the study.The relevant provisions of the new Turkish Commercial Code, which will come into force on 1 July 2012, are examined in this thesis in comparison with the provisions of the Turkish Commercial Law No. 6762. This thesis is consists of three main parts. In the first part, the emphasis is on the concept of main contract and its legal attributes; and in accordance with the legal opinions stemming from the German, Swiss and Turkish doctrines the first part tries to reach a conclusion regarding the legal attributes of the main contract.The content of the main contract, which is the point of departure regarding the main contract amendment, is also analyzed in this part by means of discussing the provisions of the TCL in comparison with that of the NTCC. The second part primarily focused on the concept of amendment and sought to determine what kind of amendments should be evaluated within the scope of main contract amendment.The issue of procedures and conditions for the amendment is elaborated under the subheadings: the preparation of the text of amendment, (if necessary) the authorization from the Ministry of Industry and Commerce, the decree for the amendment in the general assembly, registration at the trade registry and promulgation with the approval of the privileged shareholders.The last part of the thesis is on the limits and supervision of main contract amendment. Within this context, this part tried to determine the limits stipulated for the main contract amendments under the provisions of the law particularly by indispensable and vested rights as well as the rights incurred from concessional shares. Within the same part, under the heading/title of invalidity of the main contract amendment the cases of absence, voidness, revocation and pending invalidity have been analyzed in general terms.
Keywords: Anonim ortaklıklar; Change; Companies; Contracts; Değişim; Incorporated companies; Sözleşmeler; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Şirketler

L'acquisition et la cession des actions des sociétés chinoises par des investisseurs étrangers - Li, Guannan (Université d'Orléans, 2010)
L’apparition de l’acquisition et de la cession des actions étrangères en Chine s’inscrit dans la progression de développement de l’économie chinoise qui a été fortement stimulée par l’application de la politique d’ouverture. Depuis l’adhésion à l’OMC en 2001,les modes d’investissement de l’acquisition et de la cession d’actions ont graduellement commencé à remplacer celle d’investissement relative simplement à l’installation d’une entreprise étrangère en Chine. Bien que la législation chinoise ait essayé de contribuer à la protection de ces nouvelles modes d’investissement étranger, les défauts de loi ainsi que le vide juridique deviennent comme même l’obstacle principal qui empêche le développement de l’acquisition et la cession des actions étrangères en Chine. Dans ce contexte, la problématique de cette thèse est d’une part d’analyser l’ensemble des dispositions actuelles portant sur l’acquisition et la cession des actions étrangères afin de les mettre en œuvre en pratique, d’autre part de rationaliser les mécanismes juridiques chinois en recherchant la possibilité de réforme proposé.
Keywords: Acquisition by agreement; Acquisition by offer; Acquisition d'actions; Acquisition of shares; Acquisition par accord; Acquisition par offre; Actions de sociétés; Cession d'actions; Cession of shares; Chine; Concentration; Droit des actionnaires; Investissement en chine; Investment in China; Right of shareholders

Le groupe de sociétés en droit français et en droit chinois - Hu, Xinyu (Université d'Angers, 2010)
La création des groupes de sociétés est devenu un phénomène économique incontournable dans notre société moderne. Ce phénomène est reconnu, de manière différente, par les diverses branches de droit, tant en France qu'en Chine. Nous constatons sa prise en considération en droit des sociétés, en droit comptable, en droit fiscal, en droit financier, en droit social, en droit de la concurrence et même en droit pénal. Au sein d'un même pays, la reconnaissance juridique des groupes de sociétés n'est pas uniforme, en raison de la différence des finalités poursuivies par chacune des branches de droit. La création d'un droit spécial de groupe de sociétés, visant à lui affecter un statut juridique unique, s'avère inopportun. Actuellement, le groupe de sociétés n'est pas encore parfaitement défini en termes juridiques, et se caractérise par une certaine relativité en droit. Un droit régissant le groupe de sociétés semble impossible sauf à réaménager profondément le régime actuel du droit des sociétés. Afin de ne pas ignorer la réalité économique du groupe dans l'ordre juridique, il est plus pertinent d'adapter les règles de droit actuelles. A cet égard, le droit français sert de modèle pour le droit chinois. Ce dernier pourrait, dans les prochains travaux législatifs, s'inspirer des dispositifs légaux et jurisprudentiels français cherchant à préserver non seulement la dynamique économique de groupe de sociétés, mais aussi le maintien de l'équilibre des intérêts conflictuels entre les diverses parties prenantes. A l'égard des relations entre les associés majoritaires, minoritaires et les dirigeants sociaux, le droit français démontre que les règles traditionnelles du droit des sociétés sont a priori suffisantes pour résoudre les problèmes engendrés dans le cadre du groupe de sociétés. Ainsi les règles juridiques françaises paraissent équilibrées dans la mise en oeuvre de la responsabilité du groupe vis-à-vis des créanciers, y compris les salariés. Cet équilibre est assuré par une série de régimes classiques, tel que la fictivité, la confusion des patrimoines et la responsabilité des dirigeants de fait. Le droit chinois, fortement influencé par les régimes anglo-saxons, notamment par ceux de la "Business Judgement Rule " et de la " levée du voile corporatif ", pourrait s'inspirer des dispositifs français, plus adaptées et efficaces. The creation of corporate group became one significant economic phenomenon in our modern society. In France as well as in China, this phenomenon is acknowledged in the different ways by the various branches of law. It is taken into consideration by the company law, the accounting law, the tax law, the financial law, the labour law, the competition law and even by the criminal law. In each country, the ways of acknowledgement of the corporate group are not identical, due to the difference of the objectives that the various branches of law attempt to realize. The establishment of one special law for the corporate group, which recognizes its unified legal status, appears to be improper. Up to now, the corporate groups have not yet been perfectly described in legal terms, and do not constitute a solid legal conception. The legislation of one corporate group law seems to be impossible, unless a fundamental revision of the current company law were realized. In order to avoid the ignorance of the economical reality of the corporate group by the law, it is better to proceed to the adjustment of the currently effective legal provisions. In this respect, the French law constitutes one model to be followed by the Chinese law. The latter could, through the legal reforms in the future, be inspired by the legal and judicial rules of the French law, which seeks to preserve not only the economical vitality of the corporate group, but also the balance of the conflicting interests of the stakeholders. With regard to the relations between the majority shareholders, the minority shareholders and the corporate directors, the French law comes to demonstrate that traditional rules of the company law, after adaptation, are normally sufficient to resolve the problems incurred within the corporate group. Furthermore, the French legal provisions appear capable to maintain a balanced solution related to the group's responsibility vis-à-vis the creditors (employees included). This balance is ensured in French law by a series of classical provisions, such as the ''fictivité''(false company), confusion of assets as well as the liability of the de facto directors. The Chinese law, currently under strong influence of the Anglo-Saxons legal provisions - especially the ''Business Judgement Rule'' and the ''Piercing the corporate veil'' rule, could refer to the French provisions, which is more adapted and efficient.
Keywords: China; Chine; France; Groupe de sociétés; Holdings; SARL; Société à responsabilité limitée

Le pacte d'actionnaires dans l'environnement sociétaire - Leroy, Caroline (Université Paris-Est, 2010)
Le pacte d’actionnaires se place dans une forme de dépendance unilatérale au contrat de société qui n’est pas sans rappeler le rapport juridique d’accessoire à principal.En effet, s’il est fondamentalement distinct du contrat de société qu’il complète, tout pacte conclu par certains actionnaires, en dehors des statuts, afin d’organiser leurs relations interindividuelles d’actionnaires, trouve nécessairement sa matière et puise sa raison d’être dans le pacte social. Ainsi, la dépendance du pacte au contrat de société se manifeste-t-elle, de la manière la plus évidente, par la caducité qu’entraîne pour le pacte l’arrivée du terme du contrat de société ou la perte de la qualité d’actionnaire d’un partenaire.Dès lors, par analogie avec la règle selon laquelle l’accessoire a vocation à suivre le sort du principal, cette dimension d’accessoire du contrat de société justifie que le pacte subisse l’influence du cadre juridique auquel le contrat de société est lui-même soumis, à savoir le droit des sociétés et, en particulier, l’ordre public sociétaire.Cette dépendance au contrat de société, par essence commune à tous les pactes d’actionnaires en raison de leur objet matériel et de leur cause, est à géométrie variable. Elle repose en effet sur divers facteurs de rattachement au contrat de société que sont l’exercice du droit de vote, la détention des actions ou la qualité d’actionnaire des partenaires, lesquels impriment, selon qu’ils s’immiscent plus ou moins profondément dans le fondement, la structure ou encore le fonctionnement de la société, différents degrés de dépendance dans la relation pacte - contrat de société.Malgré l’hétérogénéité du régime des pactes d’actionnaires, il est alors possible de dégager,à l’aune de cette dimension d’accessoire, une tendance fondamentale qui anime, en droit positif, la jurisprudence relative aux pactes. Cette ligne directrice réside dans la variabilité du degré d’emprise des règles qui encadrent le contrat de société sur le régime des pactes d’actionnaires.La jurisprudence se révèle être, en effet, d’une manière générale et par-delà la casuistique, en cohérence avec cette influence proportionnelle de l’environnement sociétaire à l’intensité du degré de dépendance que présente chaque type de pacte en fonction du facteur qui le rattache au contrat de société. Les pactes caractérisés par une dépendance marquée au contrat de société bénéficient ainsi d’une marge de liberté à la mesure de celle dont bénéficie le contrat de société pour l’aménagement de l’exercice du droit de vote ou de la perte de la qualité d’actionnaire. Au contraire, les pactes caractérisés par une dépendance modérée au contrat de société, qui organisent des cessions ou des acquisitions d’actions,sont plus largement libérés des contraintes auxquelles est soumis le contrat de société au regard du principe de libre négociabilité des actions. Quant à l’influence sur les pactes de certains autres principes d’ordre public sociétaire, tels que la prohibition des clauses léonines ou l’expertise de l’article 1843-4 du Code civil, elle demeure incertaine en droit positif. Toutefois, la jurisprudence tend à reconnaître le particularisme de ces règles et à leur retirer, en conséquence, tout caractère impératif en dehors du cadre des relations entretenues collectivement par les actionnaires avec la société.
Keywords: Accessoire; Accessory / incident; Acte individuel ou collectif; Actes juridiques; Aménagement des statuts; Company constitution; Company structure and organisation; Composition de l’actionnariat; Connecting factors to the company agreement; Contrat de société; Convention extra-statutaire entre actionnaires; Corporate law; Corporate law (contractualisation); Dependence to a contract / contractual dependency; Droit de vote; Droit des sociétés (contractualisation); Dépendance contractuelle; Extra-statutory shareholders’ agreement; Facteurs de rattachement au contrat de société; Fonctionnement de la société; Individual or collective deed; Inter-individual relationships between shareholders; Liberté contractuelle; Limited company; Memorandum and articles of association extra-statutory adjustment; Memorandum and articles of association of the company/ company agreement; Ordre public sociétaire; Pacte d’actionnaires; Pactes d'actionnaires; Qualité d’actionnaire; Relations inter-individuelles entre actionnaires; Shareholder status; Shareholder structure; Shareholders’ agreement; Société Anonyme; Sociétés anonymes; Statuts / contrat de société; Voting right

Les contrats civils appliqués aux actions - Delecourt, Benoist (Université Lille 2, 2010)
Les contrats civils appliqués aux actions ont pour finalité le transfert, souvent provisoire, des différents droits politiques et financiers inhérents à ces titres : les droits politiques convoités sont le droit de vote et la qualité d’actionnaire afin de devenir administrateur, si les statuts l’imposent ; les droits financiers permettent quant à eux de transmettre l’entreprise et d’utiliser les actions comme garantie. Pour opérer ces transferts, les praticiens utilisent des contrats classiques, souvent issus du Code civil, mais aussi des contrats d’inspiration civiliste qui emploient des techniques civilistes, leur empruntent une partie de leurs régimes juridiques et poursuivent les mêmes finalités. Toutefois, ces contrats ne donnent pas entière satisfaction : les uns ont un régime juridique souple mais n’offrent pas une sécurité juridique suffisante ; les autres sont au contraire fiables mais affligés d’un régime juridique contraignant. Le législateur, en instituant la fiducie, pouvait remédier à ces inconvénients. Mais si la fiducie offre une grande sécurité juridique, c’est toujours au détriment de la liberté contractuelle. Une nouvelle réforme de la fiducie est donc indispensable.
Keywords: Actionnaires; Conseil de surveillance; Contrats; Crédit; Droit de vote; Entreprises (transmission); Garantie des obligations financières; Nantissement de comptes-titres; Obligations (finances); Prêt; Prêt de titres financiers; Sûreté; Transmission d’entreprise; Vente à réméré

Abuso de minoria em direito societário: abuso das posições subjetivas minoritárias - Adamek, Marcelo Vieira von (Universidade de São Paulo, 2010)
A tese tem por objeto a análise do instigante tema do abuso de minoria em direito societário, sobre o qual muitos possuem uma noção geral empírica, extraída da sua vivência profissional, mas que, no direito brasileiro, não havia sido objeto de análise sistemática por parte dos juristas pátrios, que ao tema dedicaram não mais do que algumas breves considerações, malgrado a sua inegável importância e a riquíssima experiência acumulada noutros países, em especial na França, Itália e Alemanha. Partindo das constatações inegáveis de que a minoria, ainda quando atue em face de um grupo controlador preestabelecido, exerce um verdadeiro poder e de que, onde há poder, existe sempre a possibilidade de sua degeneração, do seu desvirtuamento, procurou-se apontar quais são os pressupostos caracterizadores do abuso de minoria no direito societário brasileiro, com apoio em subsídios de direito comparado. De fato, tanto a maioria como a minoria podem exercer os seus direitos de maneira abusiva dentro de uma sociedade, de modo que o estudo do tema não pode ser entendido como um golpe à posição dos grupos minoritários, e sim o contrário: só quem conhece os limites dos seus poderes tem condições de exercê-los de forma eficaz, sem temer as reações de seus atos. Elaborado sob tal perspectiva, o estudo encontra-se dividido em cinco partes. A primeira delas, composta por dois capítulos, tem por objetivo caracterizar o abuso de minoria em direito societário analisando, para tanto, os vários institutos empregados pela doutrina nessa tarefa edefinindo os seus elementos constitutivos. Na segunda parte, procura-se apresentar a tipologia do abuso de minoria e a sua casuística, com destaque para as situações mais interessantes ou corriqueiras. A terceira parte, por sua vez, trata do delicado e intrigante problema dos meios de repressão dos abusos de minoria e as possíveis técnicas contratuais e estatutárias de auto-tutela. A quarta parte, a seu turno, traz breves considerações sobre a hipótese, também pouquíssimo explorada na doutrina, do abuso de igualdade, que pode se instalar em sociedades em que o capital votante é igualmente dividido entre dois sócios e que, assim, só consegue operar sob o signo da unanimidade. Por fim, na quinta e última parte são apresentadas as considerações finais, com o apanhado das principais conclusões construídas ao longo da tese. The purpose of this thesis is to analyze the exciting theme of minority abuse in the corporate law, of which many legal professionals have general empirical knowledge, extracted from their professional experience, but that, in the Brazilian law system, had not been the subject matter of a systematic analysis on the part of Brazilian law experts, that dedicated no more than some brief considerations to the theme, in spite of their undeniable importance and very rich experience accumulated in other countries, especially in France, Italy and Germany. Based on undeniable verifications that the minority, even if acting against a pre-established controlling group, exercises a true power and that, where there is power, there is always a possibility for degeneration and distortion of power, we sought to point out the assumptions characterizing minority abuse in the Brazilian corporate law, supported on inputs from comparative law. Actually, both the majority and the minority may exercise their rights abusively in a society, so that the study of the theme should not be understood as an attack on the position of minority groups, much on the contrary: only those who know the limitations of their powers are in a position to exercise them effectively, without fearing any reactions to their actions. Prepared under such perspective, this study is divided into five parts. The first of them, consisting of two chapters, intends to characterize minority abuse in corporate law analyzing for such, the several institutes employed by the doctrine in that task and defining their constitutive elements. In the second part, the author seeks to present the typology of minority abuse and its casuistry, highlighting situations that are most interesting or ordinary. The third part, in turn, discusses the delicate and intriguing problem of manners to repress minority abuses and possible contractual and statutory self-protection techniques. The fourth part brings brief considerations on the hypothesis, also very little explored in the doctrine, of equality abuse, that may get settled in societies where the voting capital is equally divided among shareholders and therefore, can only operate under the sign of unanimity. Finally, the fifth part presents the final considerations, with a summary of the main conclusions developed throughout the thesis.
Abus de minorité en droit des sociétés : abus de position subjective minoritaire
Keywords: Abuse; Acionista minoritário; Assembleia geral; Aumento de capital; Conflicts of interest; Corporate law; Fraud on the majority; Minority; Sociedade anônima; Sociedade comercial

La cession de droits sociaux de l'associé minoritaire - Guebidiang A Tchoyi-Doumbe, Hélène (Université d'Auvergne Clermont-Ferrand 1, 2010)
L’associé minoritaire peut quitter sa société pour des raisons diverses : baisse de la valeur de ses droits sociaux, mésentente avec les coassociés, simple désaffection, opposition à la politique des majoritaires. L’étude de la cession des droits sociaux de l’associé minoritaire traduit d’une façon équivoque, ce sentiment pour cet associé d’être libre de céder ses titres et en même temps d’être limité dans l’exercice de cette liberté par certaines règles du droit des sociétés. L’étude de la cession des droits sociaux par un associé minoritaire est axée sur une analyse faite au regard strictement du contrat de société que la volonté de sortie de l’associé minoritaire vient remettre en cause. En nourrissant la réflexion des points de friction les plus classiques comme l’exclusion, la qualité d’associé ou l’intérêt social, l’objectif est de présenter les différentes règles d’organisation de la cession des titres d’un associé minoritaire, les difficultés pratiques et théoriques qui y sont liées et surtout son analyse juridique. Sur ce dernier point, la principale interrogation que l’on se pose est de savoir si la cession minoritaire des droits sociaux est une cession simple ou une cession de contrôle. A travers les grandes questions qui se sont posées lors du débat relatif à la spécificité de la cession de contrôle, nous avons pu démontrer que les réponses qui ont été apportées ou les règles qui ont servies à la spécificité de la cession de contrôle ne sont pas toujours applicables dans le cadre d’une cession minoritaire des droits sociaux. En outre, le sujet pose la question de la protection de l’associé minoritaire. Cette question redonne un réel intérêt au débat relatif à la généralisation du droit de retrait comme solution à l’emprisonnement des associés minoritaires, solution que la frénésie législative de ces dernières années n’a pas pris en compte.
Keywords: Actions de sociétés; Capital social (droit commercial); Cession; France

Reforming corporate governance: Protecting minority shareholder rights through a strong corporate law system - Deniz, Ozden (American University, 2010)
Keywords: Association law; Corporate governance; Corporate law; Minority shareholder (protection)

L'utilité du capital social : étude de droit français - Mabika, Nany Elodie Itsiembou (Université Clermont-Ferrand 1, 2010)
En dépit des critiques proférées à l'encontre du capital social, cette notion existe encore et continue d'être régie en droit français comme la garantie minimale des créanciers. En effet, la loi assure sa formation au sein de toutes les formes sociales. Il se compose de la valeur des apports en nature et en numéraire et des ressources internes à la société. Toutefois, les textes révèlent des faiblesses notamment au niveau de l'exclusion de la valeur des apports en industrie et de l'institution du principe de libération fractionnée. D'où les solutions envisagées dans ces travaux sur ces points. Le capital social participe à la protection des créanciers, en ce que son montant est préservé des distributions effectuées au profit des associés et non des pertes sociales. Or, à l'exception, du compte courant d'associé, l'étude souligne la présence d'une réglementation non moins négligeable des mesures protégeant l'intangibilité du capital social afin de lui permettre d'être utile dans sa mission principale. En effet, les associés et les dirigeants notamment encourent des sanctions en cas de violation des textes régissant la formation et le maintien du capital. Ces mesures ayant une portée dissuasive marquent incontestablement l'intérêt que le législateur français porte au capital social. Le capital social n'intéresse pas que les créanciers puisqu'il correspond d'abord à l'investissement des associés. En effet, ces derniers apportent des biens au capital dans le but de s'enrichir personnellement. Le législateur institue à leur avantage un instrument de mesure de leurs droits et obligations qu'est le capital social. En effet, son principe de proportionnalité a l'avantage de proportionner et d'équilibrer tous les partages effectués entre eux afin d'éviter que certains associés ne s'imposent au détriment des autres.
Keywords: Capital social; Corporate law; Droit des sociétés; France; Société